Preliminary characterization of Yunnan dry-cured beef using lipidomics and volatilomics - Shuai Tang; Jiayan Tan; Jiao Li; Wen Xun; Nannan Zhou; Yanfei Du; Yucai Yang; Chunying Weng; Keshi Yang; Huiwen Dong; Guozhou Liao; Guiying Wang (Meat Science, 2026)

Density functional theory studies on CO2 adsorption mechanisms of biochar: a comprehensive review and future perspectives - Yujie Cheng; Xu Yang; Hongchi Chen; Jiao Ma; Fei Gao; Shuai Guo; Zhuozhi Wang; Lei Zhang; Li Xu; Boxiong Shen (Fuel, 2026)

Constructing a “hole highway” on Fe2O3: surface passivation and catalysis synergy for efficient photoelectrochemical water splitting - Tingling Wu; Wanping Li; Zongyu Yang; Jiancheng Hu; Keke Li; Jiao He; Jian Luo; Dan Zhou; Wei Hu (Fuel, 2026)

Shikonin alleviates high-fat diet-induced vascular aging and dysfunction by inhibiting oxidative stress and mitochondrial damage - Guang-qiu Ren; Hui-jun Liu; Ya-qi Guo; Mei-ling He; Jiao Li; Zhan-xia Li; Chen-hui Jia; Tong Liu; Jing Yang (Molecular Biology Reports, 2026)

Controlling filamentous cyanobacterial blooms requires adaptive, weather-informed strategy - Jiao Fang; Ming Su; Yande Li; Yuying Gui; Yufan Ai; Ogalo Joseph; Tengxin Cao; Shilong He; Min Yang (Water Research, 2026)

Fe-carbon-microbe coupling mediated CO₂ emission enhancement by dissolved black carbon in riparian soils - Yushu Yang; Zhenchen Li; Xiaoyun Li; Hongyi Wang; Li Gu; Hong Cheng; Binquan Jiao; Weiliang Pan (Soil and Tillage Research, 2026)

Multi-omics-based insights into the microbial community composition and quality characteristic differentiation potential between Xuanwei and Iberian dry-cured hams - Nannan Zhou; Jiayan Tan; Shuai Tang; Yanfei Du; Wen Xun; Yucai Yang; Jiao Li; Chunying Weng; Kesi Yang; Huiwen Dong; Enyong Pu; Guozhou Liao; et al. (International Journal of Food Microbiology, 2026)

Fabricating highly-dispersed W-O-Si structure via silanols modulation over WOx/SiO2 catalyst enables efficient olefin metathesis - Haoxuan Tan; Jianhao Jiao; Yun Zu; Qiang Li; Yucai Qin; Ye Yang; Kai He; Zhongxing Geng; Lijuan Song (Fuel, 2026)

Accelerating large-scale plane-wave hybrid functional calculations via low-rank approximations and high-performance computing on the Sugon supercomputer - Yufan Yao; Junwei Feng; Lingyun Wan; Shizhe Jiao; Jielan Li; Junshi Chen; Hong An; Xinming Qin; Wei Hu; Jinlong Yang (Computer Physics Communications, 2026)

Selective removal of fluoxetine by a core-shell molecularly imprinted TiO2 photocatalyst: degradation mechanism and toxicity mitigation - Ding Pan; Xin-Yi Jiao; Peng Liu; Jing-Hao Yang; Jing-Jun Qin; Cai-Shan Wang; Ying-Zhi Ding; Xue-Rong Wang; Yan-Chao Jin; Xin-Hui Liu; Zhang Liu; Li-Ping Li (Chemical Engineering Journal, 2026)

Development of a large-scale model test bench for GSHP-based tunnel insulation system - Tantan Zhu; Tianyi Li; Yi Yang; Chao Yang; Wang Jiao; Bin Zeng; Fuwang Ma (Cold Regions Science and Technology, 2026)

A study on the combined toxicity assessment of sulfamethoxazole and tetracycline hydrochloride in actual aquaculture wastewater using Chlorella vulgaris and the mechanisms of their removal - Yujie Jiao; Yang Liu; Bingyuan Li; Guotao Xiao; Guangjie Liu; Yanhui Ha; Jiawei Tian; Sujin Lu; Yaqi Mao (Bioresource Technology, 2026)

LEGDeeplab: A lightweight edge-guided model for semantic segmentation of maize leaf rust - Zhenbang Zhou; Haipeng Niu; Guangsheng Zhang; Longfei Zhou; Jingwei Qi; Guijun Yang; Tengyue Cui; Yinghua Jiao; Changchun Li (Computers and Electronics in Agriculture, 2026)

Electrospun membrane fabrication from waste PET plastic bottles and hydrophilic spray coating modification for efficient oil/water separation - Bingfan Li; Jiahao Liao; Chao Yang; Jiang Han; Tifeng Jiao (Journal of Environmental Chemical Engineering, 2026)

An alternative intensification strategy for Dirammox-based wastewater treatment via algal-bacterial granular sludge: Sludge granulation, nutrient removal and metagenomic analysis - Rui Cheng; Jiao Li; Meng Wu; Weiqiang Zhang; Xiaochen Xu; Guoquan Zhang; Fenglin Yang (Journal of Environmental Chemical Engineering, 2026)

Bioelectrochemical post-treatment of bio-treated kitchen digested wastewater for simultaneous removal of nitrite and refractory organics via microbial co-metabolism - Zhi Yang; Jiong Zhou; Shuxuan Lin; Jiao Li; Meng Cao; Jian Zhou (Journal of Environmental Chemical Engineering, 2026)

Ecological synergy thresholds: Mechanisms and governance implications for enhancing city-level ecosystem carbon sink in China - Shuoshuo Li; Yaobin Liu; Jiao Liu; Bao-Jie He; Yang Shen; Guoen Wei (Global and Planetary Change, 2026)

Regional differentiation of microbial communities and metabolites in Yunnan dry-cured beef: insights from high-throughput sequencing and untargeted metabolomics - Jiayan Tan; Shuai Tang; Nannan Zhou; Yucai Yang; Wen Xun; Jiao Li; Yanfei Du; Kesi Yang; Chunying Weng; Huiwen Dong; Guiying Wang; Guozhou Liao (Food Research International, 2026)

Elucidation of microbial community structure, small-molecule metabolic and flavor profile characteristics in Xuanwei ham under different processing techniques - Nannan Zhou; Wen Xun; Jiao Li; Yanfei Du; Yucai Yang; Jiayan Tan; Shuai Tang; Kesi Yang; Chunying Weng; Huiwen Dong; Enyong Pu; Guozhou Liao; et al. (Food Research International, 2026)

Cross-contamination and transfer dynamics of Listeria monocytogenes biofilms between food-contact surfaces and small yellow croaker (Larimichthys polyactis) - Jiarui Zhang; Chunyan Lv; Hu Shi; Juming Tang; Fanbin Kong; Feng Li; Yang Jiao (Food Control, 2026)

W-doped Na3V2(PO4)2F3/C cathode materials for high-rate and long-life sodium-ion batteries - Ying Liu; Ruifang Jiao; Yu Cao; Yang Shao; Chenping Li; Rundong Wan; Ruian Huang; Zhengfu Zhang; Yuejing Bin; Jinsong Wang; Xiaoping Yang (Chemical Engineering Journal, 2026)

Radical-driven formation of atmospheric carbonyls and their contributions to ozone and secondary organic aerosols in petrochemical city, China - Xue Yang; Yanmei Jiang; Gen Zhang; Ouyang Li; Qi Zhou; Xuan Ge; Zhifei Wang; Hongyu Xu; Jiao Qiao (Atmospheric Environment, 2026)

Allelic variation in cis-regulation of UNE12 underlies differential Verticillium wilt resistance in tetraploid cottons - Meixia Xie; Ziming Li; Jiaxuan Zhao; Minghui Ye; Mengjia Jiao; Zhicheng Wang; Xinxin Zheng; Xinyu Zhang; Jin Zhang; Yan Wang; Man Gu; Lingxia Zhai; et al. (Science Bulletin, 2026)

Digestibility and in vitro fecal fermentation of whole-wheat breads with different estimated glycemic indices - Yueyue Yang; Mingju Li; Mengfei Gao; Miaomiao Wang; Kejun Cheng; Aiquan Jiao; Zhengyu Jin (Food Chemistry, 2026)

Membrane-regulated seawater electrolysis for sustainable hydrogen production - Zhongting Liu; Jingfen Yuan; Sunpeng Shan; Guangpu Li; Song Gu; Cheng Chen; Wei Yu; Mingzhu Zhou; Saleem Raza; Ying Liu; Hongjun Lin; Yang Jiao; et al. (Water Research, 2026)

Bisphenol A induces osteoporosis by targeting LAMA4 and OLR1: Novel insights into environmental bone toxicity - Zhenyang Wang; Yongqin Chen; Jiling Ma; Yuxuan Yang; Ke Li; Xiejia Jiao; Biteng Xu; Guidong Shi; Liang Wang; Lei Qi (Toxicology, 2026)

Mechanisms of action and clinical research progress of photobiomodulation - Guiyun Shi; Kairui Wei; Ruocun Wang; Yayu Wang; Xianyu Wang; Luyang Gao; Shuyi Li; Bo Yang; Lina Tuerxunaili; Yi Jiao (Journal of Photochemistry and Photobiology B: Biology, 2026)

Genesis of boltwoodite in the hinterland surface of the Taklamakan Desert: Implication for exploration of sandstone-hosted uranium deposits - Liqun Wu; Shouyu Wang; Yangquan Jiao; Gui Wang; Liang Yue; Zhenpeng Tao; Wenlong Yang; Rui Chu; Mingzheng Zhang; Yingli Fu; Bingqian Li (Journal of Geochemical Exploration, 2026)

Intra-seafood strain diversity and temporal dynamics of Vibrio parahaemolyticus in a retail stall - Naike Wang; Fuxing Jiao; Jiancheng Wang; Shanwei Tong; Li Xie; Yixiang Jiang; Lulu Hu; Yinghui Li; Luigi Vezzulli; Jaime Martinez-Urtaza; Daniel Falush; Chao Yang (International Journal of Food Microbiology, 2026)

Effects of different processing methods on the nutritional components and in vitro digestion and fermentation characteristics of foxtail millet (Setaria italica) - Qi Li; Yufan Yang; Zirui Jiao; Wensen Zhao; Yingchun Zhu; Shuijing Wang; Xiaowen Wang (Food Research International, 2026)

Mechanistic investigation of carotenoid effects on lipid digestion-related processes: Pancreatic lipase inhibition and bile salt-mediated emulsion destabilization - Junkun Pan; Muhammad Nawaz; Keying Feng; Chengheng Li; Jiechao Liu; Hui Liu; Zhenzhen Lv; Wenbo Yang; Qiang Zhang; Zhonggao Jiao (Food Chemistry, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Machine learning–fugacity framework reveals the fate and environmental drivers of per- and polyfluoroalkyl substances in a mountainous river - Yanan Li; Wenjing Lv; Jiao Ren; Jianhui Tang; Jiayin Dai; Qiusheng He; Yang Cui; Lijuan Huo; Ke Zhang; Yitao Pan (Environmental Pollution, 2026)

An on-axis integrated microfluidic chemiluminescence immunoassay platform for rapid multiplex biomarker quantification - Qingjin Wu; Yujian Liu; Hailin Wu; Chenglong Wang; Quandong Li; Yongping Lin; Jiao Yang; Peng Li; Yingchun Li (Chemical Engineering Journal, 2026)

Pd single atoms anchored on mesoporous C3N5: An exceptional photocatalyst for hydrogen production - Yang Wang; Cun-Feng Fan; Jiao-Yan Li; Xiao-Qin Zheng; Xuan-Yi Liu; Ying Zhou; Jiahui Kou; Hengming Huang; Lin-Bing Sun (Chemical Engineering Journal, 2026)

Preparing large number of ultrafine microdroplets using annular ejector - Xiaokang Hu; Jiao Li; Zhenzhen Wang; Jingcai Cheng; Chao Yang; Fan Zhou; Aqiang Chen; Qingshan Huang (Chemical Engineering Journal, 2026)

Impact of enhanced high-latitude moisture transport on precipitation in Central Arid Region of Asia: Evidence from stable isotopes in precipitation - Ziwen Liu; Xinrui Lin; Yinying Jiao; Rui Li; Qinqin Wang; Xiaoyu Qi; Wenmin Li; Jiangwei Yang; Yuxin Miao; Zhijie Zheng; Yani Gun; Guofeng Zhu (Atmospheric Research, 2026)

NtGCN2 is associated with multilayer cadmium tolerance in tobacco via coordinated transcriptional changes in growth, antioxidant, and detoxification pathways - Xiaotian Shi; Ke Zhang; Songjie Zhang; Chong Chen; Manman Zhang; Hongbo Du; Xiaoquan Zhang; Yongxia Yang; Jiao Du; Ning Li; Songtao Zhang (Physiology and Molecular Biology of Plants, 2026)

Deep degassing in the southeastern margin of the Tibetan Plateau: Fluid fluxes, sources, and tectonic implications of the Ganzi-Litang suture zone - Deyang Zhao; Xiaocheng Zhou; Miao He; Jiao Tian; Yao Yang; Ju Zhang; Jingchao Li; Jinyuan Dong; Yucong Yan; Zhaojun Zeng; Yuwen Wang (Applied Geochemistry, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Adaptive real-time dosing strategy for advanced phosphorus removal using model predictive control and time-series analysis in WWTPs - Hongbo Liu; Xinyu Li; Yang Chen; Junbo Zhang; Jiao Li; Jiayu Hui; Jiaxi Liu; Wenhui An (Water Research, 2026)

Maize/peanut intercropping alleviates continuous peanut cropping stress via root exudate– and rhizosphere bacteria–mediated mechanisms - Zizheng Li; Li Cui; Jie Zhang; Tingting Yi; Hong Yu; Jialei Zhang; Sha Yang; Nianyuan Jiao; Feng Guo; Shubo Wan (Soil and Tillage Research, 2026)

Discovery of isotope 153Hf near the proton drip line via isochronous mass spectrometry: extending the nuclear landscape with HIAF - Hongfu Li; Min Zhang; Hongyang Jiao; Xing Xu; Chaoyi Fu; Jinyang Shi; Jiahao Lv; Xu Zhou; Yuanming Xing; Mingze Sun; Yuhu Zhang; Xiaohong Zhou; et al. (Science Bulletin, 2026)

Direct photoreforming of polylactic acid waste into valuable fuels via interface-activated superoxide radicals - Dongpo He; Ziyao Zhou; Fangming Zhao; Zheng Li; Jie Xiong; Jinyu Ding; Yang Wu; Liang Chen; Meng Zhou; Jun Hu; Junfa Zhu; Wensheng Yan; et al. (Science Bulletin, 2026)

Selective recruitment of NAT10-catalyzed ac4C-modified mRNAs into stress granules by poly(A)-binding protein promotes mRNA stability and plant heat stress tolerance - Wanhong Zhang; Yanxiao Bu; Yubing Jiao; Yingwen Wang; Lili Shen; Ying Li; Binna Lv; Tzu-Chieh Ho; Yih-Cherng Liou; Chin-Kuo Chen; Fei Han; Robert Y.L. Wang; et al. (Molecular Plant, 2026)

Magnetic response associated enhancement of magneto-Fenton degradation of p-Nitrophenol over amorphous FeSiB - Xingwang Sun; Mengyuan Wei; Jiao Li; Haipeng Yang; Jianwen Liu; Shenghui Xie (Journal of Cleaner Production, 2026)

Spatial structure-mediated attenuation of protective LAB–pathogen competition: Quantitative modeling in structured versus liquid matrices - Chun-lei Lu; Jiao Li; Hua-xiang Li; Zhen-quan Yang (International Journal of Food Microbiology, 2026)

Structural characterization, functional properties and formation mechanism of alkali-thermal induced egg white gel: from macroscopic gel properties to molecular conformation and interactions - Shende Hu; Xiaochen Liu; Luping Gu; Cuihua Chang; Junhua Li; Xiaosan Wang; Jun Sun; Shijian Dong; Han Jiao; Yanjun Yang; Yujie Su (Food Research International, 2026)

Differential analysis of the characteristic lipidome in bovine milk from desert regions from a lipidomics perspective - Wenya Jiao; Wentao Qian; Xuhui Fan; Pengjie Wang; Fazheng Ren; Menghui Wang; Jingru Zhao; Jinhui Yang; Hongliang Li; Yi Wang (Food Bioscience, 2026)

Long-term exposure to ambient PM2.5 constituents and risk of microvascular complications among individuals with type 2 diabetes mellitus: a nationwide cohort study in UK - Zhisheng Wang; Jiao Yang; Wanbing Huang; Dankang Li (Environmental Research, 2026)

Faecalibaculum rodentium- derived quinic acid- mediated Treg differentiation drives the attenuation intestinal inflammation by Agrimoniae Herba polysaccharides - Jiayan Hu; Yitong Yu; Zhibin Wang; Muyuan Wang; Yuxi Wang; Xiaowei Chen; Yuyue Liu; Mengyu Zheng; Chengtao Liang; Chenran Lv; Anqi Yang; Zhengdao Lin; et al. (Carbohydrate Polymers, 2026)

Spatiotemporal trajectories and heterogeneity of post-seismic debris flow activity after the wenchuan earthquake: deciphering decadal-scale evolution and driving mechanisms - Yu Yang; Kaiheng Hu; Chuan Tang; Jiao Wang; Wanjia Guo; Yinghua Cai; Chenxiao Tang; Ming Chen; Ning Li (Bulletin of Engineering Geology and the Environment, 2026)

Effects of organic slow-release fertilizer and superabsorbent polymer applications on banana yield, soil nutrient dynamics, and microbial ecology - Yangwenzheng Li; Feifei Chen; Jin Yin; Xiaoyan Sun; Shang Luo; Yang Yu; Jialiang Luo; Dong Li; Yangqiu Jiao; Zhiqiang Zhu (Applied Soil Ecology, 2026)

A Protective Role for Melatonin: Enhancing Heat Tolerance in Alisma plantago-aquatica Seedlings - Wen-hui Chen; Jiao Wang; Ke-yu Wang; De-qiang Li; Zi-zhong Tang; Yang-er Chen; Shu Yuan; Lu Zhang; Ming Yuan (Journal of Plant Growth Regulation, 2026)

Chemical composition of the endogenous fungus Fusarium sp. L-3 derived from Chinese Qinan agarwood - Ming-Li Han; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Na Xiao; You-Xing Zhao (Natural Product Research, 2026)

Multi-modal Features Analysis and Performance Assessment for Endovascular Surgery Skills - Shichao Liang; Panpan Yuan; Xuehuan Zhang; Shilong Li; Long Li; Bin Yang; Feng Gao; Yiming Deng; Liqun Jiao; Duanduan Chen (Annals of Biomedical Engineering, 2026)

Unraveling the Exosome-Derived ceRNA Network of Cartilage Injury in Kashin-Beck Disease Chondrocytes - Chaowei Wang; Lulu Bai; Liangyu Cui; Pengyan Jiao; Zhouyun Chen; Yang Liu; Yirong Qin; Hui Wang; Lian Liu; Qi Jing; Yuyang Ma; Yuequan Yuan; et al. (Biological Trace Element Research, 2026)

Exogenous methyl jasmonate enhances maize resistance by modulating secondary metabolites and suppressing Spodoptera frugiperda performance - Wenjing Li; Qingqing Ju; Ling Wang; Nina Yang; Haichen Yin; Shengbo Cong; Huaiheng Wu; Li Xue; Zhenbiao Jiao; Dong Xu; Peng Wan (Crop Protection, 2026)

Multi-level evaluation of sedimentary phosphorus release risk in freshwater water bodies based on dilute-acid extracted phosphorus as indicator - Lanwei Liang; Xin Zhao; Ruilian Guo; Zhenjun Liu; Xiaohan Liu; Xuemei Chen; Yuepeng Yin; Sen Gu; Yang Jiao; Qingman Li (Water Research, 2026)

Impact of dams on the water cycle in inland river basins of arid regions: based on runoff and isotope data - Zhijie Zheng; Guofeng Zhu; Rui Li; Yingying Jiao; Xiaoyu Qi; Jiangwei Yang; Wenmin Li; Yani Gun; Yuxin Miao; Qingyang Wang; Ziwen Liu (Journal of Hydrology, 2026)

The potential mechanism of nitrous oxide accumulation in wastewater treatment plants under different load conditions - Wen-Jiao Sang; Bing Gong; Chong-Yang Xing; Bei-Bei Chen; Zhi-Lin Zhang; Hui-Min Fu; Ya-Song Chen; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Yu-Lin Wang; Qiang Wang; et al. (International Biodeterioration & Biodegradation, 2026)

Homothorax regulates BarH1 expression and olfactory perception in Monochamus alternatus hope - Qi-Cheng Li; Sheng-Xin Wu; Mei-Jiao Yang; Pu-Yuan Zhang; Yan-Ling Wei; Man-Qun Wang (Insect Biochemistry and Molecular Biology, 2026)

A critical review on whether reducing the bandgap width is the sole approach to enhancing photocatalytic efficiency in g-C3N4-based materials - Yujie Jiao; Yang Liu; Guotao Xiao; Binyuan Li; Guangjie Liu; Jiali Lei; Qikai Liu; Shengyun Fu; Yin Luo; Sujin Lu; Yaqi Mao (Environmental Research, 2026)

Risk-informed multi-objective techno-economic assessment of air-to-liquid retrofits with heat recovery in legacy air-cooling data centers - Runchen Zhao; Jinpeng Hu; Yingtao Sun; Han Yang; Hao Yu; Cunlu Zhao; Qiuwang Wang; Zhigang Li; Fei Duan; Chun Yang; Yanmei Jiao; Dongxu Ji; et al. (Energy and Buildings, 2026)

Histidine-modified cinnamaldehyde/cisplatin nanodrugs and their synergistic antitumor effects in liver cancer - Shuxian Wang; Niuniu Yang; Jiao Li; Lu Wang; Sirong Li; Yaqian Zhang; Xu Cheng; Conghu Li (Chemical Engineering Journal, 2026)

Coupling mass transfer and chemisorption for efficient CO₂ sequestration in tailings-based materials: The role of multiscale porosity - Liuhua Yang; Haikun Liu; Zhenhua Li; Huazhe Jiao; Quanming Li; Zhentao Li; Shuisheng Chen; Botao Fu (Chemical Engineering Journal, 2026)

Techno-economic analysis, energy, exergy and environmental assessment of green methanol production via solar-driven gasification of corn stalk using Aspen Plus simulation - Jiaqi Jiao; Guosheng Li; Baoxin Niu; Lingyu Tai; Sunu Herwi Pranolo; Paolo De Filippis; Benedetta De Caprariis; Yang Zhang; Jingang Yao (Biomass and Bioenergy, 2026)

Research progress on rapid detection technology of soybean phenotypic indicators under saline-alkali stress - Haiou Guan; Jiaoying Li; Xiaodan Ma; Xueyan Zhang; Jiao Yang (Planta, 2026)

Impact of bedrock exposure and soil depth outweighs soil nutrient availability on woody species and functional diversity in lithology-differentiated habitats of dolomite and limestone - Jingjing You; Min Jiao; Xiaodong Li; Xihong Yang; Lipeng Zang; Danmei Chen; Qingfu Liu; Guangqi Zhang; Yuejun He (Plant and Soil, 2026)

Structural Variability in Bulk Soil and Rhizosphere Microbial Communities at Different Restoration Modes of Open-pit Coal Mine - Qingjun Meng; Mengke Ma; Shengnan Li; Xiaoyu Han; Tao Jin; Yang Jiao; Liyan Wang (Environmental Management, 2026)

Microglial tunneling nanotubes: an intercellular transfer facilitating mitochondrial dysfunction and neuroinflammation in experimental cerebral malaria - Yan Shen; Yi Wang; Chao Yang; Jun Wang; Yuxiao Huang; Qinghao Zhu; Ganze Li; Tong Li; Jiayi Sun; Jie Ren; Xiaolin Chen; Shuhan Xing; et al. (Apoptosis, 2026)

The Characteristic, Multiscale Dynamic Mechanisms and Impacts of Heavy Precipitation Events in the Yangtze River Valley - Yu Gu; Hongjia Lei; Lingzhi Zhang; Qianrong Ma; Yang Li; Shanlei Sun; Pengcheng Yan; Yang Jiao (International Journal of Climatology, 2026)
Heavy precipitation events (HPEs) in the Yangtze River Valley (YRV) pose persistent threats to population safety and infrastructure. This study classifies five population‐weighted HPE types (P1–P5) and examines their underlying dynamics using multiscale window transform and canonical energy transfer framework. Each type links to distinct circulation patterns. During 1979–2020, P1 and P2 are associated with Meiyu front systems, with P1 producing stronger precipitation. P2 accounts for 68% of all events, resulting in the greatest population exposure. P3 is driven by landfalling typhoons and represents the second most frequent type. P4 arises from short‐wave disturbances that primarily affect northern YRV, whereas P5 is concentrated in the western YRV and influenced by low‐vortex systems. Multiscale energy diagnostics show that most HPEs draw energy from the transfer of available potential energy (APE) from background to synoptic circulations, which subsequently convert to kinetic energy (KE). This transfer dominates the maintenance of P1 and P2. In contrast, P3 cases rely more on KE cascades, reflecting their stronger dynamic forcing. P4 and P5 exhibit weaker exchanges and depend more on background circulations. Additionally, future climate projections indicate that warming will amplify convective instability and strengthen APE‐to‐KE conversions in P1 and P3, but weaken these transfers in P2, P4, and P5. As a result, the currently dominant P2 type is expected to decline, while P1 and P3 become more frequent. By 2100, the population exposed to these type events will increase by more than 20%, posing substantial risks to societal resilience and adaptation.

Leguminous green manure drives SOC pool accumulation by regulating microbial activity and C-degrading genes in tropical soils - Long Jia; Peng Li; Tong Su; Zhuochen Lou; Jiale Ye; Ruiyun Yang; Jiaguo Jiao; Huixin Li; Feng Hu (Biology and Fertility of Soils, 2026)

Spatiotemporal decoupling of littoral and lacustrine geosmin dynamics: Implications for early warning in drinking water reservoirs - Yuying Gui; Tengxin Cao; Jie Yang; Jihui Qin; Ming Su; Ziyi Yang; Qi Zhang; Yufan Ai; Jiao Fang; Yingjie Li; Yuanhong Xiao; Zhixiang Hao; et al. (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Two new diterpenoids isolated from Siegesbeckia pubescens and their in vitro anti-inflammatory activities - Mei-Hui Zhou; A-Jiao Hou; Ling-Xia Qu; Jin-Bo Li; Liu Yang; Hai Jiang (Phytochemistry Letters, 2026)

Synergistic effects of chlorination and photoaging on tire related particles aging and tetracycline adsorption: Experimental and molecular dynamics insights - Huan Tang; Jiao Wu; Beichen Yang; Zhen Li; Yue Yin; Tinglin Huang; Gang Wen; Baoshan Xing (Journal of Hazardous Materials, 2026)

Multifaceted biocontrol mechanisms of Bacillus amyloliquefaciens F028 against Botrytis cinerea in postharvest tomato fruit - Fu-Lai Han; Jin-Xiu Zhao; Ming-Yi Wang; Meng-Fei Li; Zhe Zhang; Xiao-Hang Cui; Yu-Fei Li; Hao-Jie Jiang; Qing-Xue Jiao; Jie Yang; Xin Liu; Guang-Chao Liu (International Journal of Food Microbiology, 2026)

Unraveling microbial, metabolic, and flavor differences in Yunnan dry-cured beef with Staphylococcus inoculation and fruit-vegetable powder intervention: An integrated multi-omics analysis - Shuai Tang; Jiayan Tan; Qiongfang Yang; Wen Xun; Jiao Li; Yanfei Du; Jia Liu; Nannan Zhou; Guiying Wang; Guozhou Liao; Dahai Gu (International Journal of Gastronomy and Food Science, 2026)

Janus tissue adhesive patches with antibacterial drug delivery and visceral anti-adhesion capacity for gastrointestinal anastomosis repair - Xuguang Jiao; Shenshuo Gao; Hongyang Li; Junyan Yang; Siqi Liu; Wei Jing; Bo Zhao; Pengfei Wei; Yiqian Huang; Jianjun Qu (Chemical Engineering Journal, 2026)

Influence of ecological factors on the accumulation of active substances in Camellia nitidissima - Xiao-Xia Zhao; Meng-Xue Su; Shuang-Shuang Li; Hui Gao; Guo-Yue Yan; Shu-Rui Wang; Yan-Yuan Bai; Yang-Jiao Xie (Plant Biosystems, 2026)

YOLOv8m-CGSE: An Improved Lightweight YOLOv8m for Marine Oil Spill Detection - Qingyang Wang; Junjie Lu; Bin Yang; Chen Jiao; Tao Yue; Bo Song; Jianwu Jiang; Guoqing Zhou; Jingwen Li (Journal of Marine Science and Engineering, 2026)
Unmanned Aerial Vehicle (UAV) remote sensing images provide high-resolution and flexible monitoring data for oil spill detection. To address the high computational cost and low accuracy of traditional models, this study proposes an improved model, YOLOv8m-CGSE. The model replaces standard convolution with Group Shuffle Convolution (GSConv), substitutes the C2f module with SENetV2, and introduces a light-weight Cross-scale Context Fusion Module (CCFM) to enhance multi-scale feature representation while maintaining a lightweight structure. Mosaic augmentation was applied to the marine oil spill dataset, improving mAP50 and mAP50–95 to 85.4% and 62.0%, respectively. Based on YOLOv8m, the proposed YOLOv8m-CGSE achieved mAP50 and mAP50–95 of 91.2% and 73.3%, respectively, improving accuracy while reducing parameters by 16.1% and computational cost by 12.6%. Furthermore, a supplementary vulnerability test on highly deceptive oil-free sea surfaces demonstrated that the proposed model actively suppresses complex background clutter (e.g., ship wakes and wave anomalies), effectively reducing false positive detections from 21 (baseline) to 15. The results demonstrate that the proposed model effectively balances high precision, robustness against visual lookalikes and computational efficiency for real-time marine oil spill monitoring.

miR-141-5p positively regulates ACVRL1 expression to promote cervical cancer progression - Jianbing Liu; Yongzhi Jiao; Jinjuan Wang; Xiaohua Cui; Ying Gao; Yan Zhang; Jing Xu; Jianqing Hao; Yongli Hou; Wei Wang; Guang Yang; Li Li (Human Cell, 2026)

Redox oscillations in riparian zone stimulate carbon loss by enhancing microbial respiration - Zhenchen Li; Xiaoyun Li; Binquan Jiao; Yushu Yang; Hongyi Wang; Li Gu; Hainan Ai; Hong Cheng; Shang Cheng (Water Research, 2026)

Menopause status and modifiable risk factors for early menopause in China: a nationwide cross-sectional study on geographical disparities - Ting Guo; Xinyi Wu; Peihao Liu; Zifeng Cao; Keyan Xu; Li Yang; Guangmei Huang; Qianqian Ma; Xiaomin Yang; Xin Gao; Yehuan Yang; Yilin Yang; et al. (Science Bulletin, 2026)

Effective biocontrol of Enterococcus hirae in food products by a novel bacteriophage: Insights from genomic and phenotypic analyses - Haihua Yang; Peipei Li; Jiao Jiao; Tao Li; Yuhui Li; Zengjie Diao; Tianyuan Li; Hongfang Li; Yanhui Pan; Jinyu Wang; Hui Wang; Shengwei Hu; et al. (International Journal of Food Microbiology, 2026)

Proteomics perspective: differences in milk fat globule membrane proteins across regions and farming systems - Wenya Jiao; Wentao Qian; Pengjie Wang; Menghui Wang; Jingru Zhao; Jinhui Yang; Hongliang Li; Yi Wang (Food Research International, 2026)

Leaf functional traits and wood density of evergreen and deciduous tree species in a tropical karst forest - Yu-Meng Gao; Shi-Jian Yang; Jiao-Lin Zhang; Yan-Juan Jiang; Shu-Bin Zhang; Amy Ny Aina Aritsara; Guo-Hao Hu; Pei-Li Fu; Ze-Xin Fan; Kun-Fang Cao (Flora, 2026)

Topologically entangled binder network with chain–chain synergy for high-rate and long-life zinc‑iodine batteries - Rihui Li; Yanchun Sun; Yingjie Zhou; Xinzai Lv; Ailin Wang; Haoran Yuan; Jian Yang; Yang Jiao; Haiyan Wang (Chemical Engineering Journal, 2026)

Colorimetric-chemiluminescent competitive lateral flow immunoassay for cardiac troponin I detection based on Au@CoO NPs nanozyme - Yingying Xu; Xiali Zhang; Shengwei Yang; Jiang Liu; Yan Li; Peng Li; Guanghui Zhang; Jiao Yang; Yingchun Li (Chemical Engineering Journal, 2026)

Dauricine ameliorates intestinal inflammation and oxidative stress in DSS-induced colitis through TLR4/NLRP3/GSDMD-mediated pyroptosis and Nrf2 pathway - Lin Wang; Jingyuan Liu; Jiayi Wang; Yuxin Xie; Yanan Gao; Daili Xu; Jing Li; Jing Dong; Bingyao Li; Yanjun Cao; Yang Li; Jiao He (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Application of Magnetic-Seismic Geophysical Prospecting Technology in Identifying the Carboniferous Volcanic Rocks in the Chepaizi, West Margin of Junggar Basin - Guo-hua Jiao; Wei-ping Zhang; Jin-ke Zhou; Fu-gang Sun; Hai-tao Yang; Man Li; Zhu-qiang Li (Applied Geophysics, 2026)

Antifungal mechanisms of Bacillus velezensis Shannan.BV80-12 extracellular metabolites against the citrus postharvest pathogen Penicillium italicum - Rong Wang; Yali Tan; Feiyan Dong; Jiao Yang; Xiao Li; Tong Gu; Jialan Zhang; Li Li; Mengxiang Gao (Postharvest Biology and Technology, 2026)

Two new aromatic meroterpenoids from the fruiting bodies of Ganoderma calidophilum - Wei Liu; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Yan Hua; You-Xing Zhao (Phytochemistry Letters, 2026)

Combining riverbank filtration with membrane filtration for drinking water purification: Antibiotic resistance genes control and biofilm response - Weijia Gong; Minghao Xue; Li Yang; Jiao Yin; Jinyan Lu; Han Zhang (Journal of Cleaner Production, 2026)

Predicting nitrogen surplus in agricultural lands of China using a hybrid machine learning approach with smaller datasets and fewer features - Hao Wang; Gaofei Yin; Hongda Wen; Feng Wang; Ziwei Yang; Xueying Sun; Xulin Zhang; Huiqing Jiao; Mengyu Zhai; Wenchao Li; Hongbin Liu (Journal of Environmental Sciences, 2026)

Zn(II) ions-assisted regulation of pentagon defect density in biomass-derived carbon material for highly efficient peroxymonosulfate activation - Xiaorui Jiao; Chenjia Hu; Haoyun Zhang; Li Ding; Yajun Xiang; Hua Li; Min Xu; Gang Wang; Yanwei Yang; Fengjuan Chen; Yu Tang (Chemical Engineering Journal, 2026)

Arraying calcium carbonate core-shell nanoparticles densely on carbon fibers by coordination effect for interfacial enhancement of polydicyclopentadiene/carbon fiber felt (PDCPD/CFF) composites - Nan Xiao; Qi Jiao; Jieqing Shen; Hengti Wang; Xin Yang; Lian Wang; Yongjin Li (Chemical Engineering Journal, 2026)

In situ cultivation and chromogenic screening: a dual approach for rapid discovery of PDE1 inhibitors from pinus-tree associated microbes - Cui-Juan Xu; Shuo Li; Zhong-Duo Yang; Lin-Bo Liu; Yun-He Tuo; Yong-Jiao Niu; Lei-Lei Chen; Jian-Guo Chen; Tian-Kun Zhao; Ai-Hong Zhao (World Journal of Microbiology and Biotechnology, 2026)

Quantitative fatty acid signature analysis (QFASA) to explore the diet of the plateau pika (Ochotona curzoniae) during winter on the Qinghai–Xizang (Tibetan) plateau - Min Li; Zengguang Jin; Lukasz Oldakowski; Shien Ren; Baoguo Li; Li Li,; Jazmin Osorio-Mendoza; Yang Jiao; Siqi Yong; Dehua Wang; Yanming Zhang; Guanghou Shui; et al. (Oecologia, 2026)
The plateau pika, a keystone species of the Tibetan Plateau, is also widely poisoned as an agricultural pest. An intriguing observation is that pika are more abundant where their main competitor (domestic yak) is also most abundant. A recent study showed that this may be because pika supplement their diet in winter by consuming yak feces. Here we used quantitative fatty acid signatures analysis to explore pika diet and detect the possibility of coprophagy. We collected fat tissue from pika at 3 sites of varying elevation, and compared the abundance of 10 fatty acids (FA) in their body fat with those in their main potential foods (grass, roots and feces). We used an optimization program to establish the best-fit diet to the observed FA distributions, using mouse fat as a negative control. Pika fat FA signatures matched plateau foods far better than mouse fat. Faeces consumption doubled as the elevation of the site increased from 12.8% at the lowest site to 26.8% at the highest. In contrast consumption of roots showed the opposite pattern, comprising 32% at the lowest elevation and falling to virtually zero at the highest. That might reflect the time that the surface ground is frozen inhibiting the ability to dig for roots at higher elevation sites. Our data support the previous suggestion that pika eat yak feces, potentially giving them an over-winter survival advantage increasing their populations where yak are abundant. The full extent of coprophagy however requires more data in a larger population sample.

Multi-omics analysis reveals the regulatory network of soil stoichiometry and rhizosphere microbiota on saikosaponins in Bupleurum chinense DC. - Yan Wang; Quan Guo; Chen Yang; Honghong Jiao; Xiaochen Hu; Feng Yan; Mingying Zhang; Gang Zhang; Yimin Li (Applied Soil Ecology, 2026)

Smartphone-integrated molecularly imprinted sensor with convolutional neural networks for on-site detection of Norfloxacin - Yuge Chen; Jinjie You; Qin Li; Rui Chen; Liuquan Zhang; Haifeng Jiao; Jiafeng Yang; Hua Liu; Xizhi Shi (Analytica Chimica Acta, 2026)

Emergence of a novel porcine reproductive and respiratory syndrome virus strain inducing biphasic temperature fluctuations in Tianjin, northern China - Jia Wang; Yi-Han Lu; Bo-Han; Hai-Tao Yang; Xin-lei Li; Wen Sun; Shi-Qin Zhang; Zhuo-Ran Miao; Xue-Jiao Cheng; Chun-Xue You; Ying-Feng Sun (Research in Veterinary Science, 2026)

Biological treatment and purification of photofermentation biohydrogen production effluent to achieve high-value conversion of pollutants - Yinggang Jiao; Wen Cao; Haitao Liu; Yameng Li; Hong Liu; Bing Hu; Yang Zhang; Xudong Yang; Xiaohang Guo; Quanguo Zhang; Zhiping Zhang (Process Safety and Environmental Protection, 2026)

Oxidized- and hydroxylated-pennogenin saponins from the rhizomes of Paris fargesii and their hemostatic activity - Ling-Ling Yu; Lijin Jiao; Yan-Xi Li; Xu-Hong Li; Shan-Shan Ling; Long-Gao Xiao; Rui-Qi Liu; Wei Ni; Huan Yan; Yunheng Ji; Hai-Yang Liu (Phytochemistry, 2026)

An exploration of the continuous cropping obstacle in Gastrodia elata Bl.: Insights from the soil micro-ecology - Ting Li; Dingmao Yang; Bo Li; Honghong Jiao (Physiological and Molecular Plant Pathology, 2026)

π-conjugated microplastics act as hazard amplifiers of antibiotic resistance through cross-kingdom network engineering - Tongyi Yang; Ruiqian Yuan; Xiujie Wang; Linzhi Zhai; Xiaona Dong; Haifeng Chen; Zechong Guo; Huazhe Jiao; Li-zhi Huang; Yixuan Yang; Qian-qian Jia (Journal of Hazardous Materials, 2026)

Molecular insights into the activation mechanism of cloves in braised chicken: based on flavoromics, molecular docking and kinetic modeling - Yanfei Du; Nannan Zhou; Jiao Li; Wen Xun; Yucai Yang; Shuai Tang; Jiayan Tan; Kesi Yang; Chunying Weng; Huiwen Dong; Guozhou Liao; Guiying Wang (Food Research International, 2026)

Biodegradable cellulose-based electrostatically assisted air filter with high filtration efficiency and low resistance for sub-micron PMs - Jingyi Nie; Yueqing Li; Tingting Jiao; Ruiting Yang; Meiyun Zhang (Chemical Engineering Journal, 2026)

Green fluorescent carbon dots remodel soil microbial communities and regulate gene expression to enhance the salt stress adaptability of wheat - Tiantian Zheng; Qing Chi; Yue Wang; Ting Li; Wenzhe Liu; Luyao Zhao; Shuo Yang; Dongjie Cui; Ruqiang Xu; Zhen Jiao; Hanfeng Zhang (Plant and Soil, 2026)

Deciphering the shift in extreme precipitation over the lower reaches of the Yangtze River Basin: a synoptic-scale analysis - Jiao Li; Yang Zhao; Jianping Li; Lianyi Guo; Cheng Shen; Lujia Zhang; Lin Deng; Dandan Chen (Climate Dynamics, 2026)

Modeling and prediction of biogas production based on feature selection and SRG-GRU for anaerobic digestion process - Shipin Yang; Yuqiao Cai; Yinqiang Zhang; Wenhua Jiao; Qing Zhang; Xue Mei; Lijuan Li (Environment, Development and Sustainability, 2026)

Effects of seawater on the time-dependent viscosity and diffusion behavior of cement-sodium silicate grout - Shaolong Duan; Mi Zhang; Feng Yang; Qingsong Zhang; Yuanshu Jiao; Xianghui Li; Yanqing Men; Feng Liu (Tunnelling and Underground Space Technology, 2026)

Two new compounds isolated from a sponge-derived fungus Diaporthe sp. ZYX-Z-582 - Jia-Le Chang; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Hai-Tao Li; Jiao-Cen Guo; Hao-Fu Dai; Sha-Sha Liu; You-Xing Zhao (Phytochemistry Letters, 2026)

Functional characterization of key glycoside hydrolase genes in Trichoderma harzianum T-22 reveals their critical role in biocontrol against Phytophthora capsici - Haidong Wang; Weizhen Wang; Youhua Long; Xianhui Yin; Jiao Yang; Guanxing Peng; Xiang Chen; Yanjing Yin; Yuxian Zhu; Rongyu Li (Pesticide Biochemistry and Physiology, 2026)

PIV investigation of wake Vortex Evolution and flow characteristics of a teardrop-shaped slender body in uniform flow - Jingyu Niu; Jiao Sun; Nan Jiang; Jinghang Yang; Haoyang Li; Xiaolong Wang; Zhenze Han (Ocean Engineering, 2026)

A novel enhancement and robustness-based strategy for improving biotrickling filter resilience against shock load and starvation under low-temperature conditions - Mengyao Jiang; Jiao Yang; Jinliang Li; Shunyi Li; Yuxi Yan (Journal of Environmental Chemical Engineering, 2026)

Efficient immobilization of cadmium in water by lignin-based hydrogel-coated magnetic hydroxyapatite: Performance and mechanism - Lijun Lian; Jiao Yang; Yuxi Yan; Shunyi Li; Shuyan Wang (Journal of Environmental Chemical Engineering, 2026)

Integrated metabolomics and volatilomics reveal the impact of compound curing agents on lipid-related metabolites and volatile compounds in Xuanwei ham - Wen Xun; Yucai Yang; Yanru Zhong; Jiao Li; Nannan Zhou; Yanfei Du; Shuai Tang; Jiayan Tan; Keshi Yang; Chunying Weng; Huiwen Dong; Guozhou Liao; et al. (Food Research International, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Controllable patterning of liquid metals via DMD-based stencil lithography for high-conductivity and stretchable electronics - Dinggao Wang; Chao Zhang; Fahu Yang; Min Zhao; Feng Jiao; Zhongming Li; Haili Zhao; Tao Chen (Chemical Engineering Journal, 2026)

Nanoplastics and co-pollutants negatively affect the photosynthesis of photosynthetic organisms: insights from meta-analysis and machine learning - Chun Wu; Yan Wang; Jianling Wu; Daozhen Zhou; Jiao Ren; Jiajia Yang; Xiaofang Li; Guohong Liu; Yinbao Wu; Xiliang Yan (Chemical Engineering Journal, 2026)

In situ cancer stem cell vaccination and immune activation enabled by CSC-specific ligand screening - Yujia Li; Sijia Liu; Zimai Liu; Zixian Wu; Jiao Lu; Yuanyuan Wei; Qianxi Lu; Xiaoman Guo; Xinmeng Zhang; Yaxin Yang; Yilin Wang; Yingying Zhao; et al. (Chemical Engineering Journal, 2026)

Electronic modulation of nitride/hydroxide heterostructure for long-lasting urea oxidation reaction over 1000 h - Xian-Jun Niu; Guang-Sheng Qian; Yang Bai; Shen-Bing Sun; Lei Zhou; Wei-Yong Jiao; Ji-Sen Li (Chemical Engineering Journal, 2026)

Pretreatment sequence of torrefaction and leaching for high–alkali biomass valorization: Focus on elemental migration, mineral evolution, carbon structure and torrefaction mechanism - Bowen Li; Junling Du; Rui Diao; Xu Hu; Cunzhang Yang; Ran Jiao; Fenglei Qi; Zhenting Zha; Xiaohao Liu; Peiyong Ma (Bioresource Technology, 2026)

YIP: optimized YOLOv11-seg for accurate intramuscular fat percentage prediction in pigs using non-invasive ultrasound imaging - Junhao Zhang; Hang Jiao; Genyuan Li; Hanhan Li; Chenglin Li; Pengsheng Dong; Yan Liu; Bo Jiang; Peng Shang; Feng Yang; Chunli Li; Xinjian Li; et al. (Science China Life Sciences, 2026)

Responses of the phycosphere microbiota of Karenia mikimotoi to different nutritional conditions - Yucheng Zhang; Long Chen; Kunlei Ren; Ziyang Wang; Kang Wang; Xiaodong Li; Yang Liu; Zhenjun Kang; Ming Yang; Mengliang Jiao (Acta Oceanologica Sinica, 2026)

Distinct ecophysiological characteristics of two genetically similar vibriophages - Wenqing Li; Runqi Zhu; Keming Shi; Huiyu Ding; Shiying Ren; Song Xu; Jing Zhao; Nianzhi Jiao; Yunlan Yang; Rui Zhang (Marine Life Science & Technology, 2026)

Lanostane triterpenoids from the fruiting bodies of Ganoderma multipileum and their anti-inflammatory activities - Mei-Juan Li; Qing-Yun Ma; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Yan Hua; You-Xing Zhao (Natural Product Research, 2026)

A cucurbitane-type triterpene from Sorbaria kirilowii (Regel) Maxim. and its PDE1 inhibitory activity - Ke Yang; Shuo Li; Zhong-Duo Yang; Bing Sun; Tian-Kun Zhao; Ai-Hong Zhao; Jian-Guo Chen; Yong-Jiao Niu; Sahyun Kim (Natural Product Research, 2026)

Two new compounds isolated from an endophytic fungus Eutypella sp. XLE005 derived from Conus leopardus - Xin-Ming Li; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Du-Qiang Luo; You-Xing Zhao (Natural Product Research, 2026)

Research on High Prestress Rock Bolt Support Mechanism for Jointed Surrounding Rock in Tunnels Through Structural Plane Stress Compensation Analysis - Weiteng Li; Guanghui Yang; Bingjun Sun; Yuchun Mei; Xianfeng Yin; Yang Li; Shujun Jiao; Tingchun Li (Rock Mechanics and Rock Engineering, 2026)

Persteroid, a new steroid from the marine-derived fungus Penicillium sp. ZYX-Z-143 - Lu-Ting Dai; Li Yang; Zi-Peng Wang; Jiao-Cen Guo; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Zhi-Fang Yu; You-Xing Zhao (Natural Product Research, 2026)

Two CqCofilins inhibit WSSV infection by binding with Cqβ-actin cytoskeleton in Cherax quadricarinatus - Wei-dong Li; Jiao-yang Xu; Chuang Cui; Hai-peng Liu (Aquaculture, 2026)

Enhancing the resilience of toluene-removal biotricking filter at ultra-low temperatures with microbial activator amendment - Mengyao Jiang; Jinliang Li; Jiantao Zhang; Fengguang Chai; Jiao Yang; Shunyi Li; Yuxi Yan (Process Safety and Environmental Protection, 2026)

Changes in tree composition and diversity of streetscapes and their impact on allergenic risk of pollen during urban expansion: a case study in Chengdu, China - Ming-kun Chen; Zhen-ru Yang; He Li; Hua Zong; Chen Jiao (Landscape and Urban Planning, 2026)

Synergistic effect of radio frequency combined cold plasma treatment on Staphylococcus aureus inactivation in wheat flour - Jiarui Zhang; Zhenze Duanmu; Qingqing Zeng; Hu Shi; Juming Tang; Fanbin Kong; Feng Li; Zhe Wang; Yang Jiao (Innovative Food Science & Emerging Technologies, 2026)

The effect of yeaZ on formation and resuscitation of viable but nonculturable (VBNC) Salmonella enteritidis serovar enteritidis - Yuyang Jiao; Aiqi Yang; Xin Yu; Jiayu Yu; Jianlong Zhang; Linlin Jiang; Yao Li; Yang Liu; Hongwei Zhu; Xingxiao Zhang (Food Microbiology, 2026)

Simultaneous recycling rare and precious metals from their low-grade resources in the process of recycling silicon from diamond-wire-sawn silicon waste - Dongfang Yang; Jiao Chen; Wenhui Ma; Shaoyuan Li; Yun Lei (Chemical Engineering Journal, 2026)

TP-APTES-TEOS superhydrophilic coating transforms waste plastic bottles into valuable resources for efficient oil-water separation - Bingfan Li; Xiaowen Qian; Wenbo Wu; Shiyuan Liu; Shijun Wu; Jiang Han; Yong Han; Chao Yang; Tifeng Jiao (Chemical Engineering Journal, 2026)

miR-133b-3p Mitigates D-Galactose-Induced Hippocampal Neuron Aging Through Autophagy Regulation via the MAPK/ERK Signaling Pathway - Yang Cao; Chen Zhao; Jiaxin Li; Qiang Gao; Chunmei Lv; Jiao Wang; Na Qiang; Wenwen Zhang; Huiyu Su; Xinyu Min; Jinfeng Liu; Xiaoqi Dai; et al. (Molecular Neurobiology, 2026)

Impact of salinity gradient on sediment microbial communities and the functions of carbon, nitrogen, and sulfur cycling in coastal zone - Dahai Wang; Chuanshun Zhi; Xiaonong Hu; Zhen Wu; Wei Song; Jian Wang; Xianrui Huang; Fan Yang; Yufei Jiao; Yuxi Li (Applied Geochemistry, 2026)

Electronic reconfiguration enhanced oxidase-mimicking activity of Cu–Mn3O4 for colorimetric detection of total antioxidant capacity - Xiaoliang Li; Zizhong Chen; Chengji Sui; Lin Wang; Fengjia Zheng; Fenghua Li; Xiaoxu Yang; Yanni Jiao; Dafeng Jiang (Analytica Chimica Acta, 2026)

Flow-Balanced Scheduled Routing and Robust Refueling for Inland LNG-Fuelled Liner Shipping - De-Chang Li; Kun Li; Yu-Hua Duan; Yong-Bo Ji; Zhou-Meng Ai; Fang-Fang Jiao; Hua-Long Yang (Journal of Marine Science and Engineering, 2025)
Inland LNG-fuelled liner shipping is emerging as a significant trend, yet limited refueling infrastructure presents operational challenges. The complexity of inland navigation requires frequent speed adjustments to meet scheduled arrivals, which directly affects fuel consumption and refueling strategies. Additionally, imbalances in domestic and foreign trade container flows further increase operating costs for liner shipping companies. Given estimated weekly demands, considering navigational restrictions such as water depth and bridge clearance, as well as streamflow velocity, port time windows, empty container repositioning, port selection, speed adjustment, and uncertain fuel consumption, two novel models based on empty container arc variables and node variables are formulated, aiming to maximize voyage profit. These models are extended from divisible demand to indivisible demand cases. The explicit expression for the maximum fuel consumption under the worst-case speed deviation is derived, and an external linear approximation algorithm is proposed to linearize the nonlinear models while controlling approximation errors. Furthermore, the NP-hardness of the problem, the strict equivalence of the two modeling approaches, and the solution properties are proved. A case study of LNG-fuelled liner shipping on the Yangtze River shows the following: (1) for divisible demand, both models achieve optimal solutions within seconds, while for indivisible demand, the node-variable model outperforms the arc-variable model; (2) tactical strategies should be flexibly adjusted based on seasonal water depth, fuel prices, carbon taxes, speed deviations, and expected lock passage times; and (3) increasing fuel prices and carbon taxes generally reduce port calls and sailing speeds, suggesting that stricter fuel price and carbon tax policies can support the transition to green shipping. This study provides both theoretical guidance and managerial insights, supporting shipping companies in optimizing operations and promoting the development of sustainable inland shipping.

Artificial intelligence-assisted identification and screening strategies in sweetener design - Hujun Xie; Qingbo Jiao; Hao Li; Haoxin Ye; Gerui Ren; Min Huang; Tianxi Yang (Critical Reviews in Food Science and Nutrition, 2025)

Healthy diet and slower biological aging as protective factors against microvascular complications in type 2 diabetes - Han Zhou; Shuai Ben; Qian Ma; RuiKang Yang; Jiao Xia; XiongYi Yang; Jing Li; JunYa Zhu; Qian Liu; Ya Zhao; Na Li; Kun Liu; et al. (GeroScience, 2025)

Multi-modal feature integration from UAV-RGB imagery for high-precision cotton phenotyping: A paradigm shift toward cost-effective agricultural remote sensing - Xiaoyu Zhi; Qiaomin Chen; Yingchun Han; Beifang Yang; Yaru Wang; Fengqi Wu; Shiwu Xiong; Yahui Jiao; Yunzhen Ma; Shilong Shang; Tao Lin; Yaping Lei; et al. (Computers and Electronics in Agriculture, 2025)

Paleomagnetic results from Middle–Late Oligocene-Early Miocene red beds in the far western Lhasa terrane and their tectonic implications - Jiacheng Liang; Weiwei Bian; Jiahui Ma; Suo Wang; Xianwei Jiao; Yabo Zhang; Fei Han; Siqi Wang; Jikai Ding; Hanqing Zhao; Haiyan Li; Huaichun Wu; et al. (Tectonophysics, 2025)

A comprehensive survey on the P system optimization algorithms’ variants and their applications - Shipin Yang; Songlu Wang; Wenhua Jiao; Xue Mei; Qing Zhang; Yinqiang Zhang; Lijuan Li (Swarm and Evolutionary Computation, 2025)

Postharvest application of plasma-activated water delays anthracnose symptom development in apples - Yingman Gao; Ruichen Sha; Guihuan Wei; Lingling Yang; Yupan Zhu; Yudong Liu; Ruonan Ma; Zhen Jiao; Bing Li (Postharvest Biology and Technology, 2025)

Metal–phenolic networks improve biocontrol effect of Bacillus velezensis DM14 against pear anthracnose - Jianfeng Du; Heng Li; Shenjie Liu; Jiawei Tang; Xin Zhao; Yiming Liu; Limin Wu; Yue Li; Qixiong Gao; Fuxin Sun; Ninghai Lu; Xueliang Tian; et al. (Pesticide Biochemistry and Physiology, 2025)

Electrokinetic remediation of hexavalent chromium-contaminated soil using low-molecular-weight organic acids combined with ion exchange membranes - Shuo Li; Jiao Yang; Qing Wang; Lieyan Shi; Pengxiang Liang; Yimin Hao; Wenjing Ge; Sviatoslav Viktorovich Fedorov; Hao Liu; Jingqing Gao (Journal of Water Process Engineering, 2025)

Application, challenges, and opportunities of organic metal frameworks materials in oil-water separation - Jiahao Liao; Bingfan Li; Longfei Ran; Jiang Han; Chao Yang; Zhijun Li; Tifeng Jiao (Journal of Environmental Chemical Engineering, 2025)

Optimization of buffer adjustment strategies for enhancing stability and hydrogen yield in high solid-phase biohydrogen production systems - Yameng Li; Hang Yan; Quanguo Zhang; Yinggang Jiao; Xudong Yang; Fuke Ai; Guihong Yin; Junyu Tao; Yanyan Jing; Bing Hu; Zhiping Zhang (Journal of Environmental Chemical Engineering, 2025)

The SERS method based on the COF-ag substrate, combined with machine learning, is used for the detection of tetracycline and oxytetracycline in milk. - Yunpeng Shang; Anqi Hu; Chaoqun Ma; Jiao Gu; Chun Zhu; Lei Li; Hui Gao; Taiqun Yang; Guoqing Chen (Food Chemistry, 2025)

Disrupting Aeromonas sobria quorum sensing with HNTs-zingerone embedded CS/CMC-Na film: A novel strategy for prolonging freshness of refrigerated sea bass fillets - Yanqing Li; Xuchen Li; Shaomei Li; Jiao Li; Xiang Zou; Hongwei Zhan; Guanyuan Qu; Lixiu Zhang; Yongjun Sun; Wenming Ju; Mengqi Ye; Pengdong Sun; et al. (Food Packaging and Shelf Life, 2025)

Effect of exogenous protein on 3D printing and gelling properties of low-salt sliver carp surimi (Hypophthalmichthys molitrix) - Jinsong Wu; Yaxing Yang; Feng Li; Hu Shi; Fanbin Kong; Juming Tang; Yang Jiao (Food and Bioproducts Processing, 2025)

Characterizing seasonal changes in perfluoroalkyl substances in lake sediment by environmental magnetism from a machine learning perspective - Ligang Deng; Yuteng Zhang; Jialu Shi; Jiao Yang; Daojun Yang; An Yi; Lijian Sun; Yueda Yu; Tingting Yu; Xin Qian; Huiming Li; Yifan Fan (Environmental Research, 2025)

Performance and toxicity assessment of photocatalytic degradation of sulfanilamide by g-C3N4 nanosheets constructed using temperature gradient regulated etching - Yujie Jiao; Yaqi Mao; Fei Fu; Yongxia Ma; Ru Li; Qikai Liu; Jiali Lei; Sujin Lu; Yang Liu (Environmental Research, 2025)

Covalent organic cage with boosting stability and biosafety for integrated platform: MRI mediated chem/photodynamic therapy - Xin Linghu; Wei He; Kangkang Huang; Weichen Li; Hong Yang; Shiping Yang; Jingjing Jiao (Chemical Engineering Journal, 2025)

Butterfly-inspired ultraviolet vision chip based on ZnO memristor arrays for real-time dynamic plant motion tracking - Yang Liu; Junmeng Guo; Jiao Wang; Yuwei Zhao; Yatao Zhang; Guangxiang Gu; Haoran Ruan; Pengfei Li; Yu Sun; Luyao Zhang; Zuliang Du; Gang Cheng (Chemical Engineering Journal, 2025)

Asymmetric CALF-20/PIM-1 MMMs with anisotropic properties for efficient carbon capture - Yuchao Ma; Wei Zhao; Dacheng Zhang; Kaihua Li; Qian Zhang; Ge Wang; Zhanfeng Zhao; Long Jiao; Leixin Yang; Ningning Gao; Bowen Cheng (Chemical Engineering Journal, 2025)

Study on the Influence of Geological Fault Structure on the Energy Evolution of Rockbursts - Shoujian Peng; Chaolong Qin; Qingfeng Xu; Jiang Xu; Yan Yang; Feng Jiao; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

Bacillus licheniformis B410 Alleviates Inflammation Induced by Lipopolysaccharide and Salmonella by Inhibiting NF-κB and IRF Signaling Pathways in Macrophages - Dan Xiong; Tao Sun; Mengru Liu; Bo Wang; Tianzhu Guan; Li Song; Xinan Jiao; Zhenquan Yang (Probiotics and Antimicrobial Proteins, 2025)

Insights into tissue-specific and species-dependent divergence in endophytic microbial communities of two closely related halophytes Reaumuria kaschgarica and R. songarica - Jiao Li; Xin Xiang; Wenjing Li; Boai Jia; Wenlin Yang; Wei Wang; Chengti Xu; Hengxia Yin; Benyin Zhang (Plant and Soil, 2025)

Discovery of highly effective antiviral agents based on flavonoid-benzothiazole against TMV - Jiao Tian; Chunmei Hu; Tianyu Deng; Qing Zhou; Xingping Luo; Jieyu Li; Haotao Pu; Ying Yang; Da Liu; Wei Xue (Molecular Diversity, 2025)

Enhanced degradation of polycyclic aromatic hydrocarbons by Fe(II)-Modified Biochar-catalyzed persulfate activation - Ziyan Yang; Dan Li; Ruoyang Jiao; Jingyi Zhao; Qian Jia; Xin Du (Journal of Soils and Sediments, 2025)

Biochar enhances yield and nitrogen utilization from organic fertilizers in the organic cultivation of Chinese flowering cabbage in Northwestern China - Zhan Wang; Jiao Yang; Yinkun Li; Kai Li; Yong Wang (Journal of Soils and Sediments, 2025)

Synergistic Mechanism of the Combined Application of Humic Acid and Biological Nitrification Inhibitors on Maize Yield and Nitrogen Transformation and Utilization - Yingchun Liu; Xinyue Zhong; Xianfeng Zhang; Wenliang Yang; Jiao Yang; Guocui Ren; Mengrou Li; Anning Zhu; Xiuli Xin (Journal of Soil Science and Plant Nutrition, 2025)

Gradient Drought Durations in Drying and Rewetting Cycles Reduce Soil Carbon Loss via the Crucial Roles of Microbial Biomass and Bacterial Diversity - Panpan Jiao; Lei Yang; Zhongwu Li; Xiaodong Nie (Journal of Soil Science and Plant Nutrition, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Effect of thermal-hydraulic parameters and pH on the corrosion product deposition in steam generator based on CFD - Yunchen Lai; Haiyan Xie; Shiyu Tan; Ke Wang; Dongyun Li; Xuesong Li; Yang Gao; Hongguo Hou; Nan Chao; Caishan Jiao; Yu Zhou (Annals of Nuclear Energy, 2025)

Optimization for crop-livestock systems through a holistic watershed based on water quality requirement: a case study in China - Yueying Wei; Gaofei Yin; Bingxin Tong; Ziwei Yang; Jiabao Wang; Huiqing Jiao; Hongda Wen; Xinzhong Du; Hongbin Liu; Wenchao Li (Agricultural Systems, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

BmeIF4E2 promotes AcMNPV infection in the silkworm, Bombyx mori, by direct interaction - Xin-Yi Ding; Jiang-Zhi Su; Wen-Jing Yu; Qian-Qian Jiao; Zuo-Min Shao; Ai-Jun Wan; Sheng Qin; Xia Sun; Xue-Yang Wang; Ding-Ding Lü; Mu-Wang Li (Pesticide Biochemistry and Physiology, 2025)

Electrochemical urine biopsy with a peptide/peptide nucleic acid tandem probe for Cathepsin B analysis - Gang Wang; Wen Liang; Noshin Afshan; Yuxin Lei; Haoyu Li; Yang Xiang; Jin Jiao (Chemical Engineering Journal, 2025)

Magnetically directed interfacial polyamerization of Fe3O4@CdS@CQDs-embedded polyamide nanofiltration membranes with enhanced separation and photocatalytic self-cleaning performance - Erqiao Chen; Zhihao Chen; Zhongting Liu; Mingzhu Zhou; Bisheng Li; Renjie Li; Liguo Shen; Yang Jiao; Hongjun Lin; Yanchao Xu (Chemical Engineering Journal, 2025)

Study on the effect of summer classroom temperature on cognitive performance and heart rate variability in elementary school students - Yuerong Li; Qun Zhang; Peng Wang; Yanyan Li; Jiao Yang; Shiliang Wang (Building and Environment, 2025)

Interdecadal shift in North Indian Ocean-South China Sea influence on the evolution of the East Asian summer monsoon from July to August - Jiazhe Duan; Hua Li; Na Yang; Yong Liu; Huixin Li; Yang Jiao; Botao Zhou (Atmospheric Research, 2025)

DTX1 Modulates Microglial M1 Polarization and Exacerbates Neuroinflammation in Traumatic Brain Injury Model Rats through NF—κB/IRF5 - Yonghui Zhang; Zongxing Zou; Rongwei Li; Xiaochuan Fu; Ganyu Li; Lu Wang; Yan Zhang; Yuyu Chen; Zuzhi Chen; Dongfang Yang; Yan Jiao; Weiguang Zhang; et al. (Molecular Neurobiology, 2025)

Weathering modulates soil microbial biodiversity in a Sygera Mountain alpine forest, Tibetan Plateau - Hongzhe Jiao; Qiuyu Chen; Bin Niu; Xiaoqin Yang; Guiyao Zhou; Ang Hu; Jian Wang; Guicai Si; Jiangrong Li; Eryuan Liang; Manuel Delgado-Baquerizo; Gengxin Zhang (Applied Soil Ecology, 2025)

Molecular interactions of icariin and icariside II with human serum albumin: a spectroscopic and molecular docking analysis - Na Wang; Kang-huai Zhang; Jiao Xie; Li Zhang; Hai-tao Wang; Xin Yang; Yi Zhao (Natural Product Research, 2025)

Deep learning-based species identification of gymnosperm xylem: The practice in digital forestry - Chang Zheng; Tuo He; Lichao Jiao; Yang Lu; Shoujia Liu; Tianxiao Li; Yuanyuan Miao; Dejun Feng; Jian Lin; Xian Feng; Zhonghua Huang; Min Yu; et al. (Computers and Electronics in Agriculture, 2025)

Two new compounds from the root bark of Acanthopanax gracilistylus and their inhibitory effects on neutrophil elastase, cyclooxygenase-1, and cyclooxygenase-2 in vitro - Jin-Yuan Duan; Shu-Ming Li; Hao-Dong Yang; Yuan-Gui Yang; Jiao-Feng Wu; Jing-Yu Weng; Hong-Bo Liu; Hong-Bo Xu (Phytochemistry Letters, 2025)

Quantitative characterization of uncertainty in the source apportionment induced by the dual spatial heterogeneity of soil heavy metals - Jin Wu; Mengyuan Yang; Jiao Li; Guoqiang Wang; Ganghui Zhu; A. Yinglan; Baolin Xue; Mimi Gong; Ruihui Chen (Journal of Hazardous Materials, 2025)

Trophodynamic mechanisms of per- and polyfluoroalkyl substances in oligotrophic ecosystem from the Tibetan Plateau river - Yanan Li; Jiao Ren; Yawen Li; Fengfeng Dong; Qiusheng He; Yang Cui; Ke Zhang; Zhentao Wang; Xinqi Xin; Yitao Pan; Jianhui Tang (Journal of Hazardous Materials, 2025)

A ratiometric fluorescence probe based on curcumin and supramolecular deep eutectic solvent for in vivo imaging cerebral pH - Wan-Chun Luo; Jin-Tao Zhang; Li-Na Bao; Lin-Jiao Yang; Zi-Ke Yang; Ming Jiang; Xu Yu; Li Xu (Chemical Engineering Journal, 2025)

Highly selective reduction of CO2 to CH4 mediated by 2D/0D Cs3Bi2Br9/BiOBr heterojunctions with atomic-level intimate interfaces - Tingting Ren; Yanqing Zhang; Suning Fu; Yuanming Hou; Jiaxin Wang; Jingyi Qin; Zhengzheng Xie; Jianjun Yang; Zhongjie Guan; Shilong Jiao; Qiuye Li; Xianwei Fu (Chemical Engineering Journal, 2025)

CRISPR-Cas opens a new era of antimicrobial therapy as a powerful gene editing tool - Shuqi Yang; Xin Jiao; Jiayi Liu; Yanxia Liu; Menglu Wang; Sihan Li; Jinjuan Qiao (World Journal of Microbiology and Biotechnology, 2025)

RsRCO and RsLMI1 co-regulate the formation of lobed leaf in radish (Raphanus sativus L.) - Qian Yang; Lei Cui; Xiaoyao Li; Zhaoxin Peng; Haoyan Sun; Caixia Gan; Zhen Hu; Zhixiong Liu; Zhenbiao Jiao; Zhengming Qiu; Chenghuan Yan; Xiaohui Deng (Theoretical and Applied Genetics, 2025)

Proteomic analysis reveals novel insights into astaxanthin synthesis in Haematococcus pluvialis - Zhaokun Wang; Haiyan Ma; Jiao Zhan; Li Yuan; Mingkun Yang; Feng Ge (Algal Research, 2025)

GSDME-dependent astrocyte pyroptosis promotes the progression of neuroinflammation in experimental cerebral malaria - Jun Wang; Qinghao Zhu; Guodong Tong; Kangjie Yu; Jiao Liang; Yuxiao Huang; Yi Wang; Chao Yang; Tong Li; Weilu Liang; Ganze Li; Xiaoran Liu; et al. (Apoptosis, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

The transportation and driven mechanisms of per- and polyfluoroalkyl substances (PFAS) in various saline vadose environments - Yue Lan; Xingchun Jiao; Huifeng Yang; Bo Song; Litang Hu; Li Wang; Yuhan Gao (Journal of Hydrology, 2025)

Cold atmospheric plasma-derived ROS detoxifies deoxynivalenol-induced nephrotoxicity - Ruonan Ma; Junxia Feng; Hangbo Xu; Xiaoying Zhou; Chunli Liu; Guoyu Zhou; Dongjie Cui; Yupan Zhu; Junhu Wan; Dezheng Yang; Gautam Sethi; Xudong Yang; et al. (Journal of Hazardous Materials, 2025)

Glycerol enhanced simultaneous selenite bioremediation and astaxanthin biosynthesis in Haematococcus lacustris - Yu-Hu Jiao; Zhong-Hong Zhang; Yu-Hong Liu; Yan Huang; Meng-Ting Jiang; Yong-Teng Zhao; Xinfei Xie; Wei-Dong Yang; Hong-Ye Li; Lei Cui; Xiang Wang (Journal of Hazardous Materials, 2025)

Co-Exposure of airborne microplastics and chromium: Impairment of pulmonary surfactant monolayer - Linfeng Zhang; Yan Cao; Jie Li; Chao Li; Yanlin Yang; Jiao Li; Xuewei Hu; Xiangfen Cui; Qun Zhao; Haoran Song; Jianhong Huang; Senlin Tian (Journal of Hazardous Materials, 2025)

A N^N-bidentate ligand modified with tetraphenylethylene derivative for uranium detection and decorporation in vitro and in vivo - Yong Li; Bin Yang; Wangbo Qu; Jiao Lu; Zhou Wu; Jun Wang; Ruihong Yao; Yanli Li; Zhihao Lu; Shihai Yan; Zhirong Geng; Zhilin Wang (Journal of Hazardous Materials, 2025)

Preparation of superhydrophilic membranes from discarded masks for efficient oil-water separation and anti-crude oil adhesion - Bingfan Li; Xiaowen Qian; Jiang Han; Yong Han; Chao Yang; Tifeng Jiao (Fuel, 2025)

Multifunctional au-DTNB-ag nanoparticles immunoprobes based on color-Raman properties for lateral flow immunoassay detection of Glycinin - Peng Bo Huang; Jing Long Qu; Shuo Yang; Tian Jiao Shui; Huan Huan Yang; Li Ping Cheng; Yang Qin; Jun Xi (Food Chemistry, 2025)

Phytol inhibits quorum sensing and biogenic amine production in Pseudomonas fluorescens PF12 - Hongwei Zhan; Xiang Zou; Jiao Li; Lixiu Zhang; Guanyuan Qu; Yanqing Li; Yongjun Sun; Wenming Ju; Mengqi Ye; Yang Deng; Ting Ding (Food Bioscience, 2025)

Polyphenol-based coacervate droplets as building blocks for protocells and prototissues - Qi Xie; Wei Chen; Zijian Huang; Yuan Gao; Haoyu Zhang; Zhanhao Zhou; Samira Batur; Chuansheng Fu; Jiao Zhang; Conglian Yang; Junjun Liu; Li Kong; et al. (Chemical Engineering Journal, 2025)

Overcoming the bottleneck in one-electron reduction of CO2 with mechanical energy-driven triboelectric plasma-enabled catalysis - Qinglong Ru; Bao Zhang; Sumin Li; Jiao Wang; Wei Jiang; Nannan Liu; Hui Hu; Yongcui Yang; Taifeng Liu; Qianhong Gao; Yifei Zhu; Yu Jia; et al. (Chemical Engineering Journal, 2025)

Water use patterns of riparian Populus euphratica in the Hongyashan Reservoir of Northwest China’s arid region: evidence from water isotope data - Yani Gun; Lei Wang; Guofeng Zhu; Yinying Jiao; Xiaoyu Qi; Rui Li; Jiangwei Yang; Yuxin Miao; Zhijie Zheng; Wenmin Li (Plant and Soil, 2025)

Microbial life-history strategies mediate temperature effects on organic carbon pools in black soils - Lihui Lyu; Chaoqun Wang; Kunkun Fan; Jiasui Li; Teng Yang; Guifeng Gao; Ru Sun; Jiao Wang; Xiyuan Xu; Yuxiao Zhang; Yuying Ma; Jiabao Zhang; et al. (Soil Ecology Letters, 2025)

Changes in growth and transcriptome expression patterns in mandarin fish (Siniperca scherzeri) under different photoperiods - Jiao Li; Yong Wei; Jun Song; Jun Yang; Xu-Fang Liang; Ke Lu; Qiuling Wang; Ke-Xiang Wang; Kaiting Zhi; Dan Zhao; Yan Wang; Yufeng Zhang; et al. (Acta Oceanologica Sinica, 2025)

Deciphering the UAV-LiDAR contribution to vegetation classification using interpretable machine learning - Tao Huang; Lei Jiao; Yingfei Bai; Jianwu Yan; Xiping Yang; Jiayu Liu; Wei Liang; Da Luo; Liwei Zhang; Hao Wang; Zhaolin Li; Zongshan Li; et al. (Computers and Electronics in Agriculture, 2025)

Atrazine exposure induces TDP-43 protein translocation: A potential mechanism for prefrontal cortical neurodegeneration induced by environmental pollutants - Yuan Ma; Kaidong Wang; Yuxuan Jiao; Yujing Li; Rong Hu; Yang Li; Ge Shi; Min Huang (Toxicology, 2025)

The day-one experiment at SLEGS: systematic measurement of the ( γ , 1n) cross sections on 197 Au and 159 Tb for resolving existing data discrepancies - Zirui Hao; Gongtao Fan; Hongwei Wang; Longxiang Liu; Hanghua Xu; Yue Zhang; Yuxuan Yang; Sheng Jin; Kaijie Chen; Zhicai Li; Pu Jiao; Qiankun Sun; et al. (Science Bulletin, 2025)

Selective electroreduction of carbon dioxide to ethylene over stable iodide-induced asymmetric copper sites within a metal-organic polyhedron - Yaguang Peng; Yinlin Chen; Zi Wang; Yaoyu Yin; Jiangnan Li; Huanyan Liu; Jiapeng Jiao; Wenling Zhao; Ran Duan; Pei Zhang; Jiahao Yang; Hengan Wang; et al. (Science Bulletin, 2025)

Influence of inorganic impurities in fermentation broth on the crystallization mechanism of co-produced bio-based cadaverine succinate: Experimental and molecular simulations - Xiaojie Zhao; Huazong Liu; Lu Wang; Wenxi Ji; Qixu Hu; Yue Yang; Jiao Feng; Xin Wang; Ganlu Li; Hui Li; Kequan Chen (Journal of Environmental Chemical Engineering, 2025)

Construction of Pt single-atom active sites on defective Ce-MOF for enhanced photocatalytic decomposition of DMMP - Yuanyuan Yang; Xuan Jiao; Jiahao Li; Shuoying Yin; Wanbo Chen; Feiyan Fu (Journal of Environmental Chemical Engineering, 2025)

Weathering and recycling controls on rare earth element behavior: A comparative study on granitic, basaltic and aeolian red soil crusts - Long Han; Bin Lü; Chaoqiang Li; Jiao Yang; Wenjing Ge; Jianlei Gao; Xingxing Wang; Yan Zheng (Geochimica et Cosmochimica Acta, 2025)

Effect of the degree of methyl esterification on the physicochemical properties and hypoglycaemic potential of pectin - Xu Jiao; Bingjie Yang; Fei Li; Luyao Zhang; Yunlu Wei; Jing Zhao; Quanhong Li (Food Chemistry, 2025)

A comparative study of human norovirus and human sapovirus contamination in oysters (Crassostrea gigas) tissues from physical markets and e-commerce platforms in Guangzhou, China - Junshan Gao; Yijing Li; Yang Jiao; Weicheng Cai; Jumei Zhang; Liang Xue (Food Microbiology, 2025)

Effect of environmental conditions on the survival and transfer of Enterococcus faecium between wheat flour and selected contact surfaces - Chunyan Lv; Jiarui Zhang; Feng Li; Hu Shi; Fanbing Kong; Yang Jiao (Food Microbiology, 2025)

Metal exposure is associated with cognitive function and plasma sTrem2 levels in coal miners: a cross-sectional study - Yang Li; Kaidong Wang; Ge Shi; Ai Qi; Yujing Li; Yuxuan Jiao; Rong Hu; Guilin Hu; Yonghang Li; Zhuoheng Shen; Min Huang (Environmental Research, 2025)

Green manuring with balanced fertilization improves soil ecosystem multifunctionality by enhancing soil quality and enzyme activities in a smooth vetch-maize rotation system - Long Jia; Huijuan Zhang; Jiyu Lu; Yan Liang; Yueda Li; Luyao Xu; Jiale Ye; Ruiyun Yang; Peng Li; Jiaguo Jiao; Xia Wang; Feng Hu (Agriculture, Ecosystems & Environment, 2025)

Streptococcus suis AdcA interacts with factor H and inhibits C3b deposition on the bacteria to participate in complement evasion - Siqi Pang; Zhulin Qiao; Jiajia Xu; Hao Tang; Qiuhong Zhang; Weiyao Han; Lu Peng; Jiaojiao Yang; Jiao Zhang; Qi Huang; Rui Zhou; Lu Li (Veterinary Microbiology, 2025)

Virus-host interactions and their effects on the prokaryotic community in thermokarst lakes - Yutong Song; Guibiao Yang; Pandeng Wang; Xiaoqing Luo; Jian-Yu Jiao; Zhihu Zheng; Luyao Kang; Dianye Zhang; Ziliang Li; Wei Zhou; Xuning Liu; Lili Han; et al. (Science Bulletin, 2025)

Antibiotic-induced multi-trophic effects and their cascades in a sub-tropical freshwater ecosystem - Kai-Sheng Yao; Pei-Liang Zhou; Li-Juan Tan; Hua-Qiao Yang; Lu-Kai Qiao; Fang-Zhou Gao; You-Sheng Liu; Feng-Jiao Peng; Guang-Guo Ying; Paul J. Van den Brink (Journal of Hazardous Materials, 2025)

Metagenomic analysis reveals soil microbiome responses to microplastics and ZnO nanoparticles in an agricultural soil - Jiao Sun; Weiwei Yang; Mingwei Li; Shuwu Zhang; Yuhuan Sun; Fayuan Wang (Journal of Hazardous Materials, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Biomarkers reflecting the toxicity of neonicotinoid insecticides to the central nervous system - Yeru Yang; Xiaoyang Jiao; Fen Yao; Ze Lin; Xiaolin Guo; Meimei Wang; Qingdong Xie; Wenhua Liu; Adela Jing Li; Zhen Wang (Environmental Pollution, 2025)

Fundamental insights into Brønsted acid-induced adduction improve small metabolite profiling in mass spectrometry - Wanshan Liu; Wei Chen; Yanyan Li; Shouzhi Yang; Jing Cao; Jiao Wu; Yida Huang; Ruimin Wang; Xiaonan Chen; Lin Huang; Jiayi Wang; Kun Qian; et al. (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

A Rock Strength Prediction Model Utilizing Real-Time Data from Percussion–Rotary Drilling Measurements - Guo-Hua Zhang; Jia-Cheng Yu; Zhao-Yang Han; Sheng-Lian Li; Lu-Zhao Dan; Dong-Jie Hua; Feng Xiong; Yu-Yong Jiao (Rock Mechanics and Rock Engineering, 2025)

Pilot Exploration of RGMa-BMP4 Signaling in Neutrophil Activation in NMOSD: Integrating Clinical and Molecular Insights - Weihe Zhang; Lei Cui; Yeqiong Zhang; Yang He; Xiaoxuan Li; Yu Wang; Jinsong Jiao; Dantao Peng; Ming Jin; Cheng Xiao (Molecular Neurobiology, 2025)

Impact of Proton Pump Inhibitors on Osimertinib-Induced Cardiotoxicity in NSCLC Patients - Haitao Wang; Sinan Ma; Weijia Huang; Keyu Chen; Jiao Xie; Na Wang; Youjia Li; Qianting Yang; Xin Yang; Yan Wang (Cardiovascular Toxicology, 2025)

Red-emitting aggregation-induced emission fluorescent probe for monitoring fluctuation of HClO in mitochondria during ferroptosis - Bin Yang; Wangbo Qu; Jiao Lu; Zhou Wu; Yong Li; Ruihong Yao; Jun Wang; Yanli Li; Zhihao Lu; Zhirong Geng; Zhilin Wang (Analytica Chimica Acta, 2025)

RSU1 Mediates Caco-2 Colorectal Cancer Cells Proliferation and Migration via PI3K/AKT Signaling Pathway - Yuanyuan Jiang; Jiao Li; Jishuang Qiu; Yanru Zhou; Yong Lai; Wanqi Yang (Cell Biochemistry and Biophysics, 2025)

Transcription factor FOXD3 participates in the immune response of Pinctada fucata martensii by regulating nAChR-5 - Min Yang; Yongge Huang; Xinyi Lin; Zhihan Li; Shilin Zheng; Youmei Qu; Yue Wen Deng; Ronglian Huang; Yu Jiao (Aquaculture, 2025)

Interfacial interactions of submicron plastics with carbon dots: Insights into the interface properties of microplastic weathering - Chao Liu; Yuan Jiao; Chunfan Yang; Bo Li; Wenjun Li; Tianwei Qian; Xiaona Liu (Water Research, 2025)

Molecular insights into dye decolorization performance and mechanisms under carbon limited conditions in a membrane aeration-based bioelectrochemical system - Tianyi Wang; Jiao Yin; Jiaxuan Yang; Boyan Xu; Weijia Gong; Zheng Ke; Longfeng Hu; Han Zhang; Guibai Li; Heng Liang; How Yong Ng (Water Research, 2025)

Undescribed alkaloids, peptides and polyketides from marine sediment-derived fungus Aspergillus terreus PPS1 - Yao-Yao Zheng; Guang-Shan Yao; Jiao-Jiao Li; Na Han; Jun-Qiu Mao; Ya-Hui Zhang; Ling Lv; Yang Liu; Chang-Yun Wang (Phytochemistry, 2025)

Biodegradable air filter with electrospun composite nanofibers and cellulose fibers dual network: Enhanced electrostatic adsorption, humidity resistance, and extended service life - Jingyi Nie; Binrong Sun; Tingting Jiao; Jianfei Liao; Meiyun Zhang; Ruiting Yang; Yueqing Li (Journal of Hazardous Materials, 2025)

Efficient capture and detoxification of gaseous arsenic trioxide from flue gas using silicomanganese alloy dust - Xin-Peng Ma; Guang Yang; Guan-Ming Qiao; Song-Yao Liu; Jiao-Jiao Xie; Yuan-Peng Li; Chun-Gang Yuan (Journal of Environmental Management, 2025)

Enhanced fermentative sugar yield and hydrogen production from tobacco waste via bio-surfactant assisted hydrothermal pretreatment - Zhiping Zhang; Yinggang Jiao; Guihong Yin; Junyu Tao; Jiazheng Wang; Quanguo Zhang; Zhen Wang; Xudong Yang; Hang Yan; Yameng Li (Journal of Environmental Chemical Engineering, 2025)

Preparation and characterization of Salecan β-glucan-based edible film loaded with lemon essential oil nanoemulsion: Effects on the preservation of chilled pork - Jiao Lin; Juan Dai; Qian Yang; Jiarui Li; Jing Xiao; Yuexin Zhang; YuKun Huang; Lijun Wang; Pengfei Chen; Buyi Xu; Juan Zhao; Xiao Yang; et al. (Food Chemistry, 2025)

Inhibitory effect and mechanism of lipopeptide Iturin A on food spoilage yeasts - Zhemin Li; Wencheng Jiao; Xiufang Bi; Xinyao Xie; Dan Shu; Di Luo; Jie Yang; Zhiying Yan; Hong Tan (Food Bioscience, 2025)

Utilization of hyaluronic acid to improve Mozzarella cheese: Composition, texture, microstructure, and pizza baking properties - Yufu Jiao; Lei Gao; You Kang; Yansong Gao; Yujuan Zhao; Zijian Zhao; Ge Yang; Shengyu Li (Food Hydrocolloids, 2025)

Directional thermal dehydration mediated strong anisotropic organization in covalent chitosan hydrogel - Qingye Liu; Md Nayeem Hasan Kashem; Zeqi Liu; Yinggui Wang; Celine R. Garcia; Jianhua Li; Noureddine Abidi; Wenlong Shi; Yang Jiao; Jiangyu Wu; Wei Li (Chemical Engineering Journal, 2025)

Long Non-Coding RNAs: Crucial Regulators in Alzheimer’s Disease Pathogenesis and Prospects for Precision Medicine - Chenbo Yang; Yiwei Li; Chao Chen; Zexin Sun; Enjie Liu; Na Wei; Xiaonan Liu; Jiao Shu; Na Zhao; Miaomiao Sun (Molecular Neurobiology, 2025)

Microvascular blood flow ultrasound imaging with microbubble-based H-Scan technology - Feng Jiang; Yiheng Li; Yaoyao Cui; Yang Jiao (Medical & Biological Engineering & Computing, 2025)
Ultrasound blood flow imaging plays a crucial role in the diagnosis of cardiovascular and cerebrovascular diseases. Conventional ultrafast ultrasound plane-wave imaging techniques have limited capabilities in microvascular imaging. To enhance the quality of blood flow imaging, this study proposes a microbubble-based H-Scan ultrasound imaging technique. This technique utilizes high-order H-Scan to detect the Rayleigh scattering contributed by blood flow and microbubbles at certain concentrations. The detected results are then processed in the B channel using methods such as clutter filtering based on Casorati matrix singular value decomposition (Casorati-SVD). Compared with the control group without H-Scan, the signal-to-noise ratio (SNR) of the experimental group using the microbubble-based H-Scan ultrasound imaging technique was increased by 38.61% on average and the contrast signal-to-noise ratio (CNR) was increased by 39.5% on average. The improved image quality of microvascular flow imaging was visibly enhanced. This method demonstrates significant advantages in enhancing the sensitivity and accuracy of ultrasound blood flow imaging, indicating considerable potential for clinical applications. Graphical abstract

Molecular and biological characterization of squash leaf curl China virus infecting Phaseolus vulgaris in China - Jiao Du; Shuhong Li; Xiaonan Yang; Subing Hao; Jinting Li; Rongrui Tian; Songtao Zhang; Pengbai Li (Journal of Plant Diseases and Protection, 2025)

Effects of different feeding strategies for the frozen Antarctic krill meal on growth, muscle nutrition, digestive enzyme activity, immunity, molting, and gut microbiota structure of Cherax quadricarinatus - Zhuang Mai; Jie Wei; Yakun Wang; Zhongqiang Zeng; Fubai Liu; Huarong Li; Qiyao Su; Kunhao Hong; Qiaoyan Zhou; Tianhui Jiao; Tianyan Yang; Lingyun Yu (Frontiers in Marine Science, 2025)
To investigate the effect of the frozen Antarctic krill meal (AKM) as an nutritional supplement in Cherax quadracarinatus culturing, an experiment was designed with the following groups: a control group (C) fed with basic feed throughout the experiment; Experimental Group 1 (E1) fed basic feed for 2 d and then compound feed (50% AKM + 50% basic feed) for 1 d; Experimental Group 2 (E2) fed basic feed for 1 d and then compound feed (50% AKM + 50% basic feed) for 1 d; Experimental Group 3 (E3) fed compound feed (50% AKM + 50% basic feed) daily. After 10 weeks of feeding, growth results revealed that both E1 and E2 groups exhibited significantly higher weight gain rate (WGR) and specific growth rate (SGR) compared to groups C and E3 (p < 0.05), with E2 achieving the highest survival rate (SR). Regarding muscle nutrition, the contents of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in C. quadracarinatus muscle showed a gradual increase with higher AKM feeding levels (p < 0.05), while the highest astaxanthin content was observed in group E2. Analysis of digestive enzyme activity and fluorescence quantification demonstrated that feeding AKM every other day (E2) not only enhanced the activities of trypsin and lipase in the hepatopancreas but also upregulated the expression levels of immune-related and molting-related genes (p < 0.05), whereas daily AKM feeding showed no significant improvements. Additionally, AKM feeding influenced the intestinal microbiota structure and abundance, with a notable increase in Bacteroidota phylum abundance in group E2.In conclusion, this study demonstrates that alternate-day AKM feeding (E2) optimizes growth performance, enhances muscle nutritional quality, improves digestive and immune capacities, and modifies intestinal microbiota composition in red claw crayfish. In contrast, daily AKM feeding, while elevating certain nutritional indices (e.g., EPA+DHA), exhibits limited benefits for overall growth performance and physiological function enhancement. Therefore, alternate-day AKM feeding is recommended as a superior strategy, providing scientific evidence for its application in C. quadracarinatus aquaculture.

Human-induced N-P imbalances will aggravate GHG emissions from lakes and reservoirs under persisting eutrophication - Wei Yu; Fali Liu; Xianglan Jiao; Pingping Fan; Haiquan Yang; Yongmei Zhang; Jie Li; Jingan Chen; Xuede Li (Water Research, 2025)

Aggregation behavior of photoaging nanoplastics in artificial sweat solutions - Yanlin Yang; Haoran Song; Yan Cao; Jiao Li; Jie Li; Xiangfen Cui; Xuewei Hu; Anjum Mahfuza; Ping Ning; Linfeng Zhang; Qun Zhao; Senlin Tian (Journal of Hazardous Materials, 2025)

The Physical Simulation Study on Impact Damage Characteristics of Deep Elliptical Roadway - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Yan Yang; Chaolong Qin; Xiaoli Nong; Ming Li (Rock Mechanics and Rock Engineering, 2025)

Carbon dioxide and methane fluxes in different waterbodies in Inexpressible Island, Ross Sea, East Antarctica - Zhiheng Du; Lei Wang; Simin Xie; Jiao Yang; Fangping Yan; Chuanjin Li; Minghu Ding; Yuzhu Zhang; Xi Ding; Cunde Xiao (Marine Pollution Bulletin, 2025)

Green β-cyclodextrin interlayered crumpled polyamide membranes for effective desalination - Jian Yu; Ling Zhang; Hongguang Sun; Renjie Li; Die Ling Zhao; Liguo Shen; Hongjun Lin; Yang Jiao; Yanchao Xu (Desalination, 2025)

Assembling halloysite nanotubes in nickel foam with silica fibers as scaffold for efficiently encapsulating phase change materials towards solar-thermal-electric energy conversion and management - Shuangqing Li; Xueke Jiao; Lili Chai; Zihan Su; Yushun Yang; Yafei Zhao; Yinze Yang; Dan Wang; Huishan Shang; Bing Zhang (Chemical Engineering Journal, 2025)

Hierarchical MXene@PBA@IL nanohybrids towards high-efficiently enhance fire safety of epoxy resin - Jirui Qu; Gaoyuan Li; Biyu Huang; Haopeng Zhang; Yuling Wang; Richeng Lian; Lei Liu; Lei Yang; Baojun Li; Xilei Chen; Chuanmei Jiao (Chemical Engineering Journal, 2025)

Efficient adsorption, encapsulation and stabilization of MgO in the remediation of low-concentration petroleum contaminated soil - Yin Wang; Jiao Zhao; Xiaojia Tang; Tie Li; Yang Liu; Yimin Zhu (Environmental Geochemistry and Health, 2025)

Development of RhB@CdMOF-based Fluorescent Sensor Array for Discrimination of BTEX - Zongning Guo; Shaohan Zeng; Hui Zhang; Xiaolin Zhang; Shouhui Wang; Jiwan Hu; Xuelin Huang; Li Yang; Zhe Jiao (Journal of Fluorescence, 2025)

Photoelectrocatalytic Coupling of Chlorine Radicals Enhances Sulfonamide Antibiotic Degradation in Saline-Alkaline Waters in Cold-Water Fish Aquaculture - Qikai Liu; Yang Liu; Yaqi Mao; Ru Li; Yujie Jiao; Jiali Lei; Fenzhen Zhang (Fishes, 2025)
The degradation of organic matter using TiO2 nanotube photocatalytic technology is limited by the short lifetime and diffusion radius of the generated hydroxyl radicals, decreasing the removal efficiency. This study developed a chlorine radical-coupled photoelectrocatalytic system, significantly enhancing the performance of TiO2 nanotube arrays in removing sulfonamide antibiotics (SAs) from cold-water aquaculture systems. The highest degradation rates were observed at 5 mM NaCl and 15 mM NaNO3. When SA concentrations were 0.1–10 mg/L, degradation efficiency decreased with higher initial concentrations. The best degradation was achieved at an initial pH of 3 for SA. Humic acid and sodium acetate, natural organic matter in the water column, served as low-concentration promoters and high-concentration inhibitors. In our study, three degradation intermediates were identified, and hydrolysis and nitration reactions are proposed as the primary pathways for SA degradation. We confirmed that oxygen radicals play a major role in this system. Furthermore, toxicology experiments revealed the weakening of the toxicity of the degraded products. This study provides an efficient method for treating organic matter in cold-water fish culture water in chloride-containing saline and alkaline waters.

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Metabolic mechanism, responses, and functions of genes HDH1, HDH3, and GST1 of tea (Camellia sinensis L.) to the insecticide thiamethoxam - Ping Zhang; Tianyuan Yang; Yunlong Xie; Yulong Liu; Qing X. Li; Xiangwei Wu; Rimao Hua; Weiting Jiao (Journal of Hazardous Materials, 2025)

Modulating the spatial locations of bimetallic sites in KL zeolite via atomic layer deposition for improved n-heptane aromatization - Dan Xu; Li Wei; Yang Jiao; Zhuoya Bao; Angang Song; Guofu Liu; Jianmei Wang; Arthur Ernest Dr.Koschany; Peng Zhang; Laizhi Sun; Mingxing Tang; Tao Li; et al. (Fuel, 2025)

NF-κB inhibitor PDTC involved in regulating the transplantation immunity in the pearl oyster Pinctada fucata martensii - Shirong Fu; Xinyi Lin; Xiaowen Lu; Youmei Qu; Hongxi Chen; Shilin Zheng; Zhihan Li; Yu Jiao; Qingheng Wang; Chuangye Yang; Yuewen Deng (Fish & Shellfish Immunology, 2025)

Room temperature synthesis of one-dimensional hierarchical hollow BiOBr with tunable photocatalysis reaction pathway for RhB under visible light - Niya Yang; Ruixing Li; Yajuan Xu; Min He; Daiwei Li; Suisui Su; Jiao zhang; Cuiqing Zhang; Jia Dong; Siqi Ying; Shizheng Zheng; Changyuan Hu (Environmental Research, 2025)

Microwave-responsive nanoencapsulated fluorescence thermometers for quantitative assessment of microscale localized heat regulation in chemical production - Kai Liu; Na Wang; Zongliang Kou; Xiaxin Jiao; Suguang Yang; Minghui Lyu; Hong Li; Zhenyu Zhao; Xin Gao (Chemical Engineering Journal, 2025)

An innovative approach to evaluate debris flow scale-activity across diverse aridity zones: Fusion of image recognition and geomorphometric analysis - Zhenni Jiang; Jiao Wang; Guotao Zhang; Peng Cui; Can Yang; Yifan Zhang; Bo Zhang; Chaoyue Li; Hao Wang; Jie Liu; Zhiwei Yang (CATENA, 2025)

CERK1-mediated phosphorylation of PBL19 is crucial for antifungal defense in plants - Yujia Li; Xiangjuan Huang; Ben-Qiang Gong; Yang Yu; Jian-Feng Li; Jiao Xue (Planta, 2025)

Nutrient Availability Shapes the Resistance of Soil Bacterial Community and Functions to Disturbances in Desert Ecosystem - Hang Gao; Yuan Song; Mingyu Li; Min Gao; Ziheng Peng; Haibo Pan; Jiejun Qi; Shi Chen; Yu Liu; Yang Wang; Chujie Jin; Gehong Wei; et al. (Environmental Microbiology, 2025)
Climate change has exposed desert ecosystems to frequent extreme disturbances, including wet‐dry cycles and freeze–thaw events, which accelerate desertification on a global scale. The limited nutrient availability characteristic of these ecosystems may constrain microbial survival and growth, making them more vulnerable to environmental perturbations and stressors. However, how nutrient availability modulates the stability of soil ecological communities and functions in desert ecosystems remains poorly understood. In this study, we examined how nutrient addition, applied either before or after disturbances, affects the resistance of bacterial communities and multifunctionality to drought and freeze events in desert ecosystems. Our findings revealed that freeze–thaw events, rather than drought, significantly reduced bacterial diversity, with all disturbances altering the community structure. Pre‐disturbance nutrient addition notably improved the resistance of soil bacterial diversity and community composition to disturbances, which played a critical role in maintaining multifunctionality in desert ecosystems. This enhanced bacterial resistance was strongly associated with increased bacterial network complexity and the enrichment of disturbance‐tolerant taxa. Our results highlight the pivotal role of nutrient availability in stabilising soil bacterial communities and multifunctionality under extreme climatic conditions in desert ecosystems. These findings offer valuable insights and practical strategies for the ecological protection and management of desertification.

Mixed volcanic and hydrothermal origin of siliceous rocks in a volcanic lake in the Santanghu Basin, NW China - M. Zhao; Y. Liu; X. Jiao; D. Zhou; Z. Meng; Z. Li; Y. Yang (Australian Journal of Earth Sciences, 2025)

Sequential decline in cyanobacterial, total prokaryotic, and eukaryotic responses to backward flow in a river connected to Lake Taihu - Jun Zuo; Siyu Yang; Hans-Peter Grossart; Peng Xiao; He Zhang; Rui Sun; Guoyou Li; Haoran Jiang; Qihang Zhao; Meng Jiao; Yao Cheng; Zeshuang Wang; et al. (Water Research, 2025)

Toxicity assessment of wastewater using a battery of bioassays in two textile wastewater treatment plants from a large industrial park in Guangxi, Southwest China - Feng-Jiao Peng; Sen Li; Wen-Dan You; Xin-Yu Wang; Xing-Jun Feng; Bin Yang; Guang-Guo Ying (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

The secrets to high-level green technology innovation of China's waste power battery recycling enterprises - Jianling Jiao; Yuqin Chen; Jingjing Li; Shanlin Yang (Journal of Environmental Management, 2025)

Nanoplastics facilitate the spread of antibiotic resistance genes in chemically induced competent bacteria: The hydrogen peroxide plays as the main signal factor - Chenxi Li; Qian Zhang; Linjie Wang; Zhe Piao; Ya Zhang; Yang Chong; Xin’an Jiao; Honggui Wang (Journal of Environmental Chemical Engineering, 2025)

Construction of carbon nanotube-multifunctional porous ionic polymer core–shell nanocomposite for efficient conversion of carbon dioxide under co-catalyst free conditions - Yingjun Li; Wenye Zha; Jiao Zhang; Weifeng Chen; Qiming Yang; Shenglai Zhong; Yi-Zhu Lei (Fuel, 2025)

Prevention and control strategies for psychrophilic Pseudomonas fluorescens in food: A review - Ting Ding; Hongwei Zhan; Yanqing Li; Guanyuan Qu; Lixiu Zhang; Jiao Li; Wenming Ju; Yongjun Sun; Yang Deng (Food Research International, 2025)

Dual-functional improvement of vascularization and bone formation of complementary PRP-based gel scaffold - Han Zhang; Zhonghan Wang; Yang Wang; He Liu; Mufeng Li; Bo Chao; Shixian Liu; Jianhang Jiao; Minfei Wu (Chemical Engineering Journal, 2025)

Decoding the intracellular trafficking rule for circular RNAs - Jiao Li; Xiaojuan Yang; Yong Peng (Science China Life Sciences, 2025)

Parafrigoribacterium soli sp. nov. and Parafrigoribacterium humi sp. nov., two novel siderophore-synthesizing species isolated from black soil - Yu-Ting OuYang; Le-Bin Chen; Jian-Yu Jiao; Zi-Xuan Hu; Jiong-Shan Wang; Tian-Hang Yang; Jun Xiao; Ting-Ting She; Pin-Jiao Jin; Shuang Wang; Lan Liu; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Duplicate MADS-box genes with split roles and a genetic regulatory network of floral development in long-homostyle common buckwheat - Xinyu Jiao; Yamin Li; Qingyu Yang; Xiangjian Chen; Lan Luo; Yuzhen Liu; Zhixiong Liu (Plant Science, 2025)

Gut microbiota combined with metabolome dissects Fluorene-9-bisphenol exposure-induced male reproductive toxicity - Danni Jiang; Yang Yang; Xiaojuan Han; Qianni Li; Jun Jiao; Yingxiu Ma; Lan Chao (Environmental Pollution, 2025)

Flexible and large-area electrochromic infrared devices with superior modulation functionality - Zongtao Zhang; Yifei Liu; Ke Jiao; Yunxiang Chen; Jing Tong; Jin Li; Miaoran Xu; Chao Xue; José V. Anguita; Jing Zhang; Kai Yang; Wei Zhang; et al. (Chemical Engineering Journal, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

Engineering N-donor heterocycles on dioxin-linked covalent organic frameworks to in situ improvement uranium separation and extraction selectivity in wastewater and seawater - Ruihong Yao; Jun Wang; Yanli Li; Wangbo Qu; Bin Yang; Jiao Lu; Zhou Wu; Yong Li; Zhihao Lu; Zhirong Geng; Zhilin Wang (Chemical Engineering Journal, 2025)

Highly sensitivity and wide-range flexible humidity sensor based on LiCl/cellulose nanofiber membrane by one-step electrospinning - Xiaomeng Liu; Lang Wang; Ying Lei; Xiao Li; Chunzu Cheng; Leixin Yang; Long Jiao; Shuo Yang; Dengkun Shu; Bowen Cheng (Chemical Engineering Journal, 2025)

Weather pattern classification of regional extreme precipitation events and their formation mechanisms in the Yangtze-Huai Region, China - Yuqing Jiang; Yixing Yin; Wentian Li; Shibao Dai; Xiaojun Long; Yang Jiao (Climate Dynamics, 2025)

Synthesis of phosphonitrile derivative-modified halloysite flame retardants and their simultaneous enhancement of epoxy resins flame retardancy and mechanical properties - Chunhui Meng; Yunhong Jiao; Weihong Wu; Quan Li; Yuying Yang; Hongqiang Qu (Applied Clay Science, 2025)

Peanut–cotton intercropping to enhance soil ecosystem multifunctionality: Roles of microbial keystone taxa, assembly processes, and C-cycling profiles - Shijie Zhang; Yingchun Han; Guoping Wang; Lu Feng; Yaping Lei; Shiwu Xiong; Beifang Yang; Xiaoyu Zhi; Minghua Xin; Yahui Jiao; Xiao-Fei Li; Yabing Li; et al. (Agriculture, Ecosystems & Environment, 2025)

Effects of microplastics pollution in sediments on physicochemical properties and microbial community distribution in coastal Spartina alterniflora-invaded wetlands - Guo Li; Jiao Ran; Jing Dong; Kai Yang; Jingru Hu; Jing Shi; Yumiao Zhang; Jiabin Chen; Yu Zhao; Ensheng Zhu; Suzhen Huang; Zheng Zheng (Frontiers in Marine Science, 2024)
Introduction Coastal wetlands play an important role in the global ecosystem, yet they are increasingly facing ecological degradation due to pollution and the spread of invasive Spartina alterniflora (S. alterniflora) . Among the environmental challenges, microplastics (MPs) contamination in S. alterniflora -invaded coastal wetlands is of growing concern. However, the effects of MPs pollution in S. alterniflora -invaded coastal wetlands are not clear. Methods This study investigated the effects of S. altemiflora invasion on the distribution of MPs and the effects of MPs pollution on the physicochemical properties of sediments and the structure of microbial communities in the Tiaozini wetland of Jiangsu Province, China. Results and discussion The total MPs abundance of the S. altemiflora single-plant area was the highest (16.338 x10 3 items/kg d.w.). Polyurethane and Chlorinated polyisoprene are typical MPs types in the study area. Polyurethane exhibits high abundance at all sampling sites, while Chlorinated polyisoprene is one of the dominant MPs types in the single-plant and sub-mature area of S. alterniflora . The results showed that the invasion of S. alterniflora promoted the accumulation of MPs in the sediments of the coastal wetland. This accumulation increased the total organic carbon (TOC), available phosphorus (AP) and total nitrogen (TN) contents. Moreover, MPs pollution increased the ALP and SUC enzyme activities of sediment. In addition, MPs contamination increased the abundance of Proteobacteria and Bacteroidota in the sediments. This study highlights the complex interactions between MPs pollution and S. alterniflora invasion, providing the foundation for understanding the synergistic impacts of these stressors on coastal wetland ecosystems.

Path planning of greenhouse electric crawler tractor based on the improved A* and DWA algorithms - Huiping Guo; Yi Li; Hao Wang; Chensi Wang; Jiao Zhang; Tingwei Wang; Linrui Rong; Haoyu Wang; Zihao Wang; Yaobin Huo; Shaomeng Guo; Fuzeng Yang (Computers and Electronics in Agriculture, 2024)

EVIT-YOLOv8: Construction and research on African Swine Fever facial expression recognition - Lili Nie; Bugao Li; Fan Jiao; Wenjuan Lu; Xinlong Shi; Xinyue Song; Zeya Shi; Tingting Yang; Yihan Du; Zhenyu Liu (Computers and Electronics in Agriculture, 2024)

Mitigating harmful cyanobacterial blooms in drinking water reservoirs through in-situ sediment resuspension - Jiao Fang; Yande Li; Ming Su; Tengxin Cao; Xufeng Sun; Yufan Ai; Jinyi Qin; Jianwei Yu; Min Yang (Water Research, 2024)

Type I-E CRISPR-Cas system regulates fimZY and T3SS1 genes expression in Salmonella enterica serovar Pullorum - Kai Zhang; Pengyu Wang; Shanshan Li; Xiaolei Xie; Zhenyu Wang; Yang Li; Xinan Jiao; Qiuchun Li (Veterinary Microbiology, 2024)

Sequential oxidation procedures with KMnO4: Component characteristics of labile reducing capacity fractions in anaerobic sediments - Xuemei Chen; Zhijun Li; Songjie Fu; Lanwei Liang; Xiaohan Liu; Fang Hu; Wen Zhang; Yonghong Bi; Yang Jiao; Sen Gu; Qingman Li (Science of The Total Environment, 2024)

Tailpipe emissions and fuel consumption of a heavy-duty diesel vehicle using palm oil biodiesel blended fuels - Liqiang He; Yang Li; Yihang Min; Junhao Yoong; Shiqing Chen; Jiwen Jiao; Zhenhua Li; Luole Zhu; Shaojun Zhang; Ye Wu (Science of The Total Environment, 2024)

How has the latest IMERG V07 improved the precipitation estimates and hydrologic utility over CONUS against IMERG V06? - Siyu Zhu; Zhi Li; Mengye Chen; Yixin Wen; Shang Gao; Jiaqi Zhang; Jiao Wang; Yi Nan; Sebastian C. Ferraro; Theresa E. Tsoodle; Yang Hong (Journal of Hydrology, 2024)

Investigating the relationship of co-exposure to multiple metals with chronic kidney disease: An integrated perspective from epidemiology and adverse outcome pathways - Yican Wang; Mengyun Qiao; Haitao Yang; Yuanyuan Chen; Bo Jiao; Shuai Liu; Airu Duan; Siyu Wu; Haihua Wang; Changyan Yu; Xiao Chen; Huawei Duan; et al. (Journal of Hazardous Materials, 2024)

Interaction of diesel exhaust particulate matter with mucins in simulated saliva fluids: Bioaccessibility of heavy metals and potential health risks - Jiao Li; Haorang Song; Linfeng Zhang; Jie Li; Yanlin Yang; Xiangfen Cui; Anjum Mahfuza; Yan Cao; Xuewei Hu; Chen Li; Qun Zhao; Senlin Tian (Journal of Hazardous Materials, 2024)

Corrigendum to “Innovative approach for assessing nitrogen loss risk to surface waters from crop production in a watershed scale through nitrogen surplus index method” [J. Clean. Product. 475 (2024) 143725] - Ziwei Yang; Cong Zhu; Haixuan Zhao; Gaofei Yin; Yueying Wei; Wenqi Ma; Huiqing Jiao; Jiafa Luo; Bin Xi; Hongda Wen; Shufang Guo; Wenchao Li; et al. (Journal of Cleaner Production, 2024)

Insights into flavor quality and metabolites profiles of fresh cheese with different probiotics by SPME-GC-MS and untargeted metabolomics - Qian Ma; Lu Liu; Yang Jiao; Xiangyu Qiao; Renjiao Han; Xiaodong Li; Caiyun Wang; Xiuxiu Zhang; Kouadio Jean Eric-Parfait Kouame (Food Research International, 2024)

Rapid and sensitive detection of haloxyfop-P-methyl by competitive and noncompetitive immunoassays using phage-displayed peptides - Jiao Li; Panpan Cui; Zhijia Wang; Yang Lu; Yuan Ding; Xiude Hua (Food Bioscience, 2024)

Insights into carbon-neutral treatment of rural wastewater by constructed wetlands: A review of current development and future direction - Feifei Jiao; Xinzheng Zhang; Tao Zhang; Yong Hu; Rui Lu; Guangyi Ma; Tao Chen; Hongbo Guo; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Environmental Research, 2024)

Enhancing removal performance of ortho xylene by adding polydimethylsiloxane into two-stage biofilter - Shu Wang; Yuxi Yan; Jing Zhang; Jiao Yang; Fengguang Chai; Shunyi Li (Bioresource Technology, 2024)

The role of quercetin in ameliorating bleomycin-induced pulmonary fibrosis: insights into autophagy and the SIRT1/AMPK signaling pathway - Zhipeng Li; Yang Jiao; Zhisong Wu; Haoge Liu; Yang Li; Yaodong Cai; Wan Wei; Fang Cao (Molecular Biology Reports, 2024)

Functional analysis of a rice 12-oxo-phytodienoic acid reductase gene (OsOPR1) involved in Cd stress tolerance - Longying Wu; Ruolin Wang; Mingyu Li; Zhiye Du; Yufan Jin; Yang Shi; Wenjun Jiang; Ji Chen; Yuan Jiao; Binhua Hu; Jin Huang (Molecular Biology Reports, 2024)

Drug-Resistant Epilepsy and Gut-Brain Axis: an Overview of a New Strategy for Treatment - Shuna Chen; Yang Jiao; Chao Han; Ying Li; Wei Zou; Jing Liu (Molecular Neurobiology, 2024)

Exogenous Application of Chitosan Mitigates the Inhibitory Effects of Zinc on the Growth of Wheat Seedlings by Modulating Zn Transport and ROS Scavenging - Lina Fan; Jingjing Zhang; Zhengyang Xu; Qiujuan Jiao; Zihao Song; Peiyi Yu; Deyuan Liu; Gezi Li; Shah Fahad; Zulfiqar Ali Sahito; Mohammed Ali Alshehri; Salah F. Abou-Elwafa; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Development mechanisms of cyclonic vorticity under two distinct large-scale weather patterns associated with summer heavy rainfall over North China - Jiao Li; Ping Zhao; Deliang Chen; Yang Zhao; Zhiping Wen; Chao Zhang (Climate Dynamics, 2024)

Phylogenomic analyses and comparative genomic studies of Thermus strains isolated from Tengchong and Tibet Hot Springs, China - Inam Ullah Khan; Muhammad Saqib; Arshia Amin; Sadia Manzoor; Iftikhar Ahmed; Rui-Rui Liu; Jian-Yu Jiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Dehydration–rehydration mechanism of vegetables at the cell-wall and cell-membrane levels and future research challenges - Bixiang Wang; Yue Li; Yingchi Lv; Xuan Jiao; Zhitong Wang; Yang He; Liankui Wen (Critical Reviews in Food Science and Nutrition, 2024)

In-field grading and sorting technology of apples: A state-of-the-art review - Jiangfan Yu; Zhao Zhang; Yifei Li; Wanjia Hua; Xinyu Wei; C. Igathinathane; Mustafa Mhamed; Wenqiang Zhang; Xiaoqiang Jiao; Liling Yang; Man Zhang; Han Li (Computers and Electronics in Agriculture, 2024)

Exploring spatial heterogeneity of e-scooter’s relationship with ridesourcing using explainable machine learning - Junfeng Jiao; Yiming Xu; Yang Li (Transportation Research Part D: Transport and Environment, 2024)

Evaluating approach uncertainties of quantitative detection of SARS-CoV-2 in wastewater: Concentration, extraction and amplification - Shaolin Yang; Yang Jiao; Qian Dong; Siqi Li; Chenyang Xu; Yanchen Liu; Lingli Sun; Xia Huang (Science of The Total Environment, 2024)

Miscanthus sp. root exudate alters rhizosphere microbial community to drive soil aggregation for heavy metal immobilization - Bohan Wu; Xiao Li; Shukun Lin; Ruifang Jiao; Xu Yang; Aoao Shi; Xinxing Nie; Qingqi Lin; Rongliang Qiu (Science of The Total Environment, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Formation temperature of microcrystalline dolomite in oil-rich black shale: Implications for hydrocarbon accumulation in a volcanic-lacustrine rift basin - Xin Jiao; Wan Yang; Yiqun Liu; Hong Li; Shilin Wei (Marine and Petroleum Geology, 2024)

Different preferences for inorganic carbon influence CO2 flux under Cyanobacteria or Chlorophyta dominance days - Kai-Kai Deng; Yi-Xuan Li; Peng Yan; Yuan-Chen Huo; Hao Yang; Bin Chen; Qiang He; Gui-Jiao Lin; Jin-Song Guo (Journal of Environmental Management, 2024)

Specialists regulate microbial network and community assembly in subtropical seagrass sediments under differing land use conditions - Weiguo Zhou; Xiaomei Shen; Zhimeng Xu; Qingsong Yang; Mengyu Jiao; Hanying Li; Li Zhang; Juan Ling; Hongbin Liu; Junde Dong; Anning Suo (Journal of Environmental Management, 2024)

Reducing defects in hard carbon graphite domain: Employing a fully dynamic bonding with a multi-crosslinked biomass-based binder for enhanced sodium ion storage - Jiaqi Jiao; Han Lu; Conghua Yi; Dongjie Yang; Xuezhi Zeng; Jinxin Lin; Hongqiang Li (Chemical Engineering Journal, 2024)

A multi-layer antimicrobial cellulose filter with electrostatic adsorption properties prepared by coating cellulose with chitosan and CuO - Jingyi Nie; Jianfei Liao; Tintin Jiao; Binron Sun; Meiyun Zhang; Ruiting Yang; Yueqing Li (Chemical Engineering Journal, 2024)

Nondestructive electrochemical capacity restoration of LiNi1/3Co1/3Mn1/3O2 cathode for lithium batteries - Chenyu Bai; Yiding Jiao; Wei Mao; Fangyan Li; Shuo Yang; Jie Song; Yiran Li; Luhe Li; Yu Deng; Peng Wang; Ye Zhang (Chemical Engineering Journal, 2024)

Magnitude and hotspots of soil erosion types during heavy rainstorm events on the Loess Plateau: Implications for watershed management - Bo Yang; Xiaowu Ma; Juying Jiao; Wenting Zhao; Qi Ling; Jianjun Li; Xinhan Zhang (CATENA, 2024)

Investigation of γ-polyglutamic acid production via asynchronous saccharification and fermentation of raw corn starch - Yutao Gou; Chenxin Niu; Fanglan Ge; Wei Li; Guiying Cheng; Shuai Jing; Hong Yang; Jiao Li; Yao Ren (World Journal of Microbiology and Biotechnology, 2024)

Perilla frutescens repels and controls Bemisia tabaci MED with its key volatile linalool and caryophyllene - Liming Gao; Yan Wei; Kailong Li; Jianbin Chen; Pei Wang; Jiao Du; Jing Peng; Yang Gao; Zhanhong Zhang; Yong Liu; Xiaobin Shi; Deyong Zhang (Crop Protection, 2024)

Trimethylamine N-oxide induces non-alcoholic fatty liver disease by activating the PERK - Bingmo Yang; Guomin Tang; Mengting Wang; Yifan Ni; Jiali Tong; Chunyan Hu; Ming Zhou; Kailin Jiao; Zhong Li (Toxicology Letters, 2024)

A robust triphenylamine-based monolithic polymer network for selective sieving of CO2 and PM from flue gas - Yang Lei; Shaozhen Wang; Yanli Jiang; Zhen Li; Nana Liu; Yuan Xu; Jiao Yu; Mengjiao Cui; Yang Li; Li Zhao (Science of The Total Environment, 2024)

Sediment water content drives movement of intertidal crab Helice tientsinensis more strongly than salinity variations - Xiaoxiao Li; Wei Yang; Le Jiao; Tao Sun; Zhifeng Yang (Marine Environmental Research, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Innovative approach for assessing nitrogen loss risk to surface waters from crop production in a watershed scale through nitrogen surplus index method - Ziwei Yang; Cong Zhu; Haixuan Zhao; Gaofei Yin; Yueying Wei; Wenqi Ma; Huiqing Jiao; Jia Luo; Bin Xi; Hongda Wen; Shufang Guo; Wenchao Li; et al. (Journal of Cleaner Production, 2024)

Paleomagnetic constraints on the link between the Comei-Bunbury large igneous province and the Kerguelen mantle plume - Weiwei Bian; Tianshui Yang; Jin Deng; Yiming Ma; Wenxiao Peng; Suo Wang; Xianwei Jiao; Jiahui Ma; Jiacheng Liang; Jingjie Jin; Haiyan Li; Huaichun Wu; et al. (Gondwana Research, 2024)

Three-dimensional mass transfer modeling and phenolic chemistry exploration for ultrasound-assisted and microwave drying of goji berry - Rui Zhu; Xiaoxuan Ma; Dandan Li; Yongbin Han; Sivakumar Manickam; Yang Jiao; Erico Marlon Moraes Flores; Yang Tao (Food Research International, 2024)

Colorimetric-SERS dual-mode aptasensor for Staphylococcus aureus based on MnO2@AuNPs oxidase-like activity - Jiahe Dai; Jitao Li; Yang Jiao; Xiaolan Yang; Dezhi Yang; Zitao Zhong; Hong Li; Yaling Yang (Food Chemistry, 2024)

Advancements and future perspectives in the study of oligosaccharides derived from edible-medicinal mushrooms - Shuo Wang; Jiajie Qi; Xiaoming Cai; Weijie Wu; Zhuo A. Wang; Siming Jiao; Caihong Dong; Yi Li; Zhenquan Yang (Food Bioscience, 2024)

Strong interaction heterointerface of NiFe oxyhydroxide/cerium oxide for efficient and stable water oxidation - Han Jiao; Chun Wang; Hao Tian; Zi-Yang Zhang; Yang Zhao; Ping Na; Yusuke Yamauchi; Zhong-Li Wang (Chemical Engineering Journal, 2024)

A novel pH-responsive multi-component nanodelivery system with siRNA for plant disease management - Chengying Ding; Yubing Jiao; Ying Li; Lili Shen; Wanhong Zhang; Haohua Ma; Lu Han; Zongjin Zhang; Fangfang Yan; Yunpeng Mei; Robert YL Wang; Jinguang Yang (Chemical Engineering Journal, 2024)

Sensitive dual-channel lateral flow immunoassay tagged with high brightness latex microsphere for simultaneous detection of respiratory viral antigens - Tao Dong; Guangze Sun; Zhonghuang Yang; Yiming Jiao; Jinze Li; Ziting Lin; Xin Zhang; Zihan Bian; Aihua Liu (Chemical Engineering Journal, 2024)

Influence of scion cultivar on the rhizosphere microbiome and root exudates of Phaseolus vulgaris in grafting system - Xiuli Wei; Yuanyuan Cui; Jiaqi Wang; Guoyuan Song; Ying Cao; Long Liu; Zhixin Liu; Jing Yang; Chen Li; Jiao Wang; Moran Li; Xiao Xiao (Plant and Soil, 2024)

Real-world safety and effectiveness of pirfenidone and nintedanib in the treatment of idiopathic pulmonary fibrosis: a systematic review and meta-analysis - Mengjia Kou; Yang Jiao; Zhipeng Li; Bin Wei; Yang Li; Yaodong Cai; Wan Wei (European Journal of Clinical Pharmacology, 2024)

Gas isotope geochemistry of Tangquan hot spring system in Nanjing (China) - Yifan Bao; Zhonghe Pang; Yiman Li; Jiao Tian; Ji Luo; Yifan Fan; Fengtian Yang; Tingqing Qian; Fei Chen; Caixia Sun; Zongying Zhou (Applied Geochemistry, 2024)

Linking soil nutrients, microbial community composition, and enzyme activities to saponin content of Paris polyphylla after addition of biochar and organic fertiliser - Shouzan Liu; Ye Chen; Xin Li; Junyan Lv; Xing Yang; Jiao Li; Yan Bai; Shaobo Zhang (Chemosphere, 2024)

Photochemical transformation of liquid crystal monomers in simulated environmental media: Kinetics, mechanism, toxicity variation and QSAR modeling - Yandong Yang; Xiangkun Jiang; Yi Yang; Jia Wang; Yahui Zhao; Shanshan Lin; Jiao Qu; Christopher J. Martyniuk; Yuanhui Zhao; Chao Li (Water Research, 2024)

Structurally diverse diterpenoids from the seeds of Caesalpinia minax Hance and their bioactivities - Wen-Chao Tu; Lin-Fen Ding; Liu-Dong Song; Yong-Jiao Li; Run-Cheng Yan; Yun Wu; Wei-Yang Feng; Xing-De Wu (Phytochemistry, 2024)

Urinary concentrations of mineral elements and their predictors in pregnant women in Jinan, China - Xiaohui Guo; Jiayi Song; Xiang Wang; Qichen Huang; Chuanling Wei; Yujie Yang; Nan Li; Shuang Cheng; Jiao Li; Qi Li; Ju Wang (Journal of Trace Elements in Medicine and Biology, 2024)

Straw removal reduces Cd availability and rice Cd accumulation in Cd-contaminated paddy soil: Cd fraction, soil microorganism structure and porewater DOC and Cd - Hang Zhou; Zi-Yu Wang; Chang Li; Hai-Wei Yuan; Lu Hu; Peng Zeng; Wen-Tao Yang; Bo-Han Liao; Jiao-Feng Gu (Journal of Hazardous Materials, 2024)

Adsorptive removal of aflatoxin B1 via spore protein from Aspergillus luchuensis YZ-1 - Xiyan Zhang; Rui Jiao; Yuwei Ren; Yang Wang; Hui Li; Dexin Ou; Na Ling; Yingwang Ye (Journal of Hazardous Materials, 2024)

The coordinated development among economy, society, energy, and environment and their impacts on public health in China's cities - Cheng Zhang; Meiyu Jiang; Fujie Yang; Yuehan Wang; Yaxin Xu; Sihan Lin; Li Li; Yalin Lei; Sanmang Wu; Jiao Wang (Journal of Cleaner Production, 2024)

Influence of mountain orientation on precipitation isotopes in the westerly belt of Eurasia - Longhu Chen; Guofeng Zhu; Qin Qin Wang; Linlin Ye; Xinrui Lin; Siyu Lu; Yinying Jiao; Rui Li; Gaojia Meng; Yuhao Wang; Jiangwei Yang; Chen Jia (Global and Planetary Change, 2024)

Two-stage exhumation, uplift, and basinward propagation of the Tian Shan during the late Cenozoic - Yutong Jiang; Honghua Lu; Rong Yang; Lichen Pang; Ruohong Jiao; Ying Wang; Jianzhang Pang; Youli Li (Earth-Science Reviews, 2024)

Preparation and design of intelligent multi-response PTMC/PVP composite nanofibrous dressing to promote wound closure and its applications in diabetic wounds - Liping Liu; Tao Yang; Shaoru Wang; Wenyuan Jia; Yun Liu; Kun Jiao; Yongzheng Yan; Yuheng Yang; Xuanzuo Jiang; Chiyu Li; Zhiqiang Cheng; Guomin Liu; et al. (Chemical Engineering Journal, 2024)

A Perspective on Evaluating Life Stage Differences in Drug Dosages for Drug Labeling and Instructions - Tianshu Gu; Guiying Wang; Edwin J. C. van den Oord; Emanuel Goldman; Chengyuan Yang; Ning Xie; Lan Yao; Cong-Yi Wang; Monica Jablonski; Kunal Ray; Fengxia Liu; Wensen Pan; et al. (The AAPS Journal, 2024)

Recent advances in hydrogen process safety: Deflagration behaviors and explosion mitigation strategies - Peng Yang; Tao Wang; Yuhuai Sheng; Yingying Yu; Ruikang Li; Bin Su; Fangming Cheng; Jiao Qu; Jun Deng; Zhenmin Luo (Process Safety and Environmental Protection, 2024)

Application of natural-products repurposing strategy to discover novel FtsZ inhibitors: Bactericidal evaluation and the structure-activity relationship of sanguinarine and its analogs - Jiao Meng; Mei Li; Zhicheng Zheng; Zhaoju Sun; Song Yang; Guiping Ouyang; Zhenchao Wang; Xiang Zhou (Pesticide Biochemistry and Physiology, 2024)

Long-range infrared absorption spectroscopy and fast mass spectrometry for rapid online measurements of volatile organic compounds from black tea fermentation - Chongshan Yang; Leizi Jiao; Chunwang Dong; Xuelin Wen; Peng Lin; Dandan Duan; Guanglin Li; Chunjiang Zhao; Xinglan Fu; Daming Dong (Food Chemistry, 2024)

Electrocatalytic nitrogen reduction to ammonia at low overpotentials based on tungsten carbide doped by non-precious metal single cobalt atoms - Ya Gao; Meng-Jiao Zhu; Xian-He Liu; Guo-Liang Dai; Yi-Wen Zhou; Ze-Da Meng; Li Luo; Tian Gan; Feng Chen; Yu-Yang Zhou; Wen-Wen Deng; Shou-Qing Liu (Chemical Engineering Journal, 2024)

LncRNA CCRR maintains Ca2+ homeostasis against myocardial infarction through the FTO-SERCA2a pathway - Hua Yang; Lina Xuan; Shengjie Wang; Huishan Luo; Xiaomeng Duan; Jianjun Guo; Shijia Cui; Jieru Xin; Junwei Hao; Xiufang Li; Jun Chen; Feihan Sun; et al. (Science China Life Sciences, 2024)

PEG300 Protects Mitochondrial Function By Upregulating PGC-1α to Delay Central Nervous System Oxygen Toxicity in Mice - Xin Li; Yue Shen; Dan Li; Kun Zhang; Jia Liu; Lu Yao; Jun Yang; Jiao Qian (Neurotoxicity Research, 2024)

Urolithin A exerts a protective effect on lipopolysaccharide-induced acute lung injury by regulating HMGB1-mediated MAPK and NF-κB signaling pathways - Pengfei Jiao; Yingrui Wang; Gaofei Ren; Dan Chu; Yameng Li; Yingwu Yang; Tianqing Sang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

A method for predicting methane production from anaerobic digestion of kitchen waste under small sample conditions - Shipin Yang; Yuqiao Cai; Tingting Zhao; Xue Mei; Wenhua Jiao; Lijuan Li; Hao Fang (Environmental Science and Pollution Research, 2024)

Real biofuel and fossil-fuel soot combustion activities in active and passive regeneration of diesel/gasoline particulate filters under different O2/NOx concentrations - Yetong Gai; Peng Yao; Shanshan Li; Hailong Zhang; Yang Wu; Yi Jiao; Yaoqiang Chen; Jianli Wang (Environmental Science and Pollution Research, 2024)

Rapid detection of multiple phytoplasmas with an All-In-One Dual (AIOD) CRISPR assay - Qicheng Li; Sicheng Guo; Jidong Li; Jian Jiao; Qiqi Yang; Jia Yao; Yun Chen; Xia Ye; Jun Cheng; Bin Tan; Xianbo Zheng; Yingxia Wu; et al. (Crop Protection, 2024)

Pterophyllum fossils from the Middle Jurassic Yaojie Formation, Gansu Province and its paleogeographical significance in China - Zhipeng Jiao; Cunlin Xin; Dong Yang; Yamei Zhang; Bo Zhang; Ning Chen; Yuan Bai; Lanxing Wei; Fangfang Zhang; Hong Li (Review of Palaeobotany and Palynology, 2024)

Correlations between bone metabolism biomarkers and fluoride exposure in adults and children - Shuo Yang; Shuiyuan Yu; Yuhui Du; Zichen Feng; Xuecheng Jiao; Qinyang Li; Jingjing Wu; Lei Sun; Juan Zuo; Xiaoli Fu; Zhiyuan Li; Hui Huang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Sulfur vacancy-rich bismuth sulfide nanowire derived from CAU-17 for radioactive iodine capture in complex environments: Performance and intrinsic mechanisms - Kai-Wei Chen; Xin-Yu Zhou; Xiao-Jun Dai; Yi-Ting Chen; Shu-Xuan Li; Chun-Hui Gong; Peng Wang; Ping Mao; Yan Jiao; Kai Chen; Yi Yang (Journal of Hazardous Materials, 2024)

Extracellular vesicles separated from goat milk by differential centrifugation coupled with sodium citrate pretreatments - Shangchen Fu; Li Zhu; Xi Yang; Yang Jiao; Guo Hao; Yongfeng Liu (Food Chemistry, 2024)

SERS imaging investigation of the removal efficiency of pesticide on vegetable leaves by using different surfactants - Sugui Fang; Li Fan; Yulian Niu; Guoshuai Jiao; Haidong Jia; Feng Wang; Haifeng Yang; Yan Kang (Food Chemistry, 2024)

Global climate change: Effects of future temperatures on emergency department visits for mental disorders in Beijing, China - Yan-Lin Niu; Feng Lu; Xue-Jiao Liu; Jun Wang; De Li Liu; Qi-Yong Liu; Jun Yang (Environmental Research, 2024)

Simulation of saturated–unsaturated seepage problems via the virtual element method - Yinghao Sun; Da Li; Lei Jiao; Zhongxin Liu; Yun Yang; Junda Lyu; Shan Lin (Computers and Geotechnics, 2024)

A structure-functionality insight into the bioactivity of microbial polysaccharides toward biomedical applications: A review - Hongxing Zhang; Yan Li; Yinyi Fu; Haixin Jiao; Xiangyu Wang; Qianqian Wang; Mengbo Zhou; Yang-chun Yong; Jun Liu (Carbohydrate Polymers, 2024)

Identification and characterization of two Bacillus anthracis bacteriophages - Lun Li; Huijuan Zhang; Haixiao Jin; Jin Guo; Pan Liu; Jiao Yang; Zijian Wang; Enmin Zhang; Binbin Yu; Liyuan Shi; Jinrong He; Peng Wang; et al. (Archives of Virology, 2024)
Anthrax is an acute infectious zoonotic disease caused by Bacillus anthracis , a bacterium that is considered a potential biological warfare agent. Bacillus bacteriophages shape the composition and evolution of bacterial communities in nature and therefore have important roles in the ecosystem community. B. anthracis phages are not only used in etiological diagnostics but also have promising prospects in clinical therapeutics or for disinfection in anthrax outbreaks. In this study, two temperate B. anthracis phages, vB_BanS_A16R1 (A16R1) and vB_BanS_A16R4 (A16R4), were isolated and showed siphovirus-like morphological characteristics. Genome sequencing showed that the genomes of phages A16R1 and A16R4 are 36,569 bp and 40,059 bp in length, respectively. A16R1 belongs to the genus Wbetavirus , while A16R4 belongs to the genus Hubeivirus and is the first phage of that genus found to lyse B. anthracis . Because these two phages can comparatively specifically lyse B. anthracis , they could be used as alternative diagnostic tools for identification of B. anthracis infections.

Per- and polyfluoroalkyl substances (PFASs) in bivalve molluscs from Shandong Province, China: Occurrence, distribution, and implications for human consumption - Lijun Zhu; Yanni Jiao; Liyou Wang; Peirui Xiao; Xiaoyang Li; Zhendong Yin; Tianliang Zhang; Wenbin Zhu; Yurong Liu; Jiacheng Zhang; Luping Yang (Marine Pollution Bulletin, 2024)

Microfluidic sensors for the detection of emerging contaminants in water: A review - Yihao Zhang; Jiaxuan Li; Shipu Jiao; Yang Li; Yu Zhou; Xu Zhang; Bushra Maryam; Xianhua Liu (Science of The Total Environment, 2024)

Mechanical protein polycystin-1 directly regulates osteoclastogenesis and bone resorption - Mei Huang; Jingxuan Zhou; Xiaoxiao Li; Ran Liu; Yangzi Jiang; Kaixuan Chen; Yurui Jiao; Xin Yin; Ling Liu; Yuchen Sun; Weishan Wang; Ye Xiao; et al. (Science Bulletin, 2024)

Photochemical behaviour and toxicity evolution of phenylbenzoate liquid crystal monomers in water - Chao Li; Shaochen Li; Xiao Zhang; Xiangkun Jiang; Yi Yang; Jiao Qu; Christopher J. Martyniuk (Journal of Hazardous Materials, 2024)

Using ice surrounding to improve radio frequency tempering uniformity of bulk pacific white shrimp (Litopenaeus vannamei) - Yajin Zhang; Xiangqing Chen; Yu Liu; Feng Li; Juming Tang; Hu Shi; Yang Jiao (Journal of Food Engineering, 2024)

A novel magnetic resonance tuning-magnetic relaxation switching sensor based on Gd-MOF/USPIO assembly for sensitive and convenient aflatoxin B1 detection - Shiqin Dai; Keyu Xing; Yanna Jiao; Shaoyi Yu; Xingyu Yang; Li Yao; Pei Jia; Yunhui Cheng; Zhou Xu (Food Chemistry, 2024)

Transcriptomic and biochemical analyses reveal the antifungal mechanism of cell-free supernatant from Aspergillus luchuensis YZ-1 against Aspergillus flavus - Xiyan Zhang; Rui Jiao; Yuwei Ren; Yang Wang; Hui Li; Dexin Ou; Na Ling; Yingwang Ye (Food Bioscience, 2024)

Risk assessment and spatial analysis of paralytic shellfish toxin (PST) concentrations and acute dietary exposure of commercially available shellfish in coastal areas in China - Shuwen Li; Jiao He; Jinfang Sun; Feng Pan; Pingping Zhou; Lei Zhang; Xin Yang; Chengbin Cao; Xiaojin Yu; Pei Cao (Food Control, 2024)

Is cryoablation still suitable for advanced non-small cell lung cancer after failure of first-line chemotherapy? A multicenter, prospective, randomized-controlled trial of eighty-seven patients - Yu Chen; Xueni Fang; Dan Wang; Quanwang Li; Kerui Zhang; Yuan Li; Jinghua Li; Haoyue Pang; Zhiqiang Cheng; Chunyang Zhang; Caiyun Zhang; Wuwei Yang; et al. (Cryobiology, 2024)

Massively parallel implementation of iterative eigensolvers in large-scale plane-wave density functional theory - Junwei Feng; Lingyun Wan; Jielan Li; Shizhe Jiao; Xinhui Cui; Wei Hu; Jinlong Yang (Computer Physics Communications, 2024)

Flash spinning polyethylene/Fe3O4 magnetic drive fibers for oil absorption underwater - Dengkun Shu; Xingyu Long; Pengju Zhao; Lang Wang; Zhenhua Li; Chunzu Cheng; Shuo Yang; Long Jiao; Peng Xi; Lei Xia; Chenyang Li; Bowen Cheng (Chemical Engineering Journal, 2024)

Use of statins and risks of ovarian, uterine, and cervical diseases: a cohort study in the UK Biobank - Xue-Feng Jiao; Hailong Li; Linan Zeng; Huazhen Yang; Yao Hu; Yuanyuan Qu; Wenwen Chen; Yajing Sun; Wei Zhang; Xiaoxi Zeng; Lingli Zhang (European Journal of Clinical Pharmacology, 2024)
Purpose To examine the associations between use of statins and risks of various ovarian, uterine, and cervical diseases, including ovarian cancer, endometrial cancer, cervical cancer, ovarian cyst, polycystic ovarian syndrome, endometriosis, endometrial hyperplasia, endometrial polyp, and cervical polyp. Methods We conducted a cohort study among female participants in the UK Biobank. Information on the use of statins was collected through verbal interview. Outcome information was obtained by linking to national cancer registry data and hospital inpatient data. We used Cox proportional hazards regression to examine the associations. Results A total of 180,855 female participants (18,403 statin users and 162,452 non-users) were included. Use of statins was significantly associated with increased risks of cervical cancer (adjusted hazard ratio (HR), 1.55; 95% confidence interval (95% CI), 1.05–2.30) and polycystic ovarian syndrome (adjusted HR, 4.39; 95% CI, 1.68–11.49). However, we observed no significant association between use of statins and risk of ovarian cancer, endometrial cancer, ovarian cyst, endometriosis, endometrial hyperplasia, endometrial polyp, or cervical polyp. Conclusion Our findings suggest that use of statins is associated with increased risks of cervical cancer and polycystic ovarian syndrome, but is not associated with increased or decreased risk of ovarian cancer, endometrial cancer, ovarian cyst, endometriosis, endometrial polyp, or cervical polyp.

Environmental DNA metabarcoding reveals fish diversity, community assembly and one invasive species prevalence in a National Park of Liaohe in September - Ni Xin; Zhao Li; Yong-Wei Jiang; Hui Wang; Juan Tan; Yang Li; Bing-Jiao Sun; Xiao-Long Lin (Frontiers in Marine Science, 2024)
The escalating environmental changes are imposing multiple pressures on biodiversity conservation, thereby, more attention has been paid to fish diversity and community assembly patterns. Fish diversity in Liaohe River has deteriorated significantly due to overfishing, environmental pollution and other reasons, in addition, no fish survey related research has been published in Liaohe National Park in recent years. In order to study the diversity of fish species in the area and to investigate the presence of any invasive species. This study used eDNA metabarcoding to explore the distribution and diversity of fish communities in the Liaohe National Park. The study showed that a total of 54 species of fish from six orders, 14 families, and 39 genera were detected, meantime, the invasive species Lepomis cyanellus was found at two sampling sites. The α-diversity results showed that estuarine sites had the highest species diversity. The spatial structure of fish communities in the upstream and downstream reaches were similar as indicated by non-metric multidimensional scaling. In our study, the fish community is influenced by both deterministic and stochastic processes, with the stochastic processes being the main factor. The potential existence of L. cyanellus in Liaohe National Park might be resulted from aquaculture, ornamental pet trade, other economic fish farming, artificial release. The relatively low number of fish species in this study may be attributed to the limited number of sampling events and sampling sites. In addition to these factors, over exploitation of resources, water pollution, and the invasion of alien species have directly impacted the biodiversity of aquatic life. The results of this study lay a foundation for the future biodiversity investigation in National Parks of China, meantime, the use of eDNA monitoring is crucial to prevent, to control and limit the spreading of invasive species in advance.

Strategies to optimize the structural and functional properties of myofibrillar proteins: Physical and biochemical perspectives - Honghong Gong; Jiao Liu; Limei Wang; Li You; Kun Yang; Jing Ma; Weiqing Sun (Critical Reviews in Food Science and Nutrition, 2024)

Pathogens inactivation and preservation of Pacific white shrimp by atmospheric cold plasma treatment - Xiulan Liu; Xingyu Chen; Yan Ou; Feng Li; Yang Jiao; Hu Shi (Innovative Food Science & Emerging Technologies, 2024)

Radio frequency heating induced 3D printed white croaker (Argyrosomus argentatus) surimi gelation: Effectiveness and gel quality evaluation - Yaxing Yang; Feifan Cao; Rong Han; Feng Li; Hu Shi; Fanbin Kong; Yang Jiao (Innovative Food Science & Emerging Technologies, 2024)

Study on flotation recovery of typical carbon-bearing lead-zinc sulphide ore in Guizhou with pre-decarbonization - Guanghui Li; Zheyi Zhang; Qian Wei; Fen Jiao; Congren Yang; Wei Li; Wenqing Qin (Geochemistry, 2024)

Design of anti-saponification Ca-based catalyst with porous-shell structure from crustacean waste for biodiesel production - Mengjie Zhang; Xiangpu Jiao; Dezhang Ren; Chenxin Huang; Yang Li; Duofu Chen; Zhibao Huo (Fuel, 2024)

Influences of removable gas injection methods on the temperature field and gas composition of the underground coal gasification process - Fa-qiang Su; Jun-nan Yang; Xiao-long He; Meng-jia Dai; Akihiro Hamanaka; Yi- he Yu; Wen Li; Jiao-yuan Li (Fuel, 2024)

Distribution characteristics of reactive silicon in six water bodies in the Yangtze River Basin in China - Xuemei Chen; Lanwei Liang; Songjie Fu; Xu Bao; Sen Gu; Yang Jiao; Fang Hu; Abdur Rahman; Qingman Li (Environmental Research, 2024)

Construction of Ni3S4@ZIS@C3N5 photocatalyst with type II and Z-type heterojunctions by self-assembly for efficient photocatalytic hydrogen evolution - Huixiang Yan; Wei Li; Huixing Yang; Yongzhuo Yu; Chaoyu Lv; Linlin Hou; Wenxu Zhang; Di Lin; Shichao Jiao (Environmental Research, 2024)

Establishing an efficient micropropagation method for Astragalus membranaceus (Huang Qi) - Thi Ngoc Anh Tran; Feng-Jiao Xu; Jae-Heung Ko; Deok-Chun Yang; Yingping Wang; Li Ling; Dong-Uk Yang; Seok-Kyu Jung (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

High-resolution land surface modeling of the irrigation effects on evapotranspiration over the Yellow River basin - Chenyuan Li; Xing Yuan; Yang Jiao; Peng Ji; Zhongwei Huang (Journal of Hydrology, 2024)

Solid waste-based super-retarded damp-shotcrete for low carbon and environmental protection - Feng-bin Chen; Ming-yang Li; Chun-lai Wang; Hua-zhe Jiao; Xin-ming Chen; Yi-xuan Yang; Liu-hua Yang; Hao-shuang Niu (Journal of Cleaner Production, 2024)

The ultrathin regular circular structural Ni-P nanosheet for efficient urea electrooxidation - Duo Yang; Jinqi Li; Weidong Li; You-Zhou Jiao; Jing-He Yang (Journal of Environmental Chemical Engineering, 2024)

Improvement of electroporation-mediated transformation efficiency for Bifidobacterium animalis AR668 - Jiao Li; Zhiqiang Xiong; Miao Yang; Xin Song; Guangqiang Wang; Yongjun Xia; Lianzhong Ai (Food Bioscience, 2024)

An elastase nanocomplex with metal cofactors for enhancement of target protein cleavage activity and synergistic antitumor effect - Chuanda Zhu; Xi Chen; Jingjing Gong; Jiao Liu; Lidong Gong; Zeliang Yang; Zhenyu Zhu; Qiang Zhang; Tiancheng Li; Ling Liang; Zhiqiang Lin (Chemical Engineering Journal, 2024)

Tricarboxylic acid cycle metabolites: new players in macrophage - Ying Yang; Bing-Bing Cui; Jian Li; Jiao-Jiao Shan; Jun Xu; Cheng-Yong Zhang; Xiao-Tong Wei; Ri-Ran Zhu; Jing-Yi Wang (Inflammation Research, 2024)

Non-enzymatic Detection of Uric Acid in Serum and Urine by Fluorescent and Visual Dual-Mode Sensor Based on 3-aminophenylboric Acid Functionalized Carbon Dots - Xin Li; Guoqing Chen; Anqi Hu; Yi Xiong; Taiqun Yang; Chaoqun Ma; Lei Li; Hui Gao; Chun Zhu; Yamin Wu; Jiao Gu; Hui Wu; et al. (Journal of Fluorescence, 2024)

Nitrogen and Sulfur co-doped Carbon dots as an “on-off-on” Fluorescent Sensor for the Detection of Hg2+ and Ampicillin - LongYao Ma; ChaoQun Ma; GuoQing Chen; Jiao Gu; Taiqun Yang; Lei Li; Hui Gao; Yi Xiong; Yamin Wu; Chun Zhu; Yan Zhou; Anqi Hu; et al. (Journal of Fluorescence, 2024)

A potential dual protection vaccine: Recombinant feline herpesvirus-1 expressing feline parvovirus VP2 antigen - Mengfang Yang; Yuzhou Jiao; Lisha Li; Yuanyuan Yan; Zhen Fu; Zirui Liu; Xiaoshuai Hu; Mengxia Li; Yuejun Shi; Junwei He; Zhou Shen; Guiqing Peng (Veterinary Microbiology, 2024)

Overexpression of Nrf2 reverses ferroptosis induced by Arenobufagin in gastric cancer - Jiao Long; Wenjun Wang; Jing Chu; Yueyue Li; Meng Wang; Jingjing Su; Yuting Yang; GuoKai Wang; Qinglin Li; Hui Cheng (Toxicology and Applied Pharmacology, 2024)

Deciphering the biotic and abiotic drivers of coalescence asymmetry between soil and manure microbiomes - Chunkai Li; Xianping Li; Sana Romdhane; Yanhong Cheng; Gen Li; Rui Cao; Peng Li; Jingjing Xu; Yexin Zhao; Yang Yang; Jiaguo Jiao; Feng Hu; et al. (Science of The Total Environment, 2024)

In-situ construction of Z-scheme silver phosphotungstate/polyimide photocatalysts and enhanced visible-light photocatalytic degradation of aflatoxin B1 in vegetable oil - Pengcheng Meng; Jiao Li; Panpan Wang; Guolong Yang; Wei Liu; Shaohua Liang; Ruinan Yang; Cong Sun (Chemical Engineering Journal, 2024)

Circ DENND4C inhibits pyroptosis and alleviates ischemia-reperfusion acute kidney injury by exosomes secreted from human urine-derived stem cells - Boxin Yang; Junxiong Wang; Jiao Qiao; Qian Zhang; Qi Liu; Yuan Tan; Qingchen Wang; Wenyuan Sun; Weimin Feng; Zhongxin Li; Chong Wang; Shuo Yang; et al. (Chemico-Biological Interactions, 2024)

Effects of residential damp indicators on asthma, rhinitis, and eczema among children: A systematic review and meta-analysis of the literature in the past 33 years - Jiao Cai; Minghan Yang; Nan Zhang; Ying Chen; Jianhua Wei; Jian Wang; Qixin Liu; Wenjie Li; Wenming Shi; Wei Liu (Building and Environment, 2024)

A four-band index for both liquid and solid water and its applications in the Aral Sea Basin - Bing Yue; Xi Chen; Saibo Li; Zhengping Du; John Wilson; Junhui Yang; Yimen Jiao; Shuangyan Huang; Chenghu Zhou (Science China Earth Sciences, 2024)

Genetic Composition of the High-Quality Winter Wheat Varieties ‘Xinmai 26’ and ‘Xinmai 45’ - Li-Juan Yang; Jian Ma; Da-Le Zhang; Hai-Feng Yang; Yan-Qi Dong; Zeng-Jun Qi; Meng-Jiao Li; Zhi-Kai Jiang; Hua-Ping Ma (Plant Molecular Biology Reporter, 2024)

o-phenylenediamine Derived Fluorescent Carbon Quantum dots for Detection of Hg(II) in Environmental Water - Anqi Hu; Guoqing Chen; Anlan Huang; Zicheng Cai; Taiqun Yang; Chaoqun Ma; Lei Li; Hui Gao; Jiao Gu; Chun Zhu; Yamin Wu; Xiaoqian Qiu; et al. (Journal of Fluorescence, 2024)

Image-based vegetation analysis of desertified area by using a combination of ImageJ and Photoshop software - Jin Tong; Longying Wu; Bin Li; Nan Jiang; Jin Huang; Di Wu; Lihong Zhou; Qingwen Yang; Yuan Jiao; Ji Chen; Ke Zhao; Xiangjun Pei (Environmental Monitoring and Assessment, 2024)

Hypoxia Potentiated Lung Cancer Cell Migration and Invasion by up-regulating HIF1α/JAK2/STAT3 Axis and Activating MMP13 Transcription - Xiaoju Cheng; Damin Liang; Xiaoqian Li; Chengmin Deng; Meng Ye; Jiao Yang; Yurui Liu; Kaifeng Wu; Jie Wu; Peng Tian (Cell Biochemistry and Biophysics, 2024)

Evolution model and failure mechanisms of rainfall-induced cracked red clay slopes: insights from Xinshao County, China - Weizhi Jiao; Ming Zhang; Peng Li; Junjin Xie; Haisong Pang; Fuxing Liu; Long Yang (Journal of Mountain Science, 2024)

Summer electricity consumption and its drivers in urban areas - Feng Gao; Zhenzhi Jiao; Shunyi Liao; Rui Liu; Zhisai Hu; Yang Liu; Hongbao Li; Wangyang Chen; Xin Chen; Guanyao Li (Applied Geography, 2024)

Therapeutic potential of dietary flavonoid hyperoside against non-communicable diseases: targeting underlying properties of diseases - Jia Xia; Yan Wan; Jiao-jiao Wu; Yu Yang; Jin-Feng Xu; Li Zhang; Dong Liu; Lu Chen; Fei Tang; Hui Ao; Cheng Peng (Critical Reviews in Food Science and Nutrition, 2024)

Investigation of the Application and Mechanism of Nitrogen and Phosphorus Co-doped Carbon Dots for Mercury Ion Detection - Dong Yang; Chaoqun Ma; Guoqing Chen; Lei Li; Anqi Hu; Anlan Huang; Yan zhou; Zicheng Cai; Taiqun Yang; Hui Gao; Jiao Gu; Chun Zhu; et al. (Journal of Fluorescence, 2024)

Insight into the role of niche concept in deciphering the ecological drivers of MPs-associated bacterial communities in mangrove forest - Yijin Wang; Meng Jiao; Zhen Zhao; Yinghui Wang; Tiezhu Li; Yihua Wei; Ruilong Li; Fei Yang (Water Research, 2024)

Lanostane triterpenoids from the fruiting bodies of Ganoderma amboinense - Li Yang; Guan-Hai Dong; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; You-Gen Wu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2024)

Four pairs of neolignan enantiomers with distinctive isochroman moiety from the fruits of Crataegus pinnatifida and their protective activities against H2O2-induced SH-SY5Y cells - Peng Zhao; Shi-Fang Li; Jiao-Yang Hou; Shu-Yan Qin; Jia-Yi Li; Xiao-Fang Zhou; Xuan Liu; Jin-Le Hao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Anti-biofilm activity and in vivo efficacy of quinoline for the control of Vibrio parahaemolyticus in Chinese white shrimps - Shuang-Shuang Song; Yao-Yao Lu; Mei-Jing Zhu; Qian-Ye Zuo; Li-Xiang Zhou; Gui-Yang Zhu; Yun-Jiao Zhang; Xiao-Feng Lu; Jie Gong; Su-Yan Wang; Daniela D. Herrera-Balandrano; Pedro Laborda; et al. (Food Control, 2024)

Giant electrical conductivity difference enabled liquid metal-hydrogel hybrid printed circuits for soft bioelectronics - Caicai Jiao; Liangtao Li; Baoyang Lu; Qian Wang; Weili Hong; Xing Chen; Lingqian Chang; Xinpeng Wang; Yang Wang; Kang Sun; Liang Hu; Yubo Fan (Chemical Engineering Journal, 2024)

Rainfall characteristics of sediment connectivity activation from plot to watershed scales on the Loess Plateau - Xiqin Yan; Juying Jiao; Xiaohan Jiang; Qian Xu; Mengmeng Li; Ziqi Zhang; Hongkun Qi; Long Yang (CATENA, 2024)

Functional characterization of genes related to triterpene and flavonoid biosynthesis in Cyclocarya paliurus - Shuang-yan Zhang; Yu-qing Peng; Gui-sheng Xiang; Wan-ling Song; Lei Feng; Xin-yue Jiang; Xue-jiao Li; Si-mei He; Sheng-chao Yang; Yan Zhao; Guang-hui Zhang (Planta, 2024)

Ucp4 Knockdown of Cerebellar Purkinje Cells Induces Bradykinesia - Ya-Yun Wang; Hui Liu; Shu-Jiao Li; Ban Feng; Yun-Qiang Huang; Shui-Bing Liu; Yan-Ling Yang (Molecular Neurobiology, 2024)
Although uncoupling protein 4 (UCP4) is the most abundant protein reported in the brain, the biological function of UCP4 in cerebellum and pathological outcome of UCP4 deficiency in cerebellum remain obscure. To evaluate the role of Ucp4 in the cerebellar Purkinje cells (PCs), we generated the conditional knockdown of Ucp4 in PCs ( Pcp2 cre ;Ucp4 fl/fl mice) by breeding Ucp4 fl/fl mice with Pcp2 cre mice. Series results by Western blot, immunofluorescent staining, and triple RNAscope in situ hybridization confirmed the specific ablation of Ucp4 in PCs in Pcp2 cre ;Ucp4 fl/fl mice, but did not affect the expression of Ucp2 , the analog of Ucp4 . Combined behavioral tests showed that Pcp2 cre ;Ucp4 fl/fl mice displayed a characteristic bradykinesia in the spontaneous movements. The electromyogram recordings detection excluded the possibility of hypotonia in Pcp2 cre ;Ucp4 fl/fl mice. And the electrical patch clamp recordings showed the altered properties of PCs in Pcp2 cre ;Ucp4 fl/fl mice. Moreover, transmission electron microscope (TEM) results showed the increased mitochondrial circularity in PCs; ROS probe imaging showed the increased ROS generation in molecular layer; and finally, microplate reader assay showed the significant changes of mitochondrial functions, including ROS, ATP, and MMP in the isolated cerebellum tissue. The results suggested that the specific knockdown of mitochondrial protein Ucp4 could damage PCs possibly by attacking their mitochondrial function. The present study is the first to report a close relationship between UCP4 deletion with PCs impairment, and suggests the importance of UCP4 in the substantial support of mitochondrial function homeostasis in bradykinesia. UCP4 might be a therapeutic target for the cerebellar-related movement disorder. Graphical Abstract

Gut microbiota influence frailty syndrome in older adults: mechanisms and therapeutic strategies - Xiao-Ming Wang; Lu Fan; Chen-Chen Meng; Yun-Jiao Wang; Li-E Deng; Zhuo Yuan; Jun-Ping Zhang; Yan-Yang Li; Shi-Chao Lv (Biogerontology, 2024)

Species pool, local assembly processes: Disentangling the mechanisms determining bacterial α‐ and β‐diversity during forest secondary succession - Xiao Zhang; Handan Dai; Yongtao Huang; Kuan Liu; Xingang Li; Shuoxin Zhang; Shenglei Fu; Shuo Jiao; Chunbo Chen; Biao Dong; Zhu Yang; Yang Cui; et al. (Molecular Ecology, 2024)
Across ecology, and particularly within microbial ecology, there is limited understanding how the generation and maintenance of diversity. Although recent work has shown that both local assembly processes and species pools are important in structuring microbial communities, the relative contributions of these mechanisms remain an important question. Moreover, the roles of local assembly processes and species pools are drastically different when explicitly considering the potential for saturation or unsaturation, yet this issue is rarely addressed. Thus, we established a conceptual model that incorporated saturation theory into the microbiological domain to advance the understanding of mechanisms controlling soil bacterial diversity during forest secondary succession. Conceptual model hypotheses were tested by coupling soil bacterial diversity, local assembly processes and species pools using six different forest successional chronosequences distributed across multiple climate zones. Consistent with the unsaturated case proposed in our conceptual framework, we found that species pool consistently affected α‐diversity, even while local assembly processes on local richness operate. In contrast, the effects of species pool on β‐diversity disappeared once local assembly processes were taken into account, and changes in environmental conditions during secondary succession led to shifts in β‐diversity through mediation of the strength of heterogeneous selection. Overall, this study represents one of the first to demonstrate that most local bacterial communities might be unsaturated, where the effect of species pool on α‐diversity is robust to the consideration of multiple environmental influences, but β‐diversity is constrained by environmental selection.

Multiple spatial scales of bacterial and fungal structural and functional traits affect carbon mineralization - Zhiyuan Ma; Shuo Jiao; Kaikai Zheng; Haowei Ni; Dong Li; Na Zhang; Yunfeng Yang; Jizhong Zhou; Bo Sun; Yuting Liang (Molecular Ecology, 2024)
Studying the functional heterogeneity of soil microorganisms at different spatial scales and linking it to soil carbon mineralization is crucial for predicting the response of soil carbon stability to environmental changes and human disturbance. Here, a total of 429 soil samples were collected from typical paddy fields in China, and the bacterial and fungal communities as well as functional genes related to carbon mineralization in the soil were analysed using MiSeq sequencing and GeoChip gene microarray technology. We postulate that CO 2 emissions resulting from bacterial and fungal carbon mineralization are contingent upon their respective carbon consumption strategies, which rely on the regulation of interactions between biodiversity and functional genes. Our results showed that the spatial turnover of the fungal community was 2–4 times that of the bacterial community from hundreds of meters to thousands of kilometres. The effect of spatial scale exerted a greater impact on the composition rather than the functional characteristics of the microbial community. Furthermore, based on the establishment of functional networks at different spatial scales, we observed that both bacteria and fungi within the top 10 taxa associated with carbon mineralization exhibited a prevalence of generalist species at the regional scale. This study emphasizes the significance of spatial scaling patterns in soil bacterial and fungal carbon degradation functions, deepening our understanding of how the relationship between microbial decomposers and soil heterogeneity impacts carbon mineralization and subsequent greenhouse gas emissions.

Influences of hydrodynamics on microbial community assembly and organic carbon composition of resuspended sediments in shallow marginal seas - Yangli Che; Chaoran Lin; Shen Li; Jiao Liu; Longhai Zhu; Shilei Yu; Nan Wang; Haoshuai Li; Mutai Bao; Yang Zhou; Tonghao Si; Rui Bao (Water Research, 2024)

Green and sustainable microwave processing of surimi seafood: A review of protein component interactions, mechanisms, and industrial applications - Xidong Jiao; Huayu Yang; Xingying Li; Hongwei Cao; Nana Zhang; Bowen Yan; Bo Hu; Jianlian Huang; Jianxin Zhao; Hao Zhang; Wei Chen; Daming Fan (Trends in Food Science & Technology, 2024)

Dynamic fluctuations in plant leaf interception of airborne microplastics - Meng Jiao; Yijin Wang; Fei Yang; Zhen Zhao; Yihua Wei; Ruilong Li; Yinghui Wang (Science of The Total Environment, 2024)

Transcriptome analysis revealed the function of five tandemly duplicated nAChRs in the transplantation immunity in pearl oyster Pinctada fucata martensii - Min Yang; Ming Zhang; Xin lei Li; Yue wen Deng; Yu Jiao (Fish & Shellfish Immunology, 2024)

Innovative construction of nano-wrinkled polyamide membranes using covalent organic framework nanoflowers for efficient desalination and antibiotic removal - Baoliang Dai; Yijing Hu; Yidan Ding; Liguo Shen; Renjie Li; Dieling Zhao; Yang Jiao; Yanchao Xu; Hongjun Lin (Desalination, 2024)

Green N1 additive modified perovskite precursor enables effective manufacturing of large-area solar cell modules with high efficiency and stability - Yue Zang; Yibo Tu; Chuanjia Jiao; Wangnan Li; Peng Zhou; Jiahao Cheng; Gaoyuan Yang; Tianxiang Shao; Jingchuan Ye; Guodong Li; Liang Chu; Shaojian Lu; et al. (Chemical Engineering Journal, 2024)

Responses of the fungal-bacterial community and network to surface mulching and nitrogen fertilization in the Loess Plateau - Qiang Liu; Liang Tang; Haoran Sun; Xueqin Kong; Yang Jiao; Wenqi Wu; Shiqing Li; Yufang Shen (Plant and Soil, 2024)

Characterization of two peanut genotypes for biochemical quality attributes and cotyledon microstructure features - Jin Li; Chun Jiao Jiang; Hao Jie Sun; Zhi Wei Wang; Zhen Yang; Xiu Zhen Wang; Xiu Shan Sun; Ming Jun Zhang; Chuan Tang Wang (Genetic Resources and Crop Evolution, 2024)

The neglected roles of adjacent natural ecosystems in maintaining bacterial diversity in agroecosystems - Ziheng Peng; Yunfeng Yang; Yu Liu; Lianyan Bu; Jiejun Qi; Hang Gao; Shi Chen; Haibo Pan; Beibei Chen; Chunling Liang; Xiaomeng Li; Yining An; et al. (Global Change Biology, 2024)
A central aim of community ecology is to understand how local species diversity is shaped. Agricultural activities are reshaping and filtering soil biodiversity and communities; however, ecological processes that structure agricultural communities have often overlooked the role of the regional species pool, mainly owing to the lack of large datasets across several regions. Here, we conducted a soil survey of 941 plots of agricultural and adjacent natural ecosystems (e.g., forest, wetland, grassland, and desert) in 38 regions across diverse climatic and soil gradients to evaluate whether the regional species pool of soil microbes from adjacent natural ecosystems is important in shaping agricultural soil microbial diversity and completeness. Using a framework of multiscales community assembly, we revealed that the regional species pool was an important predictor of agricultural bacterial diversity and explained a unique variation that cannot be predicted by historical legacy, large‐scale environmental factors, and local community assembly processes. Moreover, the species pool effects were associated with microbial dormancy potential, where taxa with higher dormancy potential exhibited stronger species pool effects. Bacterial diversity in regions with higher agricultural intensity was more influenced by species pool effects than that in regions with low intensity, indicating that the maintenance of agricultural biodiversity in high‐intensity regions strongly depends on species present in the surrounding landscape. Models for community completeness indicated the positive effect of regional species pool, further implying the community unsaturation and increased potential in bacterial diversity of agricultural ecosystems. Overall, our study reveals the indubitable role of regional species pool from adjacent natural ecosystems in predicting bacterial diversity, which has useful implication for biodiversity management and conservation in agricultural systems.

Polyphenols and polyphenols-based biopolymer materials: Regulating iron absorption and availability from spontaneous to controllable - Yafei Zhang; Xiaojing Tian; Anguo Teng; Yu Li; Yuzhen Jiao; Kaixuan Zhao; Yang Wang; Ruonan Li; Ning Yang; Wenhang Wang (Critical Reviews in Food Science and Nutrition, 2023)

Potato late blight severity monitoring based on the relief-mRmR algorithm with dual-drone cooperation - Heguang Sun; Xiaoyu Song; Wei Guo; Mei Guo; Yanzhi Mao; Guijun Yang; Haikuan Feng; Jie Zhang; Ziheng Feng; Jiao Wang; Yuanyuan Ma; Chunkai Zheng; et al. (Computers and Electronics in Agriculture, 2023)

Ubiquitin-specific peptidase 47 (USP47) regulates cutaneous oxidative injury through nicotinamide nucleotide transhydrogenase (NNT) - Xiaoqian Li; Kun Qian; Yuehua Zhang; Yining Zhang; Yulan Liu; Chuntang Sun; Yang Jiao; Daojiang Yu; Fenghao Geng; Jianping Cao; Shuyu Zhang (Toxicology and Applied Pharmacology, 2023)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Geochemical behavior and source analysis of rare earth elements in intensive agriculture soils through high-resolution sampling - Yalu Zhang; Baowei Su; Shuangshuang Shao; Ning Li; He Jiao; Yang Dan; Huan Zhang; Chao Gao (Science of The Total Environment, 2023)

Source apportionment and source specific health risk assessment of HMs and PAHs in soils with an integrated framework in a typical cold agricultural region in China - Jin Wu; Gang Yang; Haiyang Chen; Yuanzheng Zhai; Yanguo Teng; Jiao Li; Ruihui Chen (Science of The Total Environment, 2023)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

Drying-rewetting cycles reduce bacterial diversity and carbon loss in soil on the Loess Plateau of China - Panpan JIAO; Haibing XIAO; Zhongwu LI; Lei YANG; Peng ZHENG (Pedosphere, 2023)

Removal of heavy metal ions from acidic wastewater by constructing positively charged hollow fiber nanofiltration separating-layer based on Fe (III)/co deposition-quaternization - Yaoyao Jiao; Junjie Yang; Jing Zhang; Jianxin Li; Shuhao Qin; Xiao Wu; Zhenyu Cui (Journal of Water Process Engineering, 2023)

Mechanistic investigation of Sm doping effects on SO2 resistance of W-Zr-ZSM-5 catalyst for NH3-SCR - Shuo Feng; Wenwen Kong; Yanli Wang; Yuye Xing; Zhuozhi Wang; Jiao Ma; Boxiong Shen; Long Chen; Jiancheng Yang; Zhaoming Li; Chenguang Zhang (Fuel, 2023)

Changes in groundwater dynamics and geochemical evolution induced by drainage reorganization: Evidence from 81Kr and 36Cl dating of geothermal water in the Weihe Basin of China - Jie Li; Zhonghe Pang; Yulian Liu; Shuiming Hu; Wei Jiang; Lijun Tian; Guomin Yang; Ying Jiang; Xuan Jiao; Jiao Tian (Earth and Planetary Science Letters, 2023)

Correction to: Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Arman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Nano-composite system of traditional Chinese medicine for ocular applications: molecular docking and three-dimensional modeling insight for intelligent drug evaluation - Xinyi Jiao; Xingru Peng; Xin Jin; Ning Liu; Yang Yu; Rui Liu; Zheng Li (Drug Delivery and Translational Research, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Impact of the geometric structure parameter on the performance of dielectric barrier reactor for toluene removal - Xin Yu; Shijie Li; Yang Jiao; Yitong Ren; Yongkang Kou; Xiaoqing Dang (Environmental Science and Pollution Research, 2023)

The hepatoprotective effects of plant-based foods based on the “gut–liver axis”: a prospective review - Qiongdan Hu; Wan Liao; Zhen Zhang; Sanjun Shi; Shuguang Hou; Ningping Ji; Xinjie Zhang; Qian Zhang; Yangyang Liao; Linghui Li; Zongping Zhu; Yi Chen; et al. (Critical Reviews in Food Science and Nutrition, 2023)

ASPP-YOLOv5: A study on constructing pig facial expression recognition for heat stress - Lili Nie; Bugao Li; Fan Jiao; JiaYuan Shao; Tingting Yang; Zhenyu Liu (Computers and Electronics in Agriculture, 2023)

Lanostane triterpenoids with anti-proliferative and PTP1B/α-glucosidase inhibitory activities from the fruiting bodies of Ganoderma calidophilum - Li Yang; Ting-Ting Zhang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Jia-Ju Lu; Zhi-Fang Yu; Hao-Fu Dai; You-Xing Zhao (Phytochemistry, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

New evidence of consistency between phylogeny and morphology for two taxa in ciliated protists, the subclasses Oligotrichia and Choreotrichia (Protista, Ciliophora) - Wen Song; Huixin Jiao; Juan Yang; Danxu Tang; Tingting Ye; Lu Li; Lei Yang; Lifang Li; Weibo Song; Saleh A. Al-Farraj; Hunter N. Hines; Weiwei Liu; et al. (Molecular Phylogenetics and Evolution, 2023)

Do recycling channels affect young consumers' choices for formal power battery recycling? - Jingjing Li; Yuwen Xu; Jianling Jiao; Ranran Yang; Jianrui Zha (Journal of Cleaner Production, 2023)

Climatic aridification restrained late Cenozoic denudation of the Tian Shan in the inland of Asia - Yutong Jiang; Honghua Lu; Ruohong Jiao; Lichen Pang; Rong Yang; Menghan Wu; Xiangmin Zheng; Youli Li (Global and Planetary Change, 2023)

Light-responsive benzobisthiazole as oxidase mimic for rapid determination of glutathione in food and vegetable - Jiao Wu; Lingbo Qu; Zhaohui Li; Linping Zhao; Yuanqiang Sun; Ran Yang (Food Chemistry, 2023)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

In-situ introduction of CePO4 for stabilizing electrocatalytic activity of quasi-MOF with partially missing C≡N skeleton - Shuke Li; Meng Xie; Xiao Zhang; Nana Wang; Ran Wang; Yanchao Xu; Hongjun Lin; Yang Jiao; Jianrong Chen (Chemical Engineering Journal, 2023)

Improvement of Learning and Memory by Elevating Brain D-Aspartate in a Mouse Model of Fragile X Syndrome - Yu-Jiao Li; Kun Zhang; Ting Sun; Yan-Yan Guo; Qi Yang; Shui-Bing Liu; Yu-Mei Wu; Ming-Gao Zhao (Molecular Neurobiology, 2023)
Fragile X syndrome (FXS) is an inherited human mental retardation that arises from expansion of a CGG repeat in the Fmr1 gene, causing loss of the fragile X mental retardation protein (FMRP). It is reported that N-methyl-D-aspartate receptor (NMDAR)-mediated facilitation of long-term potentiation (LTP) and fear memory are impaired in Fmr1 knockout (KO) mice. In this study, biological, pharmacological, and electrophysiological techniques were performed to determine the roles of D-aspartate (D-Asp), a modulator of NMDAR, and its metabolizing enzyme D-aspartate oxidase (DDO) in Fmr1 KO mice. Levels of D-Asp were decreased in the medial prefrontal cortex (mPFC ); however, the levels of its metabolizing enzyme DDO were increased. Electrophysiological recordings indicated that oral drinking of D-Asp recovered LTP induction in mPFC from Fmr1 KO mice. Moreover, chronic oral administration of D-Asp reversed behavioral deficits of cognition and locomotor coordination in Fmr1 KO mice. The therapeutic action of D-Asp was partially through regulating functions of NMDARs and mGluR5/mTOR/4E-BP signaling pathways. In conclusion, supplement of D-Asp may benefit for synaptic plasticity and behaviors in Fmr1 KO mice and offer a potential therapeutic strategy for FXS.

Contamination, ecological-health risks, and sources of potentially toxic elements in road-dust sediments and soils of the largest urban riverfront scenic park in China - Jun Li; Kai-Ming Li; Liang Jiao; Fei Zang; Xu Li; Yun-Qin Yang; Xiao-Xuan Mao; Xi-Sheng Tai (Environmental Geochemistry and Health, 2023)

Occurrence of 8 trace elements in Rhizoma Cibotii from China and exposure assessment - Zhijie Chu; Nannan Zhu; Lijun Shao; Hongxia Xu; Jin Li; Xiaolin Wang; Yanni Jiao; Dafeng Jiang; Peimin Yang (Environmental Science and Pollution Research, 2023)

Analysis of spatiotemporal patterns of atmospheric CO2 concentration in the Yellow River Basin over the past decade based on time-series remote sensing data - Yang Lv; Yuchen Ma; Haoyu Li; Yuhang Ding; Qinghe Meng; Jiao Guo (Environmental Science and Pollution Research, 2023)

Effect of iron-loaded sludge biochar amendments on phytoremediation potential of Cr-contaminated soils by Leersia hexandra swartz - Jin-Chao Wang; Ji-Rong Zhao; Qing-Xia Huang; Li-Jiao Yang; Guo Yu; Yu-Feng Xu; Li-Heng Liu (Chemosphere, 2023)

Effects of phosphorus species and zinc stress on growth and physiology of the marine diatom Thalassiosira weissflogii - Kailin Jiao; Hang Yang; Xuguang Huang; Fengjiao Liu; Shunxing Li (Chemosphere, 2023)

Legacy per- and polyfluoroalkyl substances (PFASs) especially alternative PFASs in shellfish from Shandong Province, China: Distribution, sources, and health risk - Jiacheng Zhang; Wei Li; Luping Yang; Zunhua Chu; Yanni Jiao; Lin Wang; Lijun Zhu; Chuan Qin; Rui Liu; Xibao Gao (Marine Pollution Bulletin, 2023)

Fe2O3 micron particles are critical for electron transfer and the distribution of electrochemically active bacteria in soil MFCs - Jingran Zhang; Shan Huang; Yongguang Yin; Liuqing Yang; Xianning Li; Wentao Jiao; Takashi Sakamaki (Science of The Total Environment, 2023)

Abietane diterpenoids with anti-inflammatory activities from Callicarpa bodinieri - Yue Sun; Hong-Ying Yang; Pei-Zhi Huang; Lan-Jun Zhang; Wei-Jiao Feng; Ya Li; Kun Gao (Phytochemistry, 2023)

Labdane and ent-halimane diterpenoids with STAT3-inhibitory activity from Leonurus sibiricus - Chen Wang; Jiao Tian; Chaoge Liu; Yiming He; Jiahang Li; Qiang Zhang; Ting Xiao; Chunfeng Xie; Cheng Yang (Phytochemistry, 2023)

Role of garbage classification in air pollution improvement of a municipal solid waste disposal base - Song Gao; Lingning Meng; Xiang Ge; Yuewu Li; Yong Yang; Yusen Duan; Qingyan Fu; Shuwei Zhang; Xuechun Yang; Weiliang Fei; Zheng Jiao (Journal of Cleaner Production, 2023)

A case study on marmatite- pyrite/pyrrhotite selective flotation with two-step pulp regulation - Haodong Li; Wenqing Qin; Zuyuan Tian; Changfa Wu; Fen Jiao; Congren Yang (Journal of Environmental Chemical Engineering, 2023)

Transcriptomic analysis reveals novel desiccation tolerance mechanism of Cronobacter based on type VI secretion system inhibition - Yang Wang; Na Ling; Rui Jiao; Xiyan Zhang; Yuwei Ren; Hui Li; Wenhua Zhao; Qingping Wu; Yingwang Ye (Food Research International, 2023)

High-throughput, highly sensitive and rapid SERS detection of Escherichia coli O157:H7 using aptamer-modified Au@macroporous silica magnetic photonic microsphere array - Xiu Wang; Wei Li; Shijie Dai; Menghua Dou; Saisai Jiao; Jing Yang; Weiwei Li; Ya Su; Qianjin Li; Jianlin Li (Food Chemistry, 2023)

Nano-wrinkled polyamide membrane preparation via heterogeneous surface-regulated interfacial polymerization for enhanced desalination performance - Zhiwen Li; Yanchao Xu; Liguo Shen; Renjie Li; Yang Jiao; Hongjun Lin; Chuyang Y. Tang (Desalination, 2023)

Innovative role of polyvinylpyrrolidone in tailoring polyamide layer for high-performance nanofiltration membranes - Zhiwen Li; Shuilian Peng; Wentian Zhang; Jianzhen Zhang; Yang Jiao; Renjie Li; Liguo Shen; Hongjun Lin; Yanchao Xu (Desalination, 2023)

The impact of bedroom environment on sleep quality in winter and summer in the Qinghai-Tibetan plateau - Chao Guo; Li Lan; Haodong Zhang; Yan Yan; Mengyuan Kang; Yige Liu; Zuobing Yang; Hu Jiao; Songming Liu (Building and Environment, 2023)

Experimental research progress of grid to rod fretting in pressurized water reactors - Yong-jun Jiao; Zheng-yang Li; Zeng-ping Pu; Mei-yin Zheng; Quan-yao Ren; Zhen-bing Cai; Yin-wei Wu; Sui-zheng Qiu (Annals of Nuclear Energy, 2023)

Coordination effect enhanced visualization of latent fingerprint with Eu (TTA)3phen-SiO2 microspheres - Kang Zhang; Meng-Jiao Zhu; Yi-Wen Zhou; Xiao Liu; Feng Chen; Yu-Yang Zhou; Wan-Fei Li; Sheng Liu; Yun Jiang; Shou-Qing Liu (Analytica Chimica Acta, 2023)

Effects of dietary isoleucine level on growth and expression of genes related to nutritional and physiological metabolism of swimming crab (Portunus trituberculatus) - Shichao Xie; Xiangkai Li; Yuhang Yang; Chen Guo; Xiangsheng Zhang; Tingting Zhu; Jiaxiang Luo; Zheng Yang; Wenli Zhao; Yuhui Cui; Lefei Jiao; Qicun Zhou; et al. (Aquaculture, 2023)

Optical properties and molecular composition of wintertime atmospheric water-soluble organic carbon in different coastal cities of eastern China - Haibiao Chen; Caiqing Yan; Qinglong Fu; Xinfeng Wang; Jiao Tang; Bin Jiang; Honglei Sun; Tiancheng Luan; Qiaoyun Yang; Qianbiao Zhao; Jun Li; Gan Zhang; et al. (Science of The Total Environment, 2023)

Carbon reduction behavior of waste power battery recycling enterprises considering learning effects - Jianling Jiao; Yuqin Chen; Jingjing Li; Shanlin Yang (Journal of Environmental Management, 2023)

Investigation on the mechanism of Nb and Si co-doping on low SO3 generation from V-based catalyst during NH3-SCR process - Shuo Feng; Bo Wang; Yuye Xing; Wenwen Kong; Jiao Ma; Chenguang Zhang; Zhaoming Li; Boxiong Shen; Zhuozhi Wang; Long Chen; Jiancheng Yang (Fuel, 2023)

Precooking treatments affect the sensory and tensile properties of autoclaved recooked noodles via moisture distribution and protein structure - Xin Guo; Fengying Gu; Yang Li; Qiaozhen Zhang; Runrun Hu; Bo Jiao; Feng Wang; Qiang Wang (Food Chemistry, 2023)

Toxic effects of perfluorocaproic acid (PFHxA) on crucian carp (Carassius auratus) and the response of the intestinal microbial community - Xue Jiao; Zheng yao Guo; Bing li Liu; Long tao Wang; Zhi nan Yang; Yuan ru Yang; Ai-dong Qian; Yue-hong Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Lactate Improves Long-term Cognitive Impairment Induced By Repeated Neonatal Sevoflurane Exposures Through SIRT1-mediated Regulation of Adult Hippocampal Neurogenesis and Synaptic Plasticity in Male Mice - Li-Li Qiu; Xiao-Xiang Tan; Jiao-Jiao Yang; Mu-Huo Ji; Hui Zhang; Chunjie Zhao; Jiang-Yan Xia; Jie Sun (Molecular Neurobiology, 2023)

Better therapeutic effect of oral administration of GS441524 compared with GC376 - Yuanyuan Yan; Jia Li; Zhe Jiao; Mengfang Yang; Lisha Li; Gang Wang; Yixi Chen; Mengxia Li; Zhou Shen; Yuejun Shi; Guiqing Peng (Veterinary Microbiology, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Sewage Sludge-Derived catalyst for extremely efficient electrocatalytic elimination of organic pollutants in water - Haonan Zhang; Shaoqing Chen; Nianji Zhang; Huihuang Chen; Yutong Yang; Yang Tu; Chuanlai Jiao; Zian Xu; Yu Xia; Hongri Suo; Zesheng Li; Chongxuan Liu; et al. (Chemical Engineering Journal, 2023)

Increased risk of respiratory and allergic diseases in preschoolers from building envelope dampness exposure: Repeated cross-sectional surveys in multicity China - Wei Yu; Yan Zhang; Baizhan Li; Yinping Zhang; Chenqiu Du; Zhuohui Zhao; Dan Norback; Jiao Cai; Qihong Deng; Chan Lu; Hua Qian; Xiaohong Zheng; et al. (Building and Environment, 2023)

Clinical Significance and Influencing Factors of Microvascular Tissue Reperfusion After Macrovascular Recanalization - Xuesong Bai; Fan Yu; Qiuyue Tian; Wei Li; Araman Sha; Wenbo Cao; Yao Feng; Bin Yang; Yanfei Chen; Peng Gao; Yabing Wang; Jian Chen; et al. (Translational Stroke Research, 2023)

Silicate Ions Derived from Calcium Silicate Extract Decelerate Ang II-Induced Cardiac Remodeling - Xin Li; Yanxin Zhang; Qishu Jin; Qiaoyu Song; Chen Fan; Yiren Jiao; Chen Yang; Jiang Chang; Zhihong Dong; Yumei Que (Tissue Engineering and Regenerative Medicine, 2023)

Effect and mechanism of Fisetin on myocardial damage induced by Patulin - Dongmei Xu; Baigang Zhang; Chenghui Huang; Jiao Lu; Yang Li; Binggang Fu (Molecular Biology Reports, 2023)

Responses of rhizosphere microbial community structure and metabolic function to heavy metal coinhibition - Ganghui Jiao; Yi Huang; Hao Dai; Hang Gou; Zijing Li; Huibin Shi; Jinyan Yang; Shijun Ni (Environmental Geochemistry and Health, 2023)

Evaluating the ecological vulnerability of Chongqing using deep learning - Jun-Yi Wu; Hong Liu; Tong Li; Yuan Ou-Yang; Jing-Hua Zhang; Teng-Jiao Zhang; Yong Huang; Wen-Long Gao; Lu Shao (Environmental Science and Pollution Research, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

Assessing community assembly controls over community-scale nutrient resorption responses to nitrogen deposition - Xiao-Tao Lü; Sasha C. Reed; Shuang-Li Hou; Guo-Jiao Yang (Oecologia, 2023)

Ecological sensitivity and its driving factors in the area along the Sichuan–Tibet Railway - Yang Chen; Tingbin Zhang; Xiaobing Zhou; Jingji Li; Guihua Yi; Xiaojuan Bie; Jiao Hu; Bo Wen (Environment, Development and Sustainability, 2023)

The interspecific competition of tree plants in the presence of AM fungi and litter facilitates root morphological development and nutrition when compared with intraspecific competition - Yun Guo; Kaiping Shen; Tingting Xia; Yuejun He; Wenda Ren; Pan Wu; Yan Lin; Bangli Wu; Xu Han; Lu Gao; Jinting Li; Xiaorun Hu; et al. (Environmental Science and Pollution Research, 2023)

Safety and immunogenicity of a TK/ gI/gE gene-deleted feline herpesvirus-1 mutant constructed via CRISPR/Cas9 in feline - Mengfang Yang; Yuzhou Jiao; Yuanyuan Yan; Lisha Li; Xiaoshuai Hu; Zhe Jiao; Mengxia Li; Yixi Chen; Yuejun Shi; Zhou Shen; Guiqing Peng (Veterinary Microbiology, 2023)

Comparison of the cross-protection of PPRSV sublineage 8.7 MLV vaccines against the recombinant NADC30-like strain - Jianda Li; Kai Meng; Yu Wang; Zhao Wang; Jun Peng; Sufang Ren; Yuyu Zhang; Lihui Guo; Fei Liu; Tingting Lv; Jian Jiao; Yanyan Liu; et al. (Veterinary Microbiology, 2023)

Effect of vegetation restoration on soil erosion control and soil carbon and nitrogen dynamics: A meta-analysis - Ruizhe Yang; Shilong Yang; Lan-lan Chen; Ze Yang; Lingying Xu; Xianglei Zhang; Guanheng Liu; Xianglei Zhang; Chuanji Jiao; Ruihua Bai; Xuecheng Zhang; Bingnian Zhai; et al. (Soil and Tillage Research, 2023)

The spatial distribution, health risk, and cytotoxicity of metal(loid)s in contaminated field soils: The role of Cd in human gastric cells damage - Jiao-Yang Ma; Wei-Yu Li; Zi-Yue Yang; Jin-Zhou Su; Li Li; Yi-Rong Deng; Yun-Fei Tuo; You-Ya Niu; Ping Xiang (Science of The Total Environment, 2023)

A novel strategy for reinforcing cementation process coupling microbially induced carbonate precipitation (MICP) with cross-linked silk fibroin - Zhaorui Gu; Xiaojing Li; Jiao Wu; Shuang Niu; Pengbo Wang; Jun-Jie Zheng; Jinyong Yan; Li Xu; Min Yang; Yunjun Yan (Journal of Environmental Chemical Engineering, 2023)

A benchmark study of different numerical methods for predicting rock failure - Yi-Ming Li; Gao-Feng Zhao; Yuyong Jiao; Chengzeng Yan; Xun Wang; Luming Shen; Lei Yang; Zhengzhao Liang; Wanrun Li; Xiaoxiong Zhou; Xiaofeng Li; Feng Liu; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Study on time effect of acidified pulverized coal micro components and discussion on mathematical correlation of influencing factors - Qingfeng Xu; Shoujian Peng; Jiang Xu; Feng Jiao; Liang Cheng; Li Jia; Hailin Yang; Yan Yang; Rulin Liu; Seeram Ramakrishna (Fuel, 2023)

Co-gasification of municipal sewage sludge and cotton stalk enhanced by metal-enriched texture dyeing sludge additives for syngas production - Jingchun Yan; Yongbo Yan; Junjie Lai; Dongyan Jia; Yong Jiao; Xingyu Zhao; Li Yang (Fuel, 2023)

The influence of MPL addition on structure, interfacial compositions and physicochemical properties on infant formula fat globules - Yibo Liu; Lu Liu; Shuming Liu; Meng Sun; Yang Jiao; Jing Chai; Lianji Bi; Awa Fanny Massounga Bora; Xiaodong Li; Xiuxiu Zhang; Bincheng Liu; Jinju Cheng; et al. (Food Research International, 2023)

Effects of high-voltage electrostatic field (HVEF) on frozen shrimp (Solenocera melantho) based on UPLC-MS untargeted metabolism - Jiao Liu; Feixia Zhu; Jing Yang; Yue Wang; Xiaohan Ma; Yongjiang Lou; Yongyong Li (Food Chemistry, 2023)

A notable reversible thermochromic (3,3-difluoropyrrolidinium)2[CuCl4] with ferroelectricity and ferroelasticity - Shulin Jiao; Zheng Tang; Dong Li; Cuiping Xu; Zhu Yang; Peng Chen; Xiaofan Sun; Hong-Ling Cai; Xiaoshan Wu (Chemical Engineering Journal, 2023)

Room-temperature self-healing and recyclable polyurethane elastomers with high strength and superior robustness based on dynamic double-crosslinked structure - Yawen Xu; Shuai Zhou; Zihang Wu; Xinyu Yang; Na Li; Zhihui Qin; Tifeng Jiao (Chemical Engineering Journal, 2023)

Zinc-ion engineered Plant-based multifunctional hydrogels for flexible wearable strain Sensors, Bio-electrodes and Zinc-ion hybrid capacitors - Yang Wang; Weikun Jiang; Jiao Li; Md Sohel Ahommed; Chao Wang; Xingxiang Ji; Yu Liu; Guihua Yang; Yonghao Ni; Gaojin Lyu (Chemical Engineering Journal, 2023)

Tailoring porous three-dimensional (Co,Mn)(Co,Mn)2O4/PPy architecture towards high-performance cathode for aqueous zinc-ion batteries - Zuze Li; Yang Zheng; Qingze Jiao; Yun Zhao; Hansheng Li; Caihong Feng (Chemical Engineering Journal, 2023)

Superior triethylamine sensing platform based on MOF activated by carbon dots for photoelectric dual-mode in biphasic system - Xue-Chun Yang; Sha-Qi Fu; Qian-Li Li; Zheng Jiao; Jing-Tai Zhao; Yun Guo; Zhi-Jun Zhang; Song Gao; Ling-Li Cheng (Chemical Engineering Journal, 2023)

Dependence of cumulative CO2 emission and microbial diversity on the wetting intensity in drying-rewetting cycles in agriculture soil on the Loess Plateau - Panpan Jiao; Lei Yang; Xiaodong Nie; Zhongwu Li; Lin Liu; Peng Zheng (Soil Ecology Letters, 2023)

miR-10a-3p Participates in Nacre Formation in the Pearl Oyster Pinctada fucata martensii by Targeting NPY - Min Yang; Xin lei Li; Yu ting Zhang; Yue wen Deng; Yu Jiao (Marine Biotechnology, 2023)

A new chamigrane sesquiterpene from the rice fermentation of Antrodiella albocinnamomea - Min Guo; Ying-Zhong Liang; Xiu-Ming Cui; Lin-Jiao Shao; Yin-Fei Li; Xiao-Yan Yang (Natural Product Research, 2023)

Derivation of copper water quality criteria in Bohai Bay for the protection of local aquatic life and the ecological risk assessment - Yang Li; Di Mu; Hong-Qing Wu; Hai-Jiao Liu; Yong-Hui Wang; Guo-Chen Ma; Xue-Min Duan; Jian-Jun Zhou; Chun-Ming Zhang; Xing-Hua Lu; Xian-Hua Liu; Jun Sun; et al. (Marine Pollution Bulletin, 2023)

Overexpressed miRNA-nov-1 promotes manganese-induced apoptosis in N27 cells by regulating Dhrs3 to activate mTOR signaling pathway - Lina Wang; Liyu Su; Yuyan Cen; Jiao Li; Jianmin Yang; Yan Li (Toxicology, 2023)

Analysis of oil synthesis pathway in Cyperus esculentus tubers and identification of oleosin and caleosin genes - Youcheng Zhu; Ying Wang; Zunmiao Wei; Xiaokai Zhang; Bingyang Jiao; Yu Tian; Fan Yan; Jingwen Li; Yajing Liu; Xuguang Yang; Jinhao Zhang; Xinyue Wang; et al. (Journal of Plant Physiology, 2023)

Temperature uniformity of frozen pork with various combinations of fat and lean portions tempered in radio frequency - Xiangqing Chen; Feng Li; Juming Tang; Hu Shi; Jing Xie; Yang Jiao (Journal of Food Engineering, 2023)

An injectable and rapidly degraded carboxymethyl chitosan/polyethylene glycol hydrogel for postoperative antiadhesion - Meiyue Wang; Sen Lin; Mengzhe Liu; Jing Jiao; Hongyan Mi; Jingjing Sun; Yiming Liu; Ruiying Guo; Sirui Liu; Haojie Fu; Yanyu Yang; Rui Li (Chemical Engineering Journal, 2023)

Triple signal amplification strategy for ultrasensitive in situ imaging of intracellular telomerase RNA - Juan Song; Shan Li; Jie Zhou; Qiao Yu; Xue-Jiao Yang; Hong-Yuan Chen; Jing-Juan Xu (Analytica Chimica Acta, 2023)

Phellinilludins A–D, new illudane sesquiterpenes from the fungus Phellinus tremulae - Jiao-Xian Du; Xue-Mei Li; Hui-Xiang Yang; Si-Qiong Teng; Ji-Kai Liu; Tao Feng (Phytochemistry Letters, 2023)

Vegetation growth due to CO2 fertilization is threatened by increasing vapor pressure deficit - Shijie Li; Guojie Wang; Chenxia Zhu; Jiao Lu; Waheed Ullah; Daniel Fiifi Tawia Hagan; Giri Kattel; Yi Liu; Zhenyu Zhang; Yang Song; Shanlei Sun; Yi Zheng; et al. (Journal of Hydrology, 2023)

Expansion of C4 plants in South China and evolution of East Asian monsoon since 35 Ma: Black carbon records in the northern South China Sea - Mengjun Li; Shiming Wan; Christophe Colin; Hualong Jin; Debo Zhao; Wenqiang Pei; Wenjun Jiao; Yi Tang; Yang Tan; Xuefa Shi; Anchun Li (Global and Planetary Change, 2023)

MXene-based single atom catalysts for efficient CO2RR towards CO: A novel strategy for high-throughput catalyst design and screening - Shoufu Cao; Hongyu Chen; Yuying Hu; Jiao Li; Chunyu Yang; Zengxuan Chen; Shuxian Wei; Siyuan Liu; Zhaojie Wang; Daofeng Sun; Xiaoqing Lu (Chemical Engineering Journal, 2023)

Prenatal and postnatal decoration in residence are associated with childhood allergies and respiratory diseases: A 10-year repeated retrospective observational study - Lexiang Wang; Wei Yu; Baizhan Li; Yan Zhang; Jiao Cai; Zhuohui Zhao; Dan Norbäck; Qihong Deng; Hua Qian; Xin Zhang; Tingting Wang; Ling Zhang; et al. (Building and Environment, 2023)

Di-(2-ethylhexyl) phthalate exposure impairs cortical development in hESC-derived cerebral organoids - Ling Yang; Jiao Zou; Zhenle Zang; Liuyongwei Wang; Zhulin Du; Dandan Zhang; Yun Cai; Minghui Li; Qiyou Li; Junwei Gao; Haiwei Xu; Xiaotang Fan (Science of The Total Environment, 2023)

Interfacial composition in infant formulas powder modulate lipid digestion in simulated in-vitro infant gastrointestinal digestion - Xiaoxue Yu; Wenli Zhou; Zhibing Jia; Lu Liu; Xiaodong Li; Xiuxiu Zhang; Jinju Cheng; Chunli Ma; Lina Sun; Yang Jiao (Food Research International, 2023)

Correlations between flavor and glucosinolates and changes in quality-related physiochemical characteristics of Guizhou suancai during the fermentation process - Hongmei Di; Jie Ma; Yi Zhang; Jia Wei; Jiao Yang; Jun Ma; Jinlin Bian; Jingyi Xu; Zhi Huang; Yi Tang; Huanxiu Li; Yangxia Zheng; et al. (Food Chemistry, 2023)

Self-supply of H2O2 and O2 by a composite nanogenerator for chemodynamic therapy/hypoxia improvement and rapid therapy of biofilm-infected wounds - Junjie Wu; Peng Shen; Xian Qin; Yulu Yang; Chuanchuan Lin; Xuan Li; Wenbo Geng; Pengfei Gao; Lixue Chen; Li Miao; Yang Jiao; Bailong Tao (Chemical Engineering Journal, 2023)

Distribution patterns of landslides triggered by the 2022 Ms 6.8 Luding earthquake, Sichuan, China - Jian-qiang Zhang; Zong-ji Yang; Qing-kai Meng; Jiao Wang; Kai-heng Hu; Yong-gang Ge; Feng-huan Su; Bo Zhao; Bo Zhang; Ning Jiang; Yu Huang; Zai-yang Ming; et al. (Journal of Mountain Science, 2023)

The impact of irrigation modes on agricultural water-energy‑carbon nexus - Ruiming Zhu; Rongqin Zhao; Xiaojian Li; Xueyao Hu; Shixing Jiao; Liangang Xiao; Zhixiang Xie; Jin Sun; Shuai Wang; Qinglin Yang; Huifang Zhang; Xiaowei Chuai (Science of The Total Environment, 2023)

Subcellular distribution, chemical forms of cadmium and rhizosphere microbial community in the process of cadmium hyperaccumulation in duckweed - Meng-Meng Zheng; Dan Feng; Hui-Jiao Liu; Gui-Li Yang (Science of The Total Environment, 2023)

In situ Raman investigation of dissolved constituent and its evolution in pulp during Zn-S selective flotation with two-step pulp regulation - Haodong Li; Congren Yang; Wenqing Qin; Zuyuan Tian; Changfa Wu; Qian Wei; Fen Jiao (Minerals Engineering, 2023)

Understanding adsorption mechanisms of mercury over unburned carbon - Lijun Fang; Zhenxing Li; Chongchong Wu; Shaohui Jiao; Zhengyang Gao; Ian D. Gates; Xunlei Ding; Weijie Yang (Fuel, 2023)

Detection of melamine by using carboxyl-functionalized Ag-COF as a novel SERS substrate - Zichen Yang; Chaoqun Ma; Jiao Gu; Yamin Wu; Chun Zhu; Lei Li; Hui Gao; Wenzhi Yin; Zirui Wang; Guoqing Chen (Food Chemistry, 2023)

Wearable, nanofiber-based microfluidic systems with integrated electrochemical and colorimetric sensing arrays for multiplex sweat analysis - Xuecui Mei; Jiao Yang; Jiang Liu; Yingchun Li (Chemical Engineering Journal, 2023)

A rotating paper-based microfluidic sensor array combining Michael acceptors and carbon quantum dots for discrimination of biothiols - Liang Zhu; Xuecui Mei; Zhengchun Peng; Jiang Liu; Jiao Yang; Yingchun Li (Chemical Engineering Journal, 2023)

Photostable and printable fluorescence carbon quantum dots for advanced message encryption and specific reversible multiple sensing of Cu2+ and cysteine - Hui Li; Tiantian Xu; Zhe Zhang; Jiao Chen; Mengyao She; Yali Ji; Boyue Zheng; Zheng Yang; Shengyong Zhang; Jianli Li (Chemical Engineering Journal, 2023)

DNA Methylation Alterations and Their Association with High Temperature Tolerance in Rice Anthesis - Bo Li; Haiya Cai; Ke Liu; Bingzhuang An; Rong Wang; Fang Yang; Changli Zeng; Chunhai Jiao; Yanhao Xu (Journal of Plant Growth Regulation, 2023)
DNA methylation is an important epigenetic mechanism involved in gene regulation under environmental stresses in plants. However, little information is available regarding its responses to high temperature (HT) and association with HT tolerance in rice. In this study, fourteen rice genotypes were classified into the susceptible, moderate, and tolerant groups by the high temperature susceptibility index (HTSI) after HT treatment. The changes of DNA methylation in rice anthesis under normal and HT30 conditions were investigated using methylation-sensitive amplified polymorphism31 (MSAP). The MSAP results showed that the DNA methylation level significantly increased in the susceptible rice group and decreased in the tolerant rice group under HT treatment, while no significant difference was observed in the moderate rice group. More hypomethylation events were detected in the tolerant rice group, while more hypermethylation was detected in the susceptible rice group. Forty-four differentially methylated epiloci (DME) were generated under both control and HT conditions, which can clearly distinguish the susceptible, moderate, and tolerant genotypes via PCoA analysis. Approximately 43.18% of DMEs were determined to be tolerance-associated epiloci (TAEs). 63.15% TAEs were sequenced and annotated into 12 genes. Quantitative RT-PCR analysis showed that 12 TAE genes were mainly upregulated in 14 rice genotypes, and their expression levels were related to the HT tolerance of rice. Here, DEGs, generated from a number of genotypes, indicate higher probabilities for association with stress tolerance. Overall, these results suggest that DNA methylation regulation might play a key role in adaptation to HT stress in rice.

Soil organic carbon and nitrogen fractions as affected by straw and nitrogen management on the North China Plain - Guocui Ren; Xianfeng Zhang; Xiuli Xin; Wenliang Yang; Anning Zhu; Jiao Yang; Mengrou Li (Agriculture, Ecosystems & Environment, 2023)

Pyrrolizidine-producing weeds in tea gardens as an indicator of alkaloids in tea - Weiting Jiao; Luyao Wang; Lei Zhu; Tingting Shen; Taozhong Shi; Ping Zhang; Chen Wang; Hongping Chen; Xiangwei Wu; Tianyuan Yang; Qing X. Li; Rimao Hua (Food Additives & Contaminants Part B-Surveillance, 2023)

Sharply and simultaneously increasing pollutant accumulations in cells of organisms induced by rare earth elements in the environment of Nanjing - Qing Yang; Mengzhu Cheng; Qing Zhou; Lihong Wang; Yunlong Jiao; Yongqiang Liu; Shuya Zhang; Li Tan; Zhenhong Gu; Hong Zhu; Hongli Luo; Daozhe Lin; et al. (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Nonlinear dynamic characteristics of suction-vortex-induced pressure fluctuations based on chaos theory for a water jet pump unit - Weixuan Jiao; Heng Zhao; Li Cheng; Yang Yang; Zhun Li; Chuan Wang (Ocean Engineering, 2023)

Photo-sonodynamic therapy mediated with OLI_NPs to induce HPV16E7-specific immune response and inhibit cervical cancer in a Tc-1-grafted murine model - Guangzong Zhao; Shuning Chen; Jiao Zheng; Chenyang Li; Xiaowen Zhong; Yang Cao; Yue Zheng; Jiangchuan Sun; Shenyin Zhu; Shufang Chang (Journal of Photochemistry and Photobiology B: Biology, 2023)

Recovery of Ni matte from Ni-bearing electroplating sludge - Hong-Yang Wang; Yu Li; Shu-Qiang Jiao; Kuo-Chih Chou; Guo-Hua Zhang (Journal of Environmental Management, 2023)

Discovery of a fossil dwarf antelope outside of Africa and its implications for the late Miocene ecosystem in the northeast margin of the Tibetan Plateau - Shi-Qi Wang; Jimin Sun; Chunxiao Li; Shi-Jie Li; Jiao Fu; Qigao Jiangzuo; Luda Xing; Rong Yang (Gondwana Research, 2023)

Bioaccumulation and toxicity of terbuthylazine in earthworms (Eisenia fetida) - Shun Li; Ye Yuan; Xing Wang; Leiming Cai; Jiao Wang; Yuanji Zhao; Lei Jiang; Xu Yang (Environmental Toxicology and Pharmacology, 2023)

A novel partially carbonized Fe3O4@PANI-p catalyst for tetracycline degradation via peroxymonosulfate activation - Ya-qi Wang; Kun Li; Mao-yuan Shang; Yi-zhen Zhang; Yang Zhang; Bo-lai Li; Yu-jiao Kan; Xiao-qiang Cao; Jian Zhang (Chemical Engineering Journal, 2023)

An antibody cocktail with broadened mutational resistance and effective protection against SARS-CoV-2 - Chunyun Sun; Hang Chi; Fei Yuan; Jing Li; Ji Yang; Aihua Zheng; Fei Wang; Lingling Sun; Yanjing Zhang; Ping Hu; Lihua Jiao; Yongqiang Deng; et al. (Science China Life Sciences, 2023)

Production and characterization of novel thermo- and organic solvent–stable keratinase and aminopeptidase from Pseudomonas aeruginosa 4–3 for effective poultry feather degradation - Xiao-Dong Pei; Fan Li; Shi-Yang Yue; Xiao-Ni Huang; Tian-Tian Gao; Dao-Quan Jiao; Cheng-Hua Wang (Environmental Science and Pollution Research, 2023)

Brevibacillus daliensis sp. nov., Isolated From Soil in Machangqing Nature Reserve - Shi-Qiang Ye; Jiang-Yuan Zhao; Le-Le Li; Cheng Ling; Meng-Yu Zhang; Jing Tang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; Zhu-Feng Shi; et al. (Current Microbiology, 2023)

Responses of microbial community composition and respiration to soil moisture in eroded soil - Panpan Jiao; Lei Yang; Zhongwu Li; Chun Liu; Peng Zheng; Di Tong; Xiaofeng Chang; Chongjun Tang; Haibing Xiao (Applied Soil Ecology, 2023)

Biochar-blended manure modified by polyacrylamide to reduce soil colloidal phosphorus leaching loss - Fayong Li; Shuang He; Boyi Liu; Jiao Yang; Xiaochun Wang; Xinqiang Liang (Environmental Science and Pollution Research, 2022)

Overexpression of α-Tubulin Gene of Sugarcane (Saccharum spp. hybrids), SoTUA, Enhances Tobacco Tolerance to Cold Stress - Jiao-Yun Chen; Bo Sun; Qaisar Khan; Li-Tao Yang; Bao-Qing Zhang; Yong-Xiu Xing; Yang-Rui Li (Sugar Tech, 2022)

Isolation and identification of two Beauveria bassiana strains from silkworm, Bombyx mori - Yiling Zhang; Xu Yang; Jiao Zhang; Mingzhen Ma; Ping He; Yu Li; Qiang Wang; Xudong Tang; Zhongyuan Shen (Folia Microbiologica, 2022)

Microplastics in Surface Waters and Floodplain Sediments of the Dagu River in the Jiaodong Peninsula, China - Jie Jiao; Gang Chen; Zechuan Yang; Zhengyan Li; Hong Hu (Journal of Ocean University of China, 2022)

Local domestication of soybean leads to strong root selection and diverse filtration of root-associated bacterial communities - Wen Luo; Jieli Wang; Yuanli Li; Chang Wang; Shanshan Yang; Shuo Jiao; Gehong Wei; Weimin Chen (Plant and Soil, 2022)

Complete genome sequence of Aconitum amalgavirus 1, a distinct member of the genus Amalgavirus - Jie Yang; Ping-Xiu Lan; Jin-Ming Li; Xiao-Jiao Chen; Guan-Lin Tan; Tai-Yun Wei; Ru-Hui Li; Fan Li (Archives of Virology, 2022)

Improving the removal efficiency of nitrogen and organics in vertical-flow constructed wetlands: the correlation of substrate, aeration and microbial activity - Wenxue Xu; Baoshan Yang; Hui Wang; Shuzhi Wang; Keqin Jiao; Chuanfeng Zhang; Feng Li; Haixia Wang (Environmental Science and Pollution Research, 2022)

Variation in soybean root-associated microbiome between lateral roots with and without nodules - Jiamin Gao; Shi Chen; Yang Wang; Jiejun Qi; Xiaomeng Li; Gehong Wei; Shuo Jiao (Plant and Soil, 2022)

Transcriptome sequencing analysis of sex-related genes and miRNAs in the gonads of Mytilus coruscus - Min Wang; Jiao Xia; Muhammad Jawad; Wenbo Wei; Lang Gui; Xiao Liang; Jin-Long Yang; Mingyou Li (Frontiers in Marine Science, 2022)
Mytilus coruscus is a significant economic species in China’s eastern coastal areas. As a dioecious species, it lacks secondary sexual characteristics, which makes it difficult for selective breeding. However, limited research is carried out on the genetic data regarding reproductive development and gender differentiation. In the current study, de novo transcriptome sequencing analyses were used to detect gonad-specific genes and miRNAs in M. coruscus . By comparing testis and ovary, 159,970 unigenes and 300 miRNAs were obtained totally, of which differentially expressed genes and miRNAs were 9,566 and 25, respectively. Analysis of qRT-PCR showed that cyp26a , dmrt4 , foxl2 , gdf9 , 17β-hsd14 , sc6a9 , zar1 , and zp4 were highly expressed in the ovary as compared to the testis, while sox2 showed lower expression in the ovary. Expression of miR-750-3p, novel 1, and miR-193 was higher in the ovary than that in the testis, whereas the expression of miR-9-5p, miR-9-3p, miR-317, novel 124, miR-2d and miR-263b were lower in the ovary. Furthermore, analysis of miR-317 by Targetscan and MiRanda predicted to target dmrt4 and the luciferase reporter was performed to confirm it. Our research provides a molecular basis for understanding sexual development and reproductive regulation. Further research is needed on the mechanism of gonadal maturation and differentiation in M. coruscus .

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Transcriptome analysis of drought tolerance and utility assessment of DnaJ gene expression as a potential index for drought resistance evaluation in maize - Anyi Dong; Tinashe Zenda; Xinyue Liu; Yafei Wang; Jiao Li; Yatong Yang; Songtao Liu; Huijun Duan (Euphytica, 2022)

Correction to: Future precipitation changes in three key sub-regions of East Asia: the roles of thermodynamics and dynamics - Jiao Li; Yang Zhao; Deliang Chen; Yanzhen Kang; Hui Wang (Climate Dynamics, 2022)

Future precipitation changes in three key sub-regions of East Asia: the roles of thermodynamics and dynamics - Jiao Li; Yang Zhao; Deliang Chen; Yanzhen Kang; Hui Wang (Climate Dynamics, 2022)
Previous studies have projected an increase in future summer precipitation across East Asia (EA). This study investigates the relative contributions of thermodynamic and dynamic components to future precipitation changes in three key sub-regions of EA where the maximum centers of the historical precipitation are located (the tropical region, East China, and the Japan and Korea sector), and analyzes the causes of the changes in thermodynamic and dynamic components. Outputs from 30 climate models of the Coupled Model Intercomparison Project Phase 6 (CMIP6) are used. From these, the five best-performing models for historical summer precipitation climatology for EA are selected. The future summer precipitations in the three sub-regions over the near- to mid-term (2020–2069) and the long-term (2070–2095) are then examined using the multi-model ensemble mean of the five models selected (MMM05). The projections were driven by four combined scenarios of the Shared Socioeconomic Pathways (SSPs) and forcing levels of the Representative Concentration Pathways (SSP1-2.6, SSP2-4.5, SSP3-7.0, and SSP5-8.5). The results show that long-term precipitations under SSP5-8.5 are greater than those under the other scenarios across all sub-regions. After the 2070s under SSP5-8.5, a marked precipitation intensification is identified in all three sub-regions, but with different rates of increase. The projected precipitation increase is primarily attributed to the thermodynamic component, while the dynamic component related to circulation changes is relatively weak. Further analysis indicates that the pattern of the thermodynamic component in the three sub-regions is dominated by the climatological upward motion, mediated by an increase in moisture.

The effect of the nucleotides immediately upstream of the AUG start codon on the efficiency of translation initiation in sperm cells - Jiao-Jiao Shi; Yuan Cao; Qiu-Hua Lang; Yao Dong; Liu-Yuan Huang; Liu-Jie Yang; Jing-Jing Li; Xue-Xin Zhang; Dan-Yang Wang (Plant Reproduction, 2022)

Lipid metabolic disorders and physiological stress caused by a high-fat diet have lipid source-dependent effects in juvenile black seabream Acanthopagrus schlegelii - Yuedong Shen; Xuejiao Li; Yangguang Bao; Tingting Zhu; Zhaoxun Wu; Bingqian Yang; Lefei Jiao; Qicun Zhou; Min Jin (Fish Physiology and Biochemistry, 2022)

Fertility conversion between cytoplasmic maintainer lines and restorer lines through molecular marker-assisted selection in pepper (Capsicum annuum L.) - Fu-Sen Ren; Hai-Feng Yang; Yu-Shun Jiao; Rui-Ping Zhang; Zhi-Wei Guo; He-Juan Liu; Qiang Sun; Xi-Jun Li; Xiu-Fang Tan; Bei Zhang; Jun-Qi Zhen; Yan-Qi Dong (Biologia, 2022)

Study of the effect of intestinal immunity in neonatal piglets coinfected with porcine deltacoronavirus and porcine epidemic diarrhea virus - Jixiang Liang; Yang Li; Zhishan Yan; Zhe Jiao; Dapeng Peng; Wanpo Zhang (Archives of Virology, 2022)

Cohnella mopanensis sp. nov., a new Gram-negative bacterium isolated from soil in Xinping Mountain National Forest Park - Jing Tang; Jiang-Yuan Zhao; Le-Le Li; Zhang-Gui Ding; Shi-Qiang Ye; Cheng Ling; Meng-Yu Zhang; Song-Guo Liang; Jian-Yu Li; Pei-Wen Yang; Jiao Xiong; Lu-Yao Feng; et al. (Archives of Microbiology, 2022)

The α5-nAChR/PD-L1 axis facilitates lung adenocarcinoma cell migration and invasion - Ping Zhu; Guiyu Kang; Yang Jiao; Chengzhi Gui; Huiping Fan; Xiangying Li; Yanfei Jia; Lulu Zhang; Xiaoli Ma (Human Cell, 2022)

Qipengyuania thermophila sp. nov., isolated from a Chinese hot spring - Zi-Yu Zhao; Ting-Ting Xia; Jian-Yu Jiao; Lan Liu; Qing-Yang Su; Meng-Meng Li; Ai-Ping Lv; Yu-Ting Ouyang; Wen-Jun Li; Hong Ming (Archives of Microbiology, 2022)

New surface subsidence control technology based on upward backfilling method of bottom drainage roadway - Huazhe Jiao; Weilin Chen; Tiegang Zhang; Jianxin Yu; Liuhua Yang; Xinming Chen; Yunfei Wang; Zhenhua Li; Tianrang Jia (Arabian Journal of Geosciences, 2022)

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Changes of community composition strengthen the positive effects of nitrogen deposition on litter N:P stoichiometry in a semi-arid grassland - Shuang-Li Hou; Jun-Jie Yang; Jiang-Xia Yin; Hai-Wei Wei; Yan-Yu Hu; Zhi-Wei Zhang; Guo-Jiao Yang; Xiao-Tao Lü (Plant and Soil, 2022)

Analysis of studies on environmental measurements using diffusive gradients in thin-films (DGT) from 1994 to 2020 - Tian-Jiao Wei; Dong-Xing Guan; Xi-Yuan Li; Yi-Long Hao; H. Henry Teng; Ji-Feng Yang; Yao-Yang Xu; Gang Li (Journal of Soils and Sediments, 2022)

Electrochemical enhancement of high-efficiency wet removal of mercury from flue gas - Nai-jiao Xu; Sen Li; Yu-hong Fu; Zhao-yang Wang; Li-juan Feng; Ji Wang (Environmental Science and Pollution Research, 2022)

Comparison of the Variability of Small Extracellular Vesicles Derived from Human Liver Cancer Tissues and Cultured from the Tissue Explants Based on a Simple Enrichment Method - Jie Chen; Zhigang Jiao; Jianwen Mo; Defa Huang; Zhengzhe Li; Wenjuan Zhang; Tong Yang; Minghong Zhao; Fangfang Xie; Die Hu; Xiaoxing Wang; Xiaomei Yi; et al. (Stem Cell Reviews and Reports, 2022)
A potential use of small extracellular vesicles (sEVs) for diagnostic and therapeutic purposes has recently generated a great interest. sEVs, when purified directly from various tissues with proper procedures, can reflect the physiological and pathological state of the organism. However, the quality of sEV is affected by many factors during isolation, including separation of sEV from cell and tissues debris, the use of enzymes for tissue digestion, and the storage state of tissues. In the present study, we established an assay for the isolation and purification of liver cancer tissues-derived sEVs (tdsEVs) and cultured explants-derived sEVs (cedsEVs) by comparing the quality of sEVs derived from different concentration of digestion enzyme and incubation time. The nano-flow cytometry (NanoFCM) showed that the isolated tdsEVs by our method are purer than those obtained from differential ultracentrifugation. Our study thus establishes a simple and effective approach for isolation of high-quality sEVs that can be used for analysis of their constituents. Graphical abstract

Decreased peripheral mtDNA in methamphetamine use disorder - Ling-Yan Su; Yuan Li; Qianjin Liu; Lijin Jiao; Jing Shen; Lu-Xiu Yang; Ti-Fei Yuan; Yong-Gang Yao (Science China Life Sciences, 2022)

Influence of the rs6736 Polymorphism on Ischemic Stroke Susceptibility in Han Chinese Individuals via the Disruption of miR-7–1 Binding to the C14orf119 Gene - Xiaojing Guo; Lulu Zhu; Xinyi Zhao; Xulong Wu; Jialei Yang; Jiao Huang; Lian Gu; Li Su (Journal of Molecular Neuroscience, 2022)

Exogenous ascorbic acid application alleviates cadmium toxicity in seedlings of two wheat (Triticum aestivum L.) varieties by reducing cadmium uptake and enhancing antioxidative capacity - Zhen Zhou; Chang Wei; Haitao Liu; Qiujuan Jiao; Gezi Li; Jingjing Zhang; Biao Zhang; Weihuan Jin; Di Lin; Guo Chen; Suqin Yang (Environmental Science and Pollution Research, 2022)

Sorption and desorption of sex hormones in soil- and sediment-water systems: A review - Xiong Dai; Xingjian Yang; Bihai Xie; Jiajia Jiao; Xiuping Jiang; Chengyu Chen; Zhen Zhang; Zhili He; Hang Lin; Weisong Chen; Yongtao Li (Soil Ecology Letters, 2022)

Multi-omics analysis reveals metabolism of okadaic acid in gut lumen of rat - Yang Liu; Yang Lu; Yu-Hu Jiao; Da-Wei Li; Hong-Ye Li; Wei-Dong Yang (Archives of Toxicology, 2022)

Solvothermal-assisted Sol–Gel method Synthesized Amorphous Mesoporous Titania for Efficient Adsorption of Sb(III) in Aqueous Solution - Yepeng Yang; Liang Jiang; Qinyuan Tang; Mi Li; Peiwen Xu; Daomei Chen; Jiao He; Yongjuan Chen; Jiaqiang Wang (Water, Air, & Soil Pollution, 2022)

Transformation of fertilizer nitrogen in fluvo-aquic soils with different textures and its influencing factors - Shijie Ding; Xiuli Xin; Wenliang Yang; Xianfeng Zhang; Anning Zhu; Shaomin Huang; Jiao Yang; Guocui Ren; Mengrou Li (Plant and Soil, 2022)

A Novel De Novo TUBB3 Variant Causing Developmental Delay, Epilepsy and Mild Ophthalmological Symptoms in a Chinese Child - Jiao Xue; Zhenfeng Song; Shuyin Ma; Zhi Yi; Chengqing Yang; Fei Li; Kaixuan Liu; Ying Zhang (Journal of Molecular Neuroscience, 2022)

LncRNA H19 rs4929984 Variant is Associated with Coronary Artery Disease Susceptibility in Han Chinese Female Population - Jiao Huang; Minhua Li; Jinhong Li; Baoyun Liang; Zhaoxia Chen; Jialei Yang; Xiaojing Guo; Siyun Huang; Lian Gu; Li Su (Biochemical Genetics, 2021)

Enhanced SA and Ca2+ signaling results in PCD-mediated spontaneous leaf necrosis in wheat mutant wsl - Huijuan Li; Zhixin Jiao; Peipei Zhang; Yongjing Ni; Ting Wang; Jing Zhang; Junchang Li; Yumei Jiang; Xiwen Yang; Lei Li; Ziping Yao; Jishan Niu; et al. (Molecular Genetics and Genomics, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Terrestrial input of herbicides has significant impacts on phytoplankton and bacterioplankton communities in coastal waters - Liqiang Yang; Shanli Mou; Hongmei Li; Zenghu Zhang; Nianzhi Jiao; Yongyu Zhang (Limnology and Oceanography, 2021)
Herbicide use has increased very rapidly worldwide in recent decades, and some of these herbicides eventually enter the ocean. At present, herbicide pollution in the ocean has become a global environmental problem. Here, in a field investigation of 22 commonly used herbicide residues (triazine, phenylurea, and amide) in the Bohai Sea and the Yellow Sea, we found that the detection rate of herbicide residues within 100 km from shore was 100%. Notably, triazine herbicides have reached concentrations (up to 12.07 nmol L −1 ) that can significantly disturb phytoplankton and bacterioplankton communities in microcosm experiments. Under exposure to triazine herbicides at close to their total in situ concentrations, the photosynthesis of the phytoplankton community was significantly inhibited, which was reflected by the significant decrease of F v / F m (28.7–63.8%) of the phytoplankton community and dissolved oxygen content (18.1–32.2%) in seawater. Concurrently, the phytoplankton community structure underwent significant changes with the dominant group shifting from diatoms to dinoflagellates, due to the higher atrazine sensitivity of diatoms compared to facultative dinoflagellates. Triazine herbicide also significantly altered the bacterioplankton community structure and inhibited their metabolism of many carbon sources including carbohydrates, amino acids, and carboxylic acids. As phytoplankton and bacterioplankton are closely related, the impact of herbicide on the bacterioplankton community was clearly aggravated by the phytoplankton community. In view of the significance of phytoplankton and bacterioplankton communities in supporting marine food webs and biogeochemical cycles, a continuous increase in herbicide input in the future may seriously affect the stability of coastal oceans.

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Effects of periodically varying codes on separation of multisource blended data - Meng-Yao Jiao; Tian-Yue Hu; Yang Liu; Zhen-Zhen Yu; Shang-Lin Liang; Li-Chao Liu; Ji-Wei (Applied Geophysics, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Flexible reconfiguration of functional brain networks as a potential neural mechanism of creativity - Junchao Li; Natasza Orlov; Zengjian Wang; Bingqing Jiao; Yibo Wang; Huawei Xu; Hui Yang; Yingying Huang; Yan Sun; Peng Zhang; Rengui Yu; Ming Liu; et al. (Brain Imaging and Behavior, 2021)

Identification of miRNA targets in eggplant in response to Verticillium dahliae by degradome sequencing - Ting Li; Nianjiao Tao; Yuanmi Lin; Min Chen; Dongli Jiao; Chunmei Xue; Wenjiao Zhu; Qing Yang (European Journal of Plant Pathology, 2021)

The Fe3O4-modified biochar reduces arsenic availability in soil and arsenic accumulation in indica rice (Oryza sativa L.) - Yao Yao; Hang Zhou; Xiu-Lan Yan; Xiao Yang; Kang-Wen Huang; Juan Liu; Li-Juan Li; Jing-Yi Zhang; Jiao-Feng Gu; Yaoyu Zhou; Bo-Han Liao (Environmental Science and Pollution Research, 2021)

Nitrogen Enrichment Reduces Nitrogen and Phosphorus Resorption Through Changes to Species Resorption and Plant Community Composition - Xiao-Tao Lü; Shuang-Li Hou; Sasha Reed; Jiang-Xia Yin; Yan-Yu Hu; Hai-Wei Wei; Zhi-Wei Zhang; Guo-Jiao Yang; Zhuo-Yi Liu; Xing-Guo Han (Ecosystems, 2021)

In vitro Antioxidant Effects of Porphyra haitanensis Peptides on H2O2-Induced Damage in HepG2 Cells - Shengjun Chen; Jiao Yu; Xiao Hu; Xianqing Yang; Laihao Li; Bo Qi; Jianchao Deng (Journal of Ocean University of China, 2021)

Mutation in ε-Sarcoglycan Induces a Myoclonus-Dystonia Syndrome-Like Movement Disorder in Mice - Jiao Li; Yiqiong Liu; Qin Li; Xiaolin Huang; Dingxi Zhou; Hanjian Xu; Feng Zhao; Xiaoxiao Mi; Ruoxu Wang; Fan Jia; Fuqiang Xu; Jing Yang; et al. (Neuroscience Bulletin, 2021)

Application of Phage-Displayed Peptides in Tumor Imaging Diagnosis and Targeting Therapy - Chunyan Li; Jia Li; Ying Xu; Ying Zhan; Yu Li; Tingting Song; Jiao Zheng; Hong Yang (International Journal of Peptide Research and Therapeutics, 2021)

Classification of COVID-19 by Compressed Chest CT Image through Deep Learning on a Large Patients Cohort - Ziwei Zhu; Zhang Xingming; Guihua Tao; Tingting Dan; Jiao Li; Xijie Chen; Yang Li; Zhichao Zhou; Xiang Zhang; Jinzhao Zhou; Dongpei Chen; Hanchun Wen; et al. (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Pseudomonas laoshanensis sp. nov., isolated from peanut field soil - Ming-Qing Wang; Chu-Shu Zhang; Li-Na Yu; Wei-Qiang Yang; Kun Jiao; Kui-Jie Gong; Xiao-Yuan Chi; Jie Bi; Yu Song; Qing-Li Yang; Jian-Cheng Zhang; Gui-Wen Yang; et al. (Archives of Microbiology, 2021)

The MYB transcription factor Baymax1 plays a critical role in rice male fertility - Xiao-Jiao Xiang; Lian-Ping Sun; Ping Yu; Zheng-Fu Yang; Pei-Pei Zhang; Ying-Xin Zhang; Wei-Xun Wu; Dai-Bo Chen; Xiao-Deng Zhan; Riaz-Muhammad Khan; Adil Abbas; Shi-Hua Cheng; et al. (Theoretical and Applied Genetics, 2021)

Genomic characteristics and pathogenicity of a new recombinant strain of porcine reproductive and respiratory syndrome virus - Yang Li; Gaoxiao Xu; Xingqian Du; Lele Xu; Zhiqian Ma; Zhiwei Li; Yingtong Feng; Dian Jiao; Wenping Guo; Shuqi Xiao (Archives of Virology, 2021)

Stochastic processes shape the biogeographic variations in core bacterial communities between aerial and belowground compartments of common bean - Yang Liu; Da Li; Jiejun Qi; Ziheng Peng; Weimin Chen; Gehong Wei; Shuo Jiao (Environmental Microbiology, 2021)
Although studies of biogeography in soil bacterial communities have attracted considerable attention, the generality of these patterns along with assembly processes and underlying drivers is poorly understood in the inner tissues of plants. Plant tissues provide unique ecological habitats for microorganisms, which play an essential role in plant performance. Here, we compared core bacterial communities among five soil–plant associated compartments of common bean across five sampling sites in China. Neutral and null modelling consistently suggested that stochastic processes dominated the core community assembly processes and escalated from the belowground compartments to the inner tissues of aerial plant parts. The multiple distance‐decay relationships also varied and had flattened patterns in the stem endosphere, which were shaped by distinct environmental factors in each compartment. Coexistence patterns also varied in topological features, in addition with the sparsest networks in the stem endosphere resulted from the interaction with the stochastic processes. This study considerably expanded our understanding of various biogeographic patterns, assembly processes, and the underlying mechanisms of core bacterial communities between aerial and belowground compartments of common bean. That will provide a scientific basis for the reasonable regulation of core bacterial consortia to get better plant performance.

The evolution of a collaboration network and its impact on innovation performance under the background of government-funded support: an empirical study in the Chinese wind power sector - Jianling Jiao; Yuwen Xu; Jingjing Li; Ranran Yang (Environmental Science and Pollution Research, 2021)

Dynamic Variations in Brain Glycogen are Involved in Modulating Isoflurane Anesthesia in Mice - Ze Fan; Zhihao Zhang; Shiyi Zhao; Yuanyuan Zhu; Dong Guo; Bo Yang; Lixia Zhuo; Jiao Han; Rui Wang; Zongping Fang; Hailong Dong; Yan Li; et al. (Neuroscience Bulletin, 2020)
General anesthesia severely affects the metabolites in the brain. Glycogen, principally stored in astrocytes and providing the short-term delivery of substrates to neurons, has been implicated as an affected molecule. However, whether glycogen plays a pivotal role in modulating anesthesia–arousal remains unclear. Here, we demonstrated that isoflurane-anesthetized mice exhibited dynamic changes in the glycogen levels in various brain regions. Glycogen synthase (GS) and glycogen phosphorylase (GP), key enzymes of glycogen metabolism, showed increased activity after isoflurane exposure. Upon blocking glycogenolysis with 1,4-dideoxy-1,4-imino-D-arabinitol (DAB), a GP antagonist, we found a prolonged time of emergence from anesthesia and an enhanced δ frequency in the EEG (electroencephalogram). In addition, augmented expression of glycogenolysis genes in glycogen phosphorylase, brain (Pygb) knock-in (Pygb H11/H11 ) mice resulted in delayed induction of anesthesia, a shortened emergence time, and a lower ratio of EEG-δ. Our findings revealed a role of brain glycogen in regulating anesthesia–arousal, providing a potential target for modulating anesthesia.

Soil potassium is correlated with root secondary metabolites and root-associated core bacteria in licorice of different ages - Yang Liu; Yanmei Li; Wen Luo; Shuang Liu; Weimin Chen; Chun Chen; Shuo Jiao; Gehong Wei (Plant and Soil, 2020)

A fundamental theorem for eco-environmental surface modelling and its applications - Tianxiang Yue; Na Zhao; Yu Liu; Yifu Wang; Bin Zhang; Zhengping Du; Zemeng Fan; Wenjiao Shi; Chuanfa Chen; Mingwei Zhao; Dunjiang Song; Shihai Wang; et al. (Science China Earth Sciences, 2020)

Identification and evaluation of tobacco cytoplasmic male sterile line Nta(gla)S K326 generated from asymmetric protoplast fusion of Nicotiana glauca and N. tabacum followed by backcrossing with N. tabacum K326 - Xue-Jun Chen; Zhi-Jun Tong; Bing-Guang Xiao; Yong-Ping Li; Fang-Chan Jiao; Yong Li; Tao Pang; Dun-Huang Fang; Xing-Fu Wu; Yi-Han Zhang; He Xie; Ge Bai; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

MALDI–TOF-MS-based high throughput genotyping of mutations associated with body measurement traits in cattle - Yongfeng Liu; Yang Jiao; Peiwei Li; Linsen Zan (Mammalian Genome, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

High-level soluble expression of human Cu,Zn superoxide dismutase with high activity in Escherichia coli - Jin-Ling Yang; Xing-Lun Li; Feng-Lin Jiang; Ting Gong; Jing-Jing Chen; Tian-Jiao Chen; Ping Zhu (World Journal of Microbiology and Biotechnology, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Phosphoinositide-3-kinase regulatory subunit 1 gene polymorphisms are associated with schizophrenia and bipolar disorder in the Han Chinese population - Jiao Huang; Zhaoxia Chen; Lulu Zhu; Xulong Wu; Xiaojing Guo; Jialei Yang; Jianxiong Long; Li Su (Metabolic Brain Disease, 2020)

Characteristics and causes of the landslide on July 23, 2019 in Shuicheng, Guizhou Province, China - Siyuan Ma; Chong Xu; Xiwei Xu; Xiangli He; Haitao Qian; Qisong Jiao; Wei Gao; Huaining Yang; Yulong Cui; Pengfei Zhang; Kai Li; Hongrong Mo; et al. (Landslides, 2020)

Identification of potential key mRNAs and LncRNAs for psoriasis by bioinformatic analysis using weighted gene co-expression network analysis - Huotao Li; Chao Yang; Jiao Zhang; Wei Zhong; Lei Zhu; Yongfeng Chen (Molecular Genetics and Genomics, 2020)

Homeobox B8 Targets Sterile Alpha Motif Domain-Containing Protein 9 and Drives Glioma Progression - Wenping Ma; Hongze Jin; Wenjie Liu; Xiaojuan Li; Xingang Zhou; Xinwu Guo; Runfa Tian; Qi Cui; Junjie Luo; Yueying Jiao; Youtao Yu; Haifeng Yang; et al. (Neuroscience Bulletin, 2020)

Xanthohumol protects neuron from cerebral ischemia injury in experimental stroke - Yang Jiao; Yuze Cao; Xiaoyu Lu; Jianjian Wang; Aigul Saitgareeva; Xiaotong Kong; Chang Song; Jie Li; Kuo Tian; Shuoqi Zhang; Ming Bai; Shuang Li; et al. (Molecular Biology Reports, 2020)

Can environmental innovation benefit from outward foreign direct investment to developed countries? Evidence from Chinese manufacturing enterprises - Yu Bai; Qianqian Qian; Jianling Jiao; Lanlan Li; Fangyi Li; Ranran Yang (Environmental Science and Pollution Research, 2020)

Litorilituus lipolyticus sp. nov., isolated from intertidal sand of the Yellow Sea in China, and emended description of Colwellia asteriadis - Ang Liu; Yan-Jiao Zhang; Qing-Jie Xue; Hui Wang; Yuan-Yuan Yang; Feng Du; Long-Yu Zhao; Hong-Hua Zhang; Yun-Qing Li; Xiu-Zhen Li (Antonie van Leeuwenhoek, 2020)

Thin-layer fine-sand capping of polluted sediments decreases nutrients in overlying water of Wuhan Donghu Lake in China - Yang Jiao; Lei Xu; Qingman Li; Sen Gu (Environmental Science and Pollution Research, 2020)

Enhancement of the summer extreme precipitation over North China by interactions between moisture convergence and topographic settings - Yang Zhao; Deliang Chen; Jiao Li; Dandan Chen; Yi Chang; Juan Li; Rui Qin (Climate Dynamics, 2020)
This study investigates the roles of atmospheric moisture transport under the influence of topography for summer extreme precipitation over North China (NC) during 1979–2016. Based on rain gauge precipitation data and a reanalysis, 38 extreme precipitation days in NC during the 38 years were selected and associated moisture fluxes estimated. The results show that there is a dominant moisture influx of 311.8 kg m −1 s −1 into NC along its southern boundary from tropical oceans, and a secondary influx of 107.9 kg m −1 s −1 across its western boundary carried by mid-latitude westerlies. The outflux across the eastern boundary is 206.9 kg m −1 s −1 and across the northern boundary is 76.0 kg m −1 s −1 , giving a net moisture gain over NC of 136.8 kg m −1 s −1 . During extreme precipitation days, the moisture flux convergence (MFC) was much larger, exceeding 4 × 10 −5 kg m −1 s −1 . The MFC maximum core, the pronounced moisture transport, and the striking extreme precipitation zone over NC are all anchored to the east of the steep slopes of the surrounding topography. Moreover, a remarkably high humidity and strong upward motion also occur near steep slopes, indicating the critical role of the adjacent topography on the extreme precipitations. Simulations with and without the topography in NC using the Weather and Research Forecasting model for six selected out of the 38 extreme precipitation days demonstrate that the surrounding topography reinforces the MFC over NC by 16% relative to the case without terrain, primarily through enhanced wind convergence and higher moisture content, as well as stronger vertical motion induced by diabatic heating. The interactions between moisture convergence and topographic settings strengthen the extreme precipitation over NC.

H2S mediates apoptosis in response to inflammation through PI3K/Akt/NFκB signaling pathway - Yueying Wang; Chengyu Zhang; Chunmei Xu; Luping Feng; Anqi Li; Xiangyang Jin; Shuang Guo; Xianqin Jiao; Jingsong Liu; Yujie Guo; Heshui Zhu; Liqiang Han; et al. (Biotechnology Letters, 2020)

Genetic dissection of yield-related traits via genome-wide association analysis across multiple environments in wild soybean (Glycine soja Sieb. and Zucc.) - Dezhou Hu; Huairen Zhang; Qing Du; Zhenbin Hu; Zhongyi Yang; Xiao Li; Jiao Wang; Fang Huang; Deyue Yu; Hui Wang; Guizhen Kan (Planta, 2020)

Evidence for the paternal mitochondrial DNA in the crucian carp-like fish lineage with hybrid origin - Shi Wang; Ni Jiao; Lu Zhao; Meiwen Zhang; Pei Zhou; Xuexue Huang; Fangzhou Hu; Conghui Yang; Yuqin Shu; Wuhui Li; Chun Zhang; Min Tao; et al. (Science China Life Sciences, 2020)

Dynamics of greenhouse gas emission induced by different burrowing activities of fossorial vertebrates in the Qinghai–Tibetan Plateau alpine meadow ecosystem - Yan Zhou; Lei Jing; Shengwu Jiao; Anping Chen; Nana Li; Jialin Lei; Meng Yang; Yifei Jia; Cai Lu; Guangchun Lei (International Journal of Biometeorology, 2020)

Biochar-related studies from 1999 to 2018: a bibliometrics-based review - Dongyang Li; Rui Zhao; Xing Peng; Zhifei Ma; Ying Zhao; Tiancheng Gong; Mengyang Sun; Yuxin Jiao; Tianxue Yang; Beidou Xi (Environmental Science and Pollution Research, 2020)

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

Rare variants in FANCA induce premature ovarian insufficiency - Xi Yang; Xiaojin Zhang; Jiao Jiao; Feng Zhang; Yuncheng Pan; Qiqi Wang; Qing Chen; Baozhu Cai; Shuyan Tang; Zixue Zhou; Siyuan Chen; Hao Yin; et al. (Human Genetics, 2019)
Premature ovarian insufficiency (POI) is a major cause of reduced female fertility and affects approximately 1% women under 40 years of age. Recent advances emphasize the genetic heterogeneity of POI. Fanconi anemia (FA) genes, traditionally known for their essential roles in DNA repair and cytogenetic instability, have been demonstrated to be involved in meiosis and germ cell development. Here, we conducted whole-exome sequencing (WES) in 50 Han Chinese female patients with POI. Rare missense variants were identified in FANCA ( Fanconi anemia complementation group A ): c.1772G > A (p.R591Q) and c.3887A > G (p.E1296G). Both variants are heterozygous in the patients and very rare in the human population. In vitro functional studies further demonstrated that these two missense variants of FANCA exhibited reduced protein expression levels compared with the wild type, suggesting the partial loss of function. Moreover, mono-ubiquitination levels of FANCD2 upon mitomycin C stimulation were significantly reduced in cells overexpressing FANCA variants. Furthermore, a loss-of-function mutation of Fanca was generated in C57BL/6 mice for in vivo functional assay. Consistently, heterozygous mutated female mice ( Fanca + / − ) showed reduced fertility and declined numbers of follicles with aging when compared with the wild-type female mice. Collectively, our results suggest that heterozygous pathogenic variants in FANCA are implicated in non-syndromic POI in Han Chinese women, provide new insights into the molecular mechanisms of POI and highlight the contribution of FANCA variants in female subfertility.

Nicotine in action: cigarette smoking modulated homotopic functional connectivity in schizophrenia - Wei Liao; Siqi Yang; Jiao Li; Yun-Shuang Fan; Xujun Duan; Qian Cui; Huafu Chen (Brain Imaging and Behavior, 2019)

Does Biochar Induce Similar Successions of Microbial Community Structures Among Different Soils? - Yang Song; Xiaona Li; Min Xu; Wei Jiao; Yongrong Bian; Xinglun Yang; Chenggang Gu; Fang Wang; Xin Jiang (Bulletin of Environmental Contamination and Toxicology, 2019)

Association of long noncoding RNA H19 polymorphisms with the susceptibility and clinical features of ischemic stroke in southern Chinese Han population - Jiao Huang; Jialei Yang; Jinhong Li; Zhaoxia Chen; Xiaojing Guo; Siyun Huang; Lian Gu; Li Su (Metabolic Brain Disease, 2019)

TP53 Polymorphism Contributes to the Susceptibility to Bipolar Disorder but Not to Schizophrenia in the Chinese Han Population - Jialei Yang; Xulong Wu; Jiao Huang; Zhaoxia Chen; Guifeng Huang; Xiaojing Guo; Lulu Zhu; Li Su (Journal of Molecular Neuroscience, 2019)

Half-dose ticagrelor versus high-dose clopidogrel in reducing platelet reactivity in acute coronary syndrome patients with high on-clopidogrel platelet reactivity (divide study) - Guang Zhong Liu; Song Zhang; Dang Hui Sun; Jing Shi; Wan Lan Bo; Wen Nan Wang; Chong Yang Zhang; Zhong Hua Wang; Wei Feng; Mei Jiao He; Yuan Yuan Liu; Shuang Li; et al. (European Journal of Clinical Pharmacology, 2019)

Chemical composition of essential oils from four Rhododendron species and their repellent activity against three stored-product insects - Li Bai; Mei-Ling Jiao; Hong-Yuan Zang; Shan-Shan Guo; Yang Wang; Yu-Li Sang; Shu-Shan Du (Environmental Science and Pollution Research, 2019)

A strategy for developing high-resolution DNA barcodes for species discrimination of wood specimens using the complete chloroplast genome of three Pterocarpus species - Lichao Jiao; Yang Lu; Tuo He; Jianing Li; Yafang Yin (Planta, 2019)

Pre-colonization of PGPR triggers rhizosphere microbiota succession associated with crop yield enhancement - Yang Zhang; Xu Gao; Zongzhuan Shen; Chengzhi Zhu; Zixuan Jiao; Rong Li; Qirong Shen (Plant and Soil, 2019)

Two new steroids with cytotoxicity from the marine sponge Dactylospongia elegans collected from the South China Sea - Jing Li; Zhuo Wang; Fan Yang; Wei-Hua Jiao; Hou-Wen Lin; Shi-Hai Xu (Natural Product Research, 2019)

Changes in the soil microbial community are associated with the occurrence of Panax quinquefolius L. root rot diseases - Jinglong Jiang; Miao Yu; Ruping Hou; Li Li; Xuming Ren; Chengjin Jiao; Lingjuan Yang; Hao Xu (Plant and Soil, 2019)

Neuroprotective Autophagic Flux Induced by Hyperbaric Oxygen Preconditioning is Mediated by Cystatin C - Zongping Fang; Yun Feng; Yuheng Li; Jiao Deng; Huang Nie; Qianzhi Yang; Shiquan Wang; Hailong Dong; Lize Xiong (Neuroscience Bulletin, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

Comparison of multi-criteria analysis methodologies for the prioritization of arsenic-contaminated sites in the southwest of China - Ruihui Chen; Yanna Xiong; Jiao Li; Yanguo Teng; Haiyang Chen; Jie Yang (Environmental Science and Pollution Research, 2019)

FcRγ deficiency improves survival in experimental sepsis by down-regulating TLR4 signaling pathway - Zhi-Min Wei; Zhuo Wang; Xiao-Jian Wan; Xian-Jing Li; Yi-Xing Li; Yang Bai; Xue Yang; Yong Yang; Shun-Chang Jiao; Zhe-Feng Liu (Immunologic Research, 2019)

Geraniin promotes osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs) via activating β-catenin: a comparative study between BMSCs from normal and osteoporotic rats - Jiao Mo; Renhua Yang; Fan Li; Bo He; Xiaochao Zhang; Yuqin Zhao; Zhiqiang Shen; Peng Chen (Journal of Natural Medicines, 2019)

The complete mitochondrial genome of the blue king crab, Paralithodes platypus (Decapoda: Lithodidae) - Li Feng; Jiao Yang; Qing-Yu Han; Gui-Fang Zhao (Conservation Genetics Resources, 2018)

Two new alkylated furan derivatives with antifungal and antibacterial activities from the plant endophytic fungus Emericella sp. XL029 - Xia Wu; Xue-Jiao Pang; Lu-Lin Xu; Ting Zhao; Xin-Yu Long; Qiong-Yin Zhang; Hai-Li Qin; Deng-Feng Yang; Xiao-Long Yang (Natural Product Research, 2018)

Protein tyrosine phosphatase 1B inhibitory activity of cone oils from Juniperus chinensis cv. Kaizuca and in silico theoretical explanation - Chen Fang; Dongyu Gu; Jiao Yang; Minjing Li; Hengming Liu; Yi Yang (Natural Product Research, 2018)

Human activity during the late Pleistocene in the Lop Nur region, northwest China: Evidence from a buried stone artifact - Kangkang Li; Xiaoguang Qin; Xiaoyan Yang; Bing Xu; Lei Zhang; Guijin Mu; Dong Wei; Chunxue Wang; Yong Wu; Xiaohong Tian; Yongchong Lin; Wen Li; et al. (Science China Earth Sciences, 2018)

Accurate Reconstruction of Porous Materials via Stochastic Fusion of Limited Bimodal Microstructural Data - Hechao Li; Pei-En Chen; Yang Jiao (Transport in Porous Media, 2018)

The Dysfunction of the Cerebellum and Its Cerebellum-Reward-Sensorimotor Loops in Chronic Spontaneous Urticaria - Yuming Wang; Jiliang Fang; Ping Song; Yan Bao; Wenwen Song; Jiao Liu; Courtney Lang; Kristen Jorgenson; Minyoung Jung; Dong Shen; Shasha Li; Ruirui Sun; et al. (The Cerebellum, 2018)

Polyphenolic compounds from Malus hupehensis and their free radical scavenging effects - Qingwen Hu; Ying-Ying Chen; Qi-Yang Jiao; Afsar Khan; Jimiao Shan; Gui-Dong Cao; Feng Li; Chao Zhang; Hong-Xiang Lou (Natural Product Research, 2018)

Hydrogeological Model for Groundwater Prediction in the Shennan Mining Area, China - Peng Xie; Wenping Li; Dongdong Yang; Junjie Jiao (Mine Water and the Environment, 2018)

Chromosome-wide gene dosage rebalance may benefit tumor progression - Honglei Zhang; Xing Yang; Xu Feng; Haibo Xu; Qin Yang; Li Zou; Mei Yan; Dequan Liu; Xiaosan Su; Baowei Jiao (Molecular Genetics and Genomics, 2018)

Species composition, functional and phylogenetic distances correlate with success of invasive Chromolaena odorata in an experimental test - Yu‐Long Zheng; Jean H. Burns; Zhi‐Yong Liao; Yang‐ping Li; Jie Yang; Ya‐jun Chen; Jiao‐lin Zhang; Yu‐guo Zheng (Ecology Letters, 2018)
Biotic resistance may influence invasion success; however, the relative roles of species richness, functional or phylogenetic distance in predicting invasion success are not fully understood. We used biomass fraction of Chromolaena odorata , an invasive species in tropical and subtropical areas, as a measure of ‘invasion success’ in a series of artificial communities varying in species richness. Communities were constructed using species from Mexico (native range) or China (non‐native range). We found strong evidence of biotic resistance: species richness and community biomass were negatively related with invasion success; invader biomass was greater in plant communities from China than from Mexico. Harvesting time had a greater effect on invasion success in plant communities from China than on those from Mexico. Functional and phylogenetic distances both correlated with invasion success and more functionally distant communities were more easily invaded. The effects of plant‐soil fungi and plant allelochemical interactions on invasion success were species‐specific.

Analysis of short-term and sub-chronic effects of ambient air pollution on preterm birth in central China - Xiangyu Li; Yisi Liu; Feifei Liu; Yuxin Wang; Xuhao Yang; Junfeng Yu; Xiaowei Xue; Anqi Jiao; Yuanan Lu; Liqiao Tian; Shiquan Deng; Hao Xiang (Environmental Science and Pollution Research, 2018)

CHOP/caspase-3 signal pathway involves in mitigative effect of selenium on lead-induced apoptosis via endoplasmic reticulum pathway in chicken testes - He Huang; Yang An; Wanying Jiao; Jinghan Wang; Shu Li; Xiaohua Teng (Environmental Science and Pollution Research, 2018)

Outcomes of EC-MPS combined with low-dose tacrolimus in DCD kidney transplantation for high-risk DGF recipients - Li-zi Jiao; Chen-guang Ding; Pu-xun Tian; Xiao-ming Ding; Xiao-ming Pan; He-li Xiang; Xiao-hui Tian; Yang Li; Jin Zheng; Wu-jun Xue (Journal of Zhejiang University-SCIENCE B, 2018)

Complete plastid genome of Larix potaninii var. macrocarpa, an endangered conifer endemic to China - Dai-Yu Qiu; Jiao Yang; Li Feng; Ding-Wen Ni; Cai-Xia Huang; Zhong-Hu Li (Conservation Genetics Resources, 2018)

Chemical composition and α-amylase inhibitory activity of the essential oil from Sabina chinensis cv. Kaizuca leaves - Dongyu Gu; Chen Fang; Jiao Yang; Minjing Li; Hengming Liu; Yi Yang (Natural Product Research, 2018)

Altered Structure and Intrinsic Functional Connectivity in Post-stroke Aphasia - Mi Yang; Pu Yang; Yun-Shuang Fan; Jiao Li; Dezhong Yao; Wei Liao; Huafu Chen (Brain Topography, 2018)

Intraspecific variation drives community-level stoichiometric responses to nitrogen and water enrichment in a temperate steppe - Xiao-Tao Lü; Yan-Yu Hu; Hai-Yang Zhang; Hai-Wei Wei; Shuang-Li Hou; Guo-Jiao Yang; Zhuo-Yi Liu; Xiao-Bo Wang (Plant and Soil, 2018)

Changes in nitrogen and phosphorus cycling suggest a transition to phosphorus limitation with the stand development of larch plantations - Tao Yan; Xiao-Tao Lü; Jiao-Jun Zhu; Kai Yang; Li-Zhong Yu; Tian Gao (Plant and Soil, 2018)

Complementary feeding patterns among ethnic groups in rural western China - Peng-fei Qu; Ya Zhang; Jia-mei Li; Ruo Zhang; Jiao-mei Yang; Fang-liang Lei; Shan-shan Li; Dan-meng Liu; Shao-nong Dang; Hong Yan (Journal of Zhejiang University-SCIENCE B, 2018)

Consistent responses of litter stoichiometry to N addition across different biological organization levels in a semi-arid grassland - Shuang-Li Hou; Jiang-Xia Yin; Jun-Jie Yang; Hai-Wei Wei; Guo-Jiao Yang; Yan-Yu Hu; Xing-Guo Han; Xiao-Tao Lü (Plant and Soil, 2017)

Identification of a novel reassortant A (H9N6) virus in live poultry markets in Poyang Lake region, China - Heng Zhang; Mingbin Liu; Xiaoxu Zeng; Xiang Zhao; Zhiqiang Deng; Lei Yang; Wenbing Chen; Zi Li; Ming Jiao; Wen Xia; Bin Han; Haiying Chen; et al. (Archives of Virology, 2017)

The influence of simulated microgravity on proliferation and apoptosis in U251 glioma cells - Jiao Zhao; He Ma; Leitao Wu; Liang Cao; Qianqian Yang; Haijun Dong; Zongren Wang; Jing Ma; Zhen Li (In Vitro Cellular & Developmental Biology - Animal, 2017)

Berry syndrome: a rare cardiac malformation with extra-cardiac findings - Jingya Li; Ya Yang; Xiaomin Duan; Lanzhong Jin; Lin Zheng; Xin Zhang; Haiyan Wei; Yan Sun; Xiaolin Zhang; Pei Li; Jiao Yang; Ning Ma; et al. (Science China Life Sciences, 2017)

Insights into the Therapeutic Potential of Heparinized Collagen Scaffolds Loading Human Umbilical Cord Mesenchymal Stem Cells and Nerve Growth Factor for the Repair of Recurrent Laryngeal Nerve Injury - Yongqin Pan; Genlong Jiao; Jingge Yang; Rui Guo; Jinyi Li; Cunchuan Wang (Tissue Engineering and Regenerative Medicine, 2017)

Effects of Exogenous γ-Aminobutyric Acid (GABA) on Photosynthesis and Antioxidant System in Pepper (Capsicum annuum L.) Seedlings Under Low Light Stress - Yuefei Li; Yong Fan; Ying Ma; Zhen Zhang; Haobo Yue; Lijie Wang; Jing Li; Yang Jiao (Journal of Plant Growth Regulation, 2017)

Response of microbial biomass and bacterial community composition to fertilization in a salt marsh in China - Yuexin Ma; Wei Tao; Changfa Liu; Jiao Liu; Zhiping Yang; Jin Li; Jichen Liu (Acta Oceanologica Sinica, 2017)

Serum Protein-Based Profiles as Novel Biomarkers for the Diagnosis of Alzheimer’s Disease - Shu Yu; Yue-Ping Liu; Hai-Liang Liu; Jie Li; Yang Xiang; Yu-Hui Liu; Shu-Sheng Jiao; Lu Liu; Yajiang Wang; Weiling Fu (Molecular Neurobiology, 2017)

Cinnamic, myristic and fumaric acids in tobacco root exudates induce the infection of plants by Ralstonia solanacearum - Shili Li; Chen Xu; Jiao Wang; Bing Guo; Liang Yang; Juanni Chen; Wei Ding (Plant and Soil, 2017)

Beyond the Arcuate Fasciculus: Damage to Ventral and Dorsal Language Pathways in Aphasia - Mi Yang; Yibo Li; Jiao Li; Dezhong Yao; Wei Liao; Huafu Chen (Brain Topography, 2017)

The complete mitochondrial genome of the Burmese roofed turtle (Batagur trivittata) (Testudines: Geoemydidae) - Li Feng; Jiao Yang; Yan-Ping Zhang; Gui-Fang Zhao (Conservation Genetics Resources, 2017)

Rubricella aquisinus gen. nov., sp. nov., a novel member of the family Rhodobacteraceae - Li-Qiang Yang; Lili Tang; Lan Liu; Nimaichand Salam; Wen-Jun Li; Xiaowei Liu; Guangzhi Jin; Nianzhi Jiao; Yongyu Zhang (Antonie van Leeuwenhoek, 2017)

17-Methoxyl-7-Hydroxy-Benzene-Furanchalcone Ameliorates Myocardial Ischemia/Reperfusion Injury in Rat by Inhibiting Apoptosis and Autophagy Via the PI3K–Akt Signal Pathway - Feifei Xuan; Jie Jian; Xing Lin; Jianchun Huang; Yang Jiao; Wansu Huang; Juman Li; Zhi Shi; Renbin Huang (Cardiovascular Toxicology, 2017)

Genome-wide scans reveal variants at EDAR predominantly affecting hair straightness in Han Chinese and Uyghur populations - Sijie Wu; Jingze Tan; Yajun Yang; Qianqian Peng; Manfei Zhang; Jinxi Li; Dongsheng Lu; Yu Liu; Haiyi Lou; Qidi Feng; Yan Lu; Yaqun Guan; et al. (Human Genetics, 2016)

Genome-Wide Analysis of the R2R3 MYB Subfamily Genes in Lotus (Nelumbo nucifera) - Jiao Deng; Ming Li; Longyu Huang; Mei Yang; Pingfang Yang (Plant Molecular Biology Reporter, 2016)

Neuroprotective Effect of Osthole on Neuron Synapses in an Alzheimer’s Disease Cell Model via Upregulation of MicroRNA-9 - Shaoheng Li; Yuhui Yan; Yanan Jiao; Zhong Gao; Yang Xia; Liang Kong; Yingjia Yao; Zhenyu Tao; Jie Song; Yaping Yan; Guangxian Zhang; Jingxian Yang (Journal of Molecular Neuroscience, 2016)

Trade‐offs and evolution of thermal adaptation in the Irish potato famine pathogen Phytophthora infestans - Li‐Na Yang; Wen Zhu; E‐Jiao Wu; Ce Yang; Peter H. Thrall; Jeremy J. Burdon; Li‐Ping Jin; Li‐Ping Shang; Jiasui Zhan (Molecular Ecology, 2016)
Temperature is one of the most important environmental parameters with crucial impacts on nearly all biological processes. Due to anthropogenic activity, average air temperatures are expected to increase by a few degrees in coming decades, accompanied by an increased occurrence of extreme temperature events. Such global trends are likely to have various major impacts on human society through their influence on natural ecosystems, food production and biotic interactions, including diseases. In this study, we used a combination of statistical genetics, experimental evolution and common garden experiments to investigate the evolutionary potential for thermal adaptation in the potato late blight pathogen, Phytophthora infestans , and infer its likely response to changing temperatures. We found a trade‐off associated with thermal adaptation to heterogeneous environments in P. infestans, with the degree of the trade‐off peaking approximately at the pathogen's optimum growth temperature. A genetic trade‐off in thermal adaptation was also evidenced by the negative association between a strain's growth rate and its thermal range for growth, and warm climates selecting for a low pathogen growth rate. We also found a mirror effect of phenotypic plasticity and genetic adaptation on growth rate. At below the optimum, phenotypic plasticity enhances pathogen's growth rate but nature selects for slower growing genotypes when temperature increases. At above the optimum, phenotypic plasticity reduces pathogen's growth rate but natural selection favours for faster growing genotypes when temperature increases further. We conclude from these findings that the growth rate of P. infestans will only be marginally affected by global warming.

Phosphorylation of Connexin 43 by Cdk5 Modulates Neuronal Migration During Embryonic Brain Development - Guang-Jian Qi; Qiang Chen; Li-Jun Chen; Yang Shu; Lu-Lu Bu; Xiao-Yun Shao; Pei Zhang; Feng-Juan Jiao; Jin Shi; Bo Tian (Molecular Neurobiology, 2016)

Elevated Expression of VEGF-C and Its Receptors, VEGFR-2 and VEGFR-3, in Patients with Mesial Temporal Lobe Epilepsy - Fei-Ji Sun; Yu-Jia Wei; Song Li; Wei Guo; Xin Chen; Shi-Yong Liu; Jiao-Jiang He; Qing Yin; Hui Yang; Chun-Qing Zhang (Journal of Molecular Neuroscience, 2016)

Characterization of the whole chloroplast genome sequence of Acer davidii Franch (Aceraceae) - Yun Jia; Jiao Yang; Yan-Ling He; Ying He; Chuan Niu; Lin-Lin Gong; Zhong-Hu Li (Conservation Genetics Resources, 2016)

Simultaneous elastic parameter inversion in 2-D/3-D TTI medium combined later arrival times - Chao-ying Bai; Tao Wang; Shang-bei Yang; Xing-wang Li; Guo-jiao Huang (Journal of Seismology, 2016)

Erratum to: The Clinical Utility of TIMP3 Expression in ACTH-Secreting Pituitary Tumor - Bowen Sun; Xiaohai Liu; Yakun Yang; Congxin Dai; Ying Li; Yonghui Jiao; Zhenqing Wei; Yong Yao; Ming Feng; Xinjie Bao; Kan Deng; Ning Wang; et al. (Journal of Molecular Neuroscience, 2016)

Effects of organic matter content and composition on ammonium adsorption in lake sediments - Li Zhang; Shengrui Wang; Lixin Jiao; Yanping Li; Jiachun Yang; Rui Zhang; Shuang Feng; Juan Wang (Environmental Science and Pollution Research, 2016)

Novel Development of a qPCR Assay Based on the rpoB Gene for Rapid Detection of Cronobacter spp. - Yuanhong Li; Qiming Chen; Hua Jiang; Yang Jiao; Fengxia Lu; Xiaomei Bie; Zhaoxin Lu (Current Microbiology, 2016)

Silibinin Prevents Autophagic Cell Death upon Oxidative Stress in Cortical Neurons and Cerebral Ischemia-Reperfusion Injury - Min Wang; Yu-Jiao Li; Yi Ding; Hui-Nan Zhang; Ting Sun; Kun Zhang; Le Yang; Yan-Yan Guo; Shui-Bing Liu; Ming-Gao Zhao; Yu-Mei Wu (Molecular Neurobiology, 2016)

Hymenochaetopsis nom. nov. proposed to replace Pseudochaete (Hymenochaetales, Basidiomycota) with descriptions of H. laricicola sp. nov and H. gigasetosa new to China - Jiao Yang; Li-Dan Dai; Shuang-Hui He (Mycological Progress, 2016)

Association between occupational stressors and type 2 diabetes among Chinese police officers: a 4-year follow-up study in Tianjin, China - Hao Yu; Jin-chuan Liu; Ya-jiao Fan; Chen Li; Li-xin Zhang; Xi Chen; Song Yue; Wen-li Lu; Xi-lin Yang; Nai-jun Tang (International Archives of Occupational and Environmental Health, 2016)

proBDNF Attenuates Hippocampal Neurogenesis and Induces Learning and Memory Deficits in Aged Mice - Jia Chen; Cheng-Ren Li; Heng Yang; Juan Liu; Tao Zhang; Shu-Sheng Jiao; Yan-Jiang Wang; Zhi-Qiang Xu (Neurotoxicity Research, 2016)

The Clinical Utility of TIMP3 Expression in ACTH-Secreting Pituitary Tumor - Bowen Sun; Xiaohai Liu; Yakun Yang; Congxin Dai; Ying Li; Yonghui Jiao; Zhenqing Wei; Yong Yao; Ming Feng; Xinjie Bao; Kan Deng; Ning Wang; et al. (Journal of Molecular Neuroscience, 2016)

EDARV370A associated facial characteristics in Uyghur population revealing further pleiotropic effects - Qianqian Peng; Jinxi Li; Jingze Tan; Yajun Yang; Manfei Zhang; Sijie Wu; Yu Liu; Juan Zhang; Pengfei Qin; Yaqun Guan; Yi Jiao; Zhaoxia Zhang; et al. (Human Genetics, 2016)

Cloning and Functional Analysis of Thylakoidal Ascorbate Peroxidase (TAPX) Gene in Sugarcane - Sheng Wang; Kun-Kun Zhang; Xing Huang; Yan-Jiao Fan; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2015)

In situ determination of hafnium isotopes from rutile using LA-MC-ICP-MS - Yang Li; YueHeng Yang; ShuJuan Jiao; FuYuan Wu; JinHui Yang; LieWen Xie; Chao Huang (Science China Earth Sciences, 2015)

Heat-induced unfolding of apo-CP43 studied by fluorescence spectroscopy and CD spectroscopy - Qing-Jie Xiao; Zai-Geng Li; Jiao Yang; Qing He; Lei Xi; Lin-Fang Du (Photosynthesis Research, 2015)

Environmental Enrichment Ameliorates Neonatal Sevoflurane Exposure-Induced Cognitive and Synaptic Plasticity Impairments - Mu-huo Ji; Xing-ming Wang; Xiao-ru Sun; Hui Zhang; Ling-sha Ju; Li-li Qiu; Jiao-jiao Yang; Min Jia; Jing Wu; Jianjun Yang (Journal of Molecular Neuroscience, 2015)

Retraction Note to: An infectious molecular clone in early infection with HIV-1 subtype CRF01_AE strains: construction and biological properties - Hong-Wei Wang; Bin Zhu; Li-Juan Hou; Guang-Jian Lu; Lu-Yang Jiao; Bao-Sheng Shen (Molecular Biology Reports, 2015)

TGF-β1 and TIMP-4 regulate atrial fibrosis in atrial fibrillation secondary to rheumatic heart disease - Yu Sun; Zi-Yang Huang; Zhen-Hua Wang; Cui-Ping Li; Xian-Liang Meng; Yun-Jiao Zhang; Feng Su; Nan Ma (Molecular and Cellular Biochemistry, 2015)

TMDL for phosphorus and contributing factors in subtropical watersheds of southern China - Cen Meng; Yuyuan Li; Yi Wang; Wen Yang; Junxia Jiao; Meihui Wang; Manyi Zhang; Yong Li; Jinshui Wu (Environmental Monitoring and Assessment, 2015)

Anti-CD69 monoclonal antibody treatment inhibits airway inflammation in a mouse model of asthma - Hui-ying Wang; Yu Dai; Jiao-li Wang; Xu-yan Yang; Xin-guo Jiang (Journal of Zhejiang University-SCIENCE B, 2015)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Marinactinospora endophytica sp. nov., isolated from a medicinal plant - Min-Jiao Liu; Thi-Nhan Khieu; Rui Gao; Wael N. Hozzein; Hong-Fei Wang; Wei Yang; Salam Nimaichand; Zhi Xiong; Yan-Qing Duan; Wen-Jun Li (Antonie van Leeuwenhoek, 2015)

P5-2 of rice black-streaked dwarf virus is a non-structural protein targeted to chloroplasts - Xiao-Ya Liu; Jian Yang; Li Xie; Jing Li; Xi-Jiao Song; Jian-Ping Chen; Heng-Mu Zhang (Archives of Virology, 2015)

Detecting and monitoring the micro-motions of trapped people hidden by obstacles based on wavelet entropy with low centre-frequency UWB radar - Yan Wang; Xiao Yu; Yang Zhang; Hao Lv; Teng Jiao; Guohua Lu; Zhao Li; Sheng Li; Xijing Jing; Jianqi Wang (International Journal of Remote Sensing, 2015)

FOXO3-mediated up-regulation of Bim contributes to rhein-induced cancer cell apoptosis - Jiao Wang; Shu Liu; Yancun Yin; Mingjin Li; Bo Wang; Li Yang; Yangfu Jiang (Apoptosis, 2015)

RETRACTED ARTICLE: An infectious molecular clone in early infection with HIV-1 subtype CRF01_AE strains: construction and biological properties - Hong-Wei Wang; Bin Zhu; Li-Juan Hou; Guang-Jian Lu; Lu-Yang Jiao; Bao-Sheng Shen (Molecular Biology Reports, 2015)

Characteristics of nitrogen loading and its influencing factors in several typical agricultural watersheds of subtropical China - Yuyuan Li; Junxia Jiao; Yi Wang; Wen Yang; Cen Meng; Baozhen Li; Yong Li; Jinshui Wu (Environmental Science and Pollution Research, 2015)

KIM-1 and NGAL as biomarkers of nephrotoxicity induced by gentamicin in rats - Qi-hui Luo; Meng-lu Chen; Feng-jiao Sun; Zheng-li Chen; Ming-yang Li; Wen Zeng; Li Gong; An-chun Cheng; Xi Peng; Jing Fang; Li Tang; Yi Geng (Molecular and Cellular Biochemistry, 2014)

Using hourly measurements to explore the role of secondary inorganic aerosol in PM2.5 during haze and fog in Hangzhou, China - Roeland Cornelis Jansen; Yang Shi; Jianmin Chen; YunJie Hu; Chang Xu; Shengmao Hong; Jiao Li; Min Zhang (Advances in Atmospheric Sciences, 2014)

Isolation and characterization of a C-repeat binding factor (CBF)-like gene in cassava (Manihot esculenta Crantz) - Ruimei Li; Yimeng Ji; Jie Fan; Chenglong Yang; Yuan Yao; Yang Zhou; Ruijun Duan; Jiao Liu; Shaoping Fu; Xinwen Hu; Jianchun Guo (Acta Physiologiae Plantarum, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Deep-Red Phosphorescent Iridium(III) Complexes Containing 1-(Benzo[b] Thiophen-2-yl) Isoquinoline Ligand: Synthesis, Photophysical and Electrochemical Properties and DFT Calculations - Gao-Nan Li; Ying Zou; Yi-Ding Yang; Jiao Liang; Feng Cui; Tao Zheng; Hui Xie; Zhi-Gang Niu (Journal of Fluorescence, 2014)

Paraxerula ellipsospora, a new Asian species of Physalacriaceae - Jiao Qin; Yan-Jia Hao; Zhu L. Yang; Yan-Chun Li (Mycological Progress, 2014)

Effect of Cocaine on Ion Channels and Glutamatergic EPSCs in Noradrenergic Locus Coeruleus Neurons - L. N. Liu; F. P. Zhu; M. Y. Song; X. J. Kang; S. J. Shang; X. Y. Zhang; H. D. Xu; S. S. Teng; B. Liu; S. T. Kuo; W. Liu; M. L. Li; et al. (Journal of Molecular Neuroscience, 2014)

Characteristics of dental morphology in the Xinjiang Uyghurs and correlation with the EDARV370A variant - JingZe Tan; QianQian Peng; JinXi Li; YaQun Guan; LiPing Zhang; Yi Jiao; YaJun Yang; SiJia Wang; Li Jin (Science China Life Sciences, 2014)

Study on phosphorus loadings in ten natural and agricultural watersheds in subtropical region of China - Yuyuan Li; Cen Meng; Ru Gao; Wen Yang; Junxia Jiao; Yong Li; Yi Wang; Jinshui Wu (Environmental Monitoring and Assessment, 2014)

Influence of hydrophilic amino acids and GC-content on expression of recombinant proteins used in vaccines against foot-and-mouth disease virus in Escherichia coli - Hongfei Wei; Mingli Fang; Min Wan; Hua Wang; Peiyin Zhang; Xiaoping Hu; XiuLi Wu; Ming Yang; Yongsheng Zhang; Lei Zhou; Chengfeng Jiao; Li Hua; et al. (Biotechnology Letters, 2014)

Efficient isolation of ion beam-induced mutants for homoeologous loci in common wheat and comparison of the contributions of Glu-1 loci to gluten functionality - Yushuang Yang; Shiming Li; Kunpu Zhang; Zhenying Dong; Yiwen Li; Xueli An; Jing Chen; Qiufang Chen; Zhen Jiao; Xin Liu; Huanju Qin; Daowen Wang (Theoretical and Applied Genetics, 2014)

Comparison between conidia and blastospores of Esteya vermicola, an endoparasitic fungus of the pinewood nematode, Bursaphelenchus xylophilus - Yun-Bo Wang; Zhi-Hong Yang; Jiao-Jiao Yu; Yong-An Zhang; Jian-Jie Xue; Zheng Li; Jing-Jie Li; Chun-Yan Wang; Zhen Wang; Jin-Gang Hou; Shahraz Begum; Li-Juan Gu; et al. (World Journal of Microbiology and Biotechnology, 2013)

MK-2206 induces cell cycle arrest and apoptosis in HepG2 cells and sensitizes TRAIL-mediated cell death - Peng Jiao; Yun-Sheng Zhou; Juan-Xia Yang; Ya-Li Zhao; Qiang-Qiang Liu; Chuang Yuan; Feng-Ze Wang (Molecular and Cellular Biochemistry, 2013)

Novel POMGnT1 mutations cause muscle-eye-brain disease in Chinese patients - Hui Jiao; Hiroshi Manya; Shuo Wang; Yanzhi Zhang; Xiaoqing Li; Jiangxi Xiao; Yanling Yang; Kazuhiro Kobayashi; Tatsushi Toda; Tamao Endo; Xiru Wu; Hui Xiong (Molecular Genetics and Genomics, 2013)

Dishevelled-2 silencing reduces androgen-dependent prostate tumor cell proliferation and migration and expression of Wnt-3a and matrix metalloproteinases - Yinhui Yang; Li Jiao; Jianguo Hou; Chuanliang Xu; Linhui Wang; Yongwei Yu; Yun Li; Chun Yang; Xia Wang; Yinghao Sun (Molecular Biology Reports, 2013)

Changes in the BAG1 Expression of Schwann Cells After Sciatic Nerve Crush - Hao Wu; Yonghua Liu; Yuan Zhou; Long Long; Xinghai Cheng; Lei Ji; Hai Weng; Tao Ding; Jiao Yang; Haixiang Wei; Ming Li; Weipeng Huan; et al. (Journal of Molecular Neuroscience, 2013)

Folate receptor-mediated boron-10 containing carbon nanoparticles as potential delivery vehicles for boron neutron capture therapy of nonfunctional pituitary adenomas - CongXin Dai; Feng Cai; Kuo Chu Hwang; YongMao Zhou; ZiZhu Zhang; XiaoHai Liu; SiHai Ma; YaKun Yang; Yong Yao; Ming Feng; XinJie Bao; GuiLin Li; et al. (Science China Life Sciences, 2013)

Toll-like receptor 4/nuclear factor-κB signaling pathway is involved in ACTG-toxin H-mediated anti-inflammatory effect - Xinying Yang; Guojian Zhang; Xuelian Tang; Jieying Jiao; Sung Yeon Kim; Joo Young Lee; Tianjiao Zhu; Dehai Li; Yong Gab Yun; Qianqun Gu; Hyun Park (Molecular and Cellular Biochemistry, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Tenuibacillus halotolerans sp. nov., a novel bacterium isolated from a soil sample from a salt lake in Xinjiang, China and emended description of the genus Tenuibacillus - Xu-Hong Gao; Sheng Gao; Yu Zhou; Hui-Lin Guan; Yun-Jiao Zhang; Man Jia; Hua-Wei Huang; Dong-Xu Yang; Wen-Jun Li; Shu-Kun Tang (Antonie van Leeuwenhoek, 2013)

RETRACTED ARTICLE: Isolation and analysis of homoeologous genes encoding gibberellin 2-oxidase 3 isozymes in common wheat - QIUFANG CHEN; HUIYUAN YA; SHIMING LI; YANPING YANG; GUANGYONG QIN; XUELI AN; DAOWEN WANG; KUNPU ZHANG; ZHEN JIAO (Journal of Genetics, 2012)

Paenibacillus thermophilus sp. nov., a novel bacterium isolated from a sediment of hot spring in Fujian province, China - Yu Zhou; Sheng Gao; Da-Qiao Wei; Ling-Ling Yang; Xing Huang; Jie He; Yun-Jiao Zhang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

BRCA1: a new candidate gene for bovine mastitis and its association analysis between single nucleotide polymorphisms and milk somatic cell score - Zhengrong Yuan; Guiyan Chu; Yang Dan; Jiao Li; Lupei Zhang; Xue Gao; Huijiang Gao; Junya Li; Shangzhong Xu; Zhihua Liu (Molecular Biology Reports, 2012)

Primary dolostone formation related to mantle-originated exhalative hydrothermal activities, Permian Yuejingou section, Santanghu area, Xinjiang, NW China - YiQun Liu; Xin Jiao; Hong Li; MingSheng Yuan; Wan Yang; XiaoHu Zhou; Hao Liang; DingWu Zhou; ChaoYang Zheng; Qin Sun; ShuangShuang Wang (Science China Earth Sciences, 2012)

Association of SERPINE2 gene with the risk of chronic obstructive pulmonary disease and spirometric phenotypes in northern Han Chinese population - Li An; Ting Yang; Yongbiao Zhang; Yingxiang Lin; Hong Zhang; Xia Jiao; Lin Hua; Huaping Dai; Chen Wang (Molecular Biology Reports, 2012)

Molecular characterization, expression pattern, polymorphism and association analysis of bovine ADAMTSL3 gene - Yongfeng Liu; Linsen Zan; Shuanping Zhao; Yaping Xin; Yang Jiao; Kui Li (Molecular Biology Reports, 2012)

Human amniotic membrane derived-mesenchymal stem cells induce C6 glioma apoptosis in vivo through the Bcl-2/caspase pathways - Hongliang Jiao; Fangxia Guan; Bo Yang; Jianbin Li; Laijun Song; Xiang Hu; Ying Du (Molecular Biology Reports, 2012)

A Promising CdSe@CdS-Quantum Dots-Cysteine for the Determination of Trace IgE by Solid Substrate Room Temperature Phosphorescence Immunoassay - Jia-Ming Liu; Li-ping Lin; Zhen-Bo Liu; Min-Lan Yang; Xin-xing Wang; Li-hong Zhang; Ma-lin Cui; Li Jiao (Journal of Fluorescence, 2012)

Streptomyces fildesensis sp. nov., a novel streptomycete isolated from Antarctic soil - Jing Li; Xin-Peng Tian; Tian-Jiao Zhu; Ling-Ling Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

Structural Characterization of Extracellular Polysaccharides Produced by the Marine Fungus Epicoccum nigrum JJY-40 and Their Antioxidant Activities - Hai-Hong Sun; Wen-Jun Mao; Jie-Ying Jiao; Jia-Chao Xu; Hong-Yan Li; Yin Chen; Xiao-Hui Qi; Yan-Li Chen; Jian Xu; Chun-Qi Zhao; Yu-Jiao Hou; Yu-Pin Yang (Marine Biotechnology, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Antigenically dominant proteins within the human liver mitochondrial proteome identified by monoclonal antibodies - YanFang Ju; JinJu Yang; Rong Liu; XiaoLan Liu; XueMei Du; Li Liu; ZhiCheng Chen; Jun Chi; ShuEr Liu; Yuan Gao; JianEn Gao; ShunChang Jiao; et al. (Science China Life Sciences, 2011)

Protective effects of Flos lonicera extract on acute liver injury by dimethylnitrosamine-induced in rats - Yang Teng; Chang Hai Sun; Guangzhi Li; Guangchen Sun; Yui Nomachi; Junko Yokota; Saburo Yoshioka; Jinbo Gang; Shuqing Jiao; Yu Zhang; Mitsuhiko Miyamura (Journal of Natural Medicines, 2010)

Spectral indices for estimating ecological indicators of karst rocky desertification - Yuemin Yue; Bing Zhang; Kelin Wang; Bo Liu; Ru Li; Quanjun Jiao; Qingqing Yang; Mingyang Zhang (International Journal of Remote Sensing, 2010)

Distributions of soil phosphorus in China’s densely populated village landscapes - Jiaguo Jiao; Erle C. Ellis; Ian Yesilonis; Junxi Wu; Hongqing Wang; Huixin Li; Linzhang Yang (Journal of Soils and Sediments, 2010)

Identification and characterization of a novel capsid protein encoded by Singapore grouper iridovirus ORF038L - Qing Jiao Wan; Jie Gong; Xiao Hong Huang; You Hua Huang; Sheng Zhou; Zheng Liang Ou-Yang; Jian Hao Cao; Li Li Ye; Qi Wei Qin (Archives of Virology, 2010)

Isolation and characterization of new microsatellite markers from the burbot (Lota Lota) - Ying Y. Zhao; Jiao Li; Xiao W. Sun; Li Q. Liang; Xiao D. Zhu; Hong S. Ou-yang (Conservation Genetics, 2009)

Estimating Long-Term Changes in China’s Village Landscapes - Erle Christopher Ellis; Nagaraj Neerchal; Kui Peng; Hong Sheng Xiao; Hongqing Wang; Yan Zhuang; Shou Cheng Li; Jun Xi Wu; Jia Guo Jiao; Hua Ouyang; Xu Cheng; Lin Zhang Yang (Ecosystems, 2009)

Mineralogical and geochemical study of a newly discovered mafic granulite, northwest China: Implications for tectonic evolution of the Altay Orogenic Belt - Han‐Lin Chen; Zi‐Long Li; Shu‐Feng Yang; Chuan‐Wan Dong; Wen‐Jiao Xiao; Yoshiaki Tainosho (Island Arc, 2006)
A mafic granulite body was newly discovered in the Altay Orogenic Belt, northwest China. The rocks comprise a suite of coarse‐grained and fine‐grained granulites. Orthopyroxenes (hypersthenes) in the rocks have high X Mg and low Al 2 O 3 contents, whereas clinopyroxenes have low TiO 2 and Al 2 O 3 contents. Amphiboles and biotites have a high Mg/(Mg + Fe 2+ ) ratio and low contents of F and Cl. The peak metamorphic pressure–temperature (P–T) conditions are estimated as 750–780°C and 6–7 kbar, and retrograde P–T conditions are in the range of 590–620°C and 2.3–3.7 kbar, indicating significant decompression. Metamorphic reactions and P–T estimates define a clockwise P–T path. Geochemically, the rocks are high in Mg/(Mg + Fe) and Al 2 O 3 , depleted in U, Th, K and Rb, and characterized by light rare earth element enrichment and a weak positive Eu anomaly. The Altay mafic granulite shows depleted Nb, P and Ti contents in the mid‐oceanic ridge basalt normalized spider diagram. The geochemical characteristics suggest that the protolith of the Altay mafic granulite was calc‐alkaline basalt and andesite with an island‐arc affinity. The rock has a high 143 Nd/ 144 Nd ratio with ɛNd(0) > 0, indicating derivation from a mantle‐depleted source. In the present study, a two‐stage model for the evolution of the Altay mafic granulite is proposed: an early stage in which calc‐alkaline basalt and andesite with island‐arc affinity were subducted into a deeper level of the crust and subjected to granulite‐facies metamorphism generating the mafic granulite, followed by the later stage exhumation of the system into the upper crust by the late Paleozoic thrusting.

The impact of cropland conversion on environmental effect in the Loess Plateau: a pilot study based on the national experimental bases - Wang Fei; Li Rui; Jiao Feng; Yang Qingke; Tian Junliang (Journal of Geographical Sciences, 2005)